PSMG3 enhances the proliferation and metastasis of hepatocellular carcinoma via inhibiting HDAC6 - Shuaihui Wu; Caiyan Wu; Huibin Wang; Yang Shi; Ping Jiang; Dilinigeer Tayier; Kunlei Wang; Qian Cheng; Xinyin Li; Qifeng Wei; Zhixiang Cheng; Bo Liao; et al. (Functional & Integrative Genomics, 2026)

Qianlong Shutong Formula alleviates benign prostatic hyperplasia associated with the regulation of inflammation, fibrosis and the Hippo-YAP/TAZ pathway - Ze-chao Zhang; Xue-jin Ye; Chang-jie Shang; Zhi-feng Wei; Yu Chen; Shu-ping Huang; Min Zhu; Bo-tao Tang; Tai-sheng Liang (Tissue and Cell, 2026)

A multi-dimensional early warning model for coal and gas outburst risk based on microseismic monitoring with seismic velocity tomography-identified risk zones - Chao Zhou; Bo Li; Dazhao Song; Xueqiu He; Zhenlei Li; Liming Qiu; Yingjie Zhao; Shan Yin; Jintao Dang; Ping Wang (Journal of Applied Geophysics, 2026)

Reshaping microbial function through Blastobotrys adeninivorans bioaugmentation to enhance flavor quality in ripened pu-erh tea: Insights from multi-omics analysis - Teng Wang; Yan Ma; Qiuyue Chen; Nianguo Bo; Guangqiang Wei; Yanhui Guan; Yiqing Guan; Dihan Yang; Hongyan Gao; Fan Yang; Xiaying Tao; Ping Liang; et al. (International Journal of Food Microbiology, 2026)

Progressive collapse behaviour of multi-storey reinforced concrete sub-frames with slab strips: Experimental tests and numerical modelling - Hui-Qiang Yan; Yan-Ren Wang; Shao-Bo Kang; Yi Chen; Xing-Ju Yang; Chun-Ping Tang (Engineering Structures, 2026)

Emulsion bipolar membrane electrodialysis for sustainable phenol recovery from coking carbolic oil - Yan-Ping Lv; Xiong-Bo Hu; Hui-Chao Liang; Qing Chen; Wei-Ming Zhang (Desalination, 2026)

Vitamin C-engineered lamellar PbI2 framework for efficient and stable FAPbI3 perovskite solar cells - Hao Xiong; Chenzhe Xu; Yixiong Lin; Ping Li; Linqin Jiang; Bo Wu; Baisheng Sa; Yu Qiu (Chemical Engineering Journal, 2026)

Decadal gelatinization and phenological advancement of small jellyfish in Laizhou Bay, Bohai Sea - Ping Fu; Shan Sun; Huichao Jiang; Jianlong He; Ling Cheng; Bo Su; Hongyan Xing; Yuanqing Ma; Lijuan Liu; Yuting Zhao; Juan Zhang; Xiaowen Zhang (Marine Pollution Bulletin, 2026)

Isolation and pathogenicity of Actinobacillus pleuropneumoniae Serovar 19 in pigs - Bo Hong; Guangyuan Yi; XvDong Lin; YingXuan Ye; XiaoLi Liu; Ahmed H. Ghonaim; Yang Zeng; Shuo Zhang; Ping Bai; Wentao Li; Xuexiang Yu; Qigai He (Veterinary Microbiology, 2026)

Effect of socket-depth ratio on the bearing behavior of rock-socketed piles over an underlying karst cave - Bai Yang; Cheng Jiang; Zheng-bo Zhao; Chao Qin; Wang-Ping Qian; Cheng-xian Cen (Transportation Geotechnics, 2026)

Pretreatment-driven component-oriented conversion and microbial community assembly: Selective regulation of coupled methane and vivianite recovery in anaerobic digestion - Lulu Dai; Shaoyang Ma; Ping Zhang; Xianhong Wang; Bo Dong; Yixin Liu; Weihua Li (Journal of Environmental Chemical Engineering, 2026)

RETRACTED: Metastable conformational regulation in heat-induced gluten aggregation: multiscale experiments and molecular dynamics reveal distinct roles of HMW-GS at the Glu-B1 locus - Bo Wang; Ping-ping Zhang; Rong-ran Zhang; Tian Lv; Yue Zhang; Pei Wang; Qin Zhou; Dong Jiang; Xin-long Dai; Hao Jiang; Tao Yang (Food Hydrocolloids, 2026)

Flexural behavior and interfacial debonding of RC beams strengthened with CFRP-reinforced Engineered Geopolymer Composites (EGC) - Kai-Di Peng; Hui-Xiang Wang; Zhi-Hao Hao; Lan-Ping Qian; Yu-Lei Bai; Bo-Tao Huang (Engineering Structures, 2026)

Structurally decoupled strongly hydrophobic biocathode enables high-performance flexible enzymatic biofuel cells for self-powered sensing - Jie Gao; Ang Xu; Jia Wu; Jinlong He; Ping Wang; Ying Liu; Qiang Wang; Bo Xu; Yuanyuan Yu; Man Zhou (Chemical Engineering Journal, 2026)

Upcycling hazardous electric arc furnace dust into defect-rich ZnO/ZnFe2O4 heterojunction for in situ H2O2 electrogeneration and water purification - Lijuan Jia; Bo Liu; Guoxing Mu; Yiqiang Ji; Fang Wang; Rui Cao; Ping Ning; Shuo Cui; Jiayu Feng (Chemical Engineering Journal, 2026)

“Precursors-in-action” nanoreactor: Coordination-activated self-assembly of cu/Fe bimetallic multifunctional metalloenzyme mimics for cascade-amplified breast cancer therapy - Peng Wang; Xin-Yi Zhang; Ying-Ying Han; Zhi-Yuan Li; Qing-Hua Shen; Long-Bo Yu; Cai-Ping Tan (Chemical Engineering Journal, 2026)

A divalent nanoparticle vaccine confers robust protective immunity against serotype O FMDV and SVA in pigs - Nan Cao; Yamei Li; Xinghua Chen; Hehai Li; Linxing Tian; Zihui Hu; Yin Bo; Feifei Diao; Huanchun Chen; Xiangmin Li; Ping Qian (Veterinary Microbiology, 2026)

Pesticide exposure in Eriocheir sinensis: Oxidative stress, endocrine disruption, gut–hepatopancreas axis impairment, and systems toxicology - Shi-Rong Li; Dan-Dan Bian; Xiang Lu; Shuang-Gui Dai; Bo-Ping Tang; Qiu-Ning Liu (Pesticide Biochemistry and Physiology, 2026)

Antifungal effects of β-cyclodextrin/Carvacrol polyvinyl alcohol film against Aspergillus chevalieri in stored wheat grains - Chen Yang; Yi-Ming Wang; Wen-Bo Sun; Yang-Yong Lv; Huan-Chen Zhai; Shan Wei; Ping-An Ma; Yuan-Sen Hu; Shuai-Bing Zhang (Journal of Stored Products Research, 2026)

Improving the efficiency of a bioaerosol disinfection reactor by using ultraviolet C light-emitting diodes and titanium dioxide photocatalyst - Chien-Ping Wang; Bo Yu Liao; Fan-Chun Hsieh; Qiang Jia; Tien-Li Chang (Journal of Photochemistry and Photobiology B: Biology, 2026)

Metabolomic insights into flavonoid migration and bioactivity enhancement in Apocynum venetum tea during hot-water brewing - Syeda Wajeeha Gillani; Kuo Xu; Ping Li; Xueli Lu; Bo Wang; Lu Wang; Juying Wang; Guosheng Wang; Ruolin Song; Tingting Ren; Chen Meng; Yiqiang Li; et al. (Food Chemistry, 2026)

Menthol-functionalized polyphenol‑copper nanoparticles for spatiotemporally modulable blood-brain barrier permeability and multimodal therapeutics-triggered immune response against glioblastoma - Xinyue Liu; Suyi Liu; Kunhui Sun; Yibao Jin; Ping Wang; Xiaowei Wang; Bo Peng; Bing Wang; Xie-an Yu (Chemical Engineering Journal, 2026)

Multipathway Pesticide Exposure and Cross‐Scale Risk Assessment in Integrated Rice–Crab Aquaculture - Dan‐Dan Bian; Shi‐Rong Li; Bo‐Ping Tang; Qiu‐Ning Liu (Reviews in Aquaculture, 2026)
Integrated rice–crab co‐culture represents a sustainable agroecosystem, yet a critical conflict arises: pesticide applications necessary for rice cultivation undermine the health of the co‐cultured Chinese mitten crab ( Eriocheir sinensis ) and jeopardize system sustainability. To address this challenge, a comprehensive analytical framework is developed, linking multipathway pesticide exposure, molecular toxicity mechanisms, cross‐scale risk assessment, and resilience‐oriented governance. This framework systematically reviews the environmental fate and exposure dynamics of pesticides in paddy fields, as well as their toxicokinetics and tissue‐specific bioaccumulation in E. sinensis . Moving beyond descriptive toxicology, the study integrates “effect hierarchy” and “mechanistic network” perspectives to unravel cascading toxicity pathways, spanning oxidative stress, neuroendocrine disruption, cellular pyroptosis, and immune suppression. The limitations of conventional risk assessment in such a complex system are critically examined, with emphasis on the dual risks to crab population resilience and human food safety. To mitigate these challenges, a novel, mechanism‐informed “Prevent–Intercept–Protect–Adapt (PIPA)” framework is proposed to bolster system resilience, combining green pest control, eco‐engineering, host health enhancement, and smart monitoring. This review enhances theoretical understanding of contaminant impacts in multitrophic systems and offers actionable management strategies to promote the sustainable development of integrated aquaculture.

Bioactive prenylated acylphloroglucinols from Hypericum scabrum - Li-Ping Teng; Jie-Lian Huang; Shui-Qing Guan; Chen-Xi Xin; Zi-Yin Mai; Yik-Ling Chew; Zhong-Bo Zhou; Gencheng Liang (Natural Product Research, 2026)

Minutes-long soft X-ray prompt emission from a compact object merger - An Li; Chen-Wei Wang; Niccolò Passaleva; Jie An; Bin-Bin Zhang; Eleonora Troja; Yi-Han Iris Yin; Yuan Liu; Shao-Lin Xiong; Li-Ping Xin; Yi-Xuan Shao; Jun Yang; et al. (Science Bulletin, 2026)

Fungal community succession drives the decay of jujube fruit (Ziziphus jujuba Mill. cv. Jingcang 1) during ambient storage - Jian-Yu Wang; Ke-Xin Jiao; Min-Xin Mao; Cheng-Gang Li; Jian-Ping Qu; Bo Zhou; Qian Zhang; Qing Hao (Postharvest Biology and Technology, 2026)

Deterministic processes result in clustered functional and phylogenetic river insect biodiversity along urbanization gradients in a (sub)tropical megacity - Zhenyuan Liu; Tingting Zhou; Weimin Wang; Bo-Ping Han; Zhicai Xie; Janne Soininen (Landscape and Urban Planning, 2026)

Zeolite-assisted Ga0.8V0.2Ox oxygen carriers boost propane dehydrogenation via chemical looping - Bo Chen; Yuhao Wang; Ping Jin; Hua Wang; Kongzhai Li; Aimin Zhang; Yane Zheng (Fuel, 2026)

Retraction notice to “Metastable conformational regulation in heat-induced gluten aggregation: multiscale experiments and molecular dynamics reveal distinct roles of HMW-GS at the Glu-B1 locus” [Food Hydrocolloids 179 (2026) 112791] - Bo Wang; Ping-ping Zhang; Rong-ran Zhang; Tian Lv; Yue Zhang; Pei Wang; Qin Zhou; Dong Jiang; Xin-long Dai; Hao Jiang; Tao Yang (Food Hydrocolloids, 2026)

A biocompatible catalytic benzyl decaging enables activation of salicylic acid-dependent defense responses in plants - Yanhao Hu; Bo He; Mian Wei; Zhengxi Xiong; Yalin Mu; Ping Chen; Wang Chen; Jiahao Wang; Wei Yan; Yonghao Ye (Chemical Engineering Journal, 2026)

MXene-enhanced self-healing nanocomposite hydrogels with multiple-dynamic-bond crosslinking for motion sensing and information transmission - Ze-Hua Hou; Huan-Jie Che; Zi-Han Jiang; Xing Wu; Jin-Ping Yuan; Jing Li; Jian-Bo Qu (Chemical Engineering Journal, 2026)

A clinically practical aging clock (physical clock) for healthy aging: development, validation, and application for health assessment and intervention - Xiao-Ming Wang; Jing Pang; Xue Yu; Xuewei Zhang; Shi-Bo Wang; Qi Pan; Aiqun Chen; Lengnan Xu; Nan Li; Xuefei Li; Yao Wang; Yujia Gu; et al. (Science China Life Sciences, 2026)

lncRNA MIR4435-2HG modulates the malignant progression of glioblastoma through the miR-181d-5p/MALT1/NF-κB signaling pathway - Pei-sheng Chen; Liu-fei Xu; Bo Wang; Sheng-ping Zhang; Yi-yu Luo; Xiang-peng Wang (Journal of Molecular Histology, 2026)

Direct quantification of thallium(I) in water by ESI-MS via supramolecular recognition with cryptand[2.2.2] - Hai Li; Ping Guo; Min Li; Ming Ma; Wei Luo; Bo Chen (Analytica Chimica Acta, 2026)

ERBB2 as a Prognostic Biomarker in Prostate Cancer: Integration of Single-Cell Transcriptomics, Deep Learning, and Immunohistochemical Validation - Chen Wang; Li-Jing Zhu; Wei-Bo Mao; Ting Chen; Teng-Fei Gu; Sheng-Ping Hu; Yong-Tao Pan; Guo-Lin Yan; Yun-Peng Dong; Jie Li (Biochemical Genetics, 2026)

Phylogeography of ‘tropical Daphnia ’ — Diaphanosoma dubium : Refugia, Lineage Divergence, and Historical Colonization Over a Warm and Complex Landscape in East Asia - Ping Liu; Meng Xu; Qi Huang; Henri J. Dumont; Diego Fontaneto; Bo‐Ping Han (Journal of Biogeography, 2026)
Aim East Asia spans temperate to tropical zones, with limited glacial influence and a complex geological history shaped by the Tibetan Plateau. Consequently, species here may show distinct phylogeographic patterns compared with those of Europe and North America. Using the warm‐adapted cladoceran Diaphanosoma dubium as a model, we tested whether it persisted in multiple watershed refugia, especially the Yangtze River Basin, during past climate oscillations, leading to geographically structured lineage divergence. Location East Asia, with a specific focus on watersheds across China. Taxon The cyclically parthenogenetic cladoceran Diaphanosoma dubium (‘tropical Daphnia ’). Methods We applied ecological niche modelling on a global occurrence dataset and population genetics analyses on mitochondrial and nuclear gene datasets from 60 populations. Results High‐fitness areas were identified mainly in the eastern Yellow River Basin plains during the Last Glacial Maximum (LGM). Phylogenetic analysis resolved five deep lineages coalescing in the Late Miocene. Ancestral cold‐adapted lineages dominated the Yellow River Basin in the Late Miocene, later dispersing and permeating southward into the Yangtze River Basin during pre‐Pleistocene cooling. Three deep lineages indicated a large refugium downstream of the Yellow River Basin and west of the Bohai Gulf, and two lineages indicated two cryptic southern refugia. The two most common lineages overlapped widely in China, expanding post‐LGM from the Paleo‐Bohai refugium, showing climate tracking and niche conservatism. Main Conclusion In contrast to our expectation, the Yangtze River Basin acted as a dispersal hub rather than a refugium in middle China. D. dubium exhibited a watershed‐associated latitudinal structure, distinct from Daphnia in Europe. Historical north‐to‐south colonization and strong gene flow mitigated genetic differentiation among watersheds. Life‐history traits drove D. dubium 's successful colonization of tropical China, with geographic range and mountainous landscapes further shaping its continental‐scale distribution and divergence.

A polar strapdown airborne gravimetry method based on the transverse coordinate system - Chao-bo Yu; Shao-kun Cai; Mei-ping Wu; Zhi-ming Xiong; Rui-hang Yu; Bai-nan Yang (Applied Geophysics, 2026)

Effects of GIAHS conservation on agricultural landscape and ecological sustainability in heritage sites: evidence from the Yuanyang Hani Rice Terraces - Jin-Rong Zhang; Hong-Bo Li; He-Ping Yang; Meng-Na Qi (Environment, Development and Sustainability, 2026)

Transcriptomic analysis of lncRNA-miRNA-mRNA competing endogenous RNA regulatory networks in radiation-induced mouse thymic degeneration - Fei Wang; Qing-hua Yu; Xin-ming Fan; Cun-yang Guo; Si-guang Xu; Wen-bo Zhang; Ping Xu (Immunologic Research, 2026)

Two new chroman derivatives from the desert plant endophytic fungus Lasiodiplodia sp - Wen-Xiang Tao; Jin Ye; Lin-Ping Zhang; Le Zhang; Dong-Yang Liu; Xiu-Feng Yang; Tian-Cheng Ma; Yi Sun; Chang Zhang; Fan-Wei Liu; Ying Chen; Bo Song (Natural Product Research, 2026)

Two new monoterpene glycosides from the endophytic fungus Diaporthe nobilis and their cytotoxic effects - Ying Chen; Jian Wang; Cai-Lin Zhao; Xiu-Feng Yang; Jin Ye; Lin-Ping Zhang; Yun-Xiao Li; Fan-Wei Liu; Le Zhang; Bo Song (Natural Product Research, 2026)

A T-DINEOF model for multiple oceanic variables reconstruction - Bo Ping; Ruiting Yang; Yunshan Meng; Fenzhen Su; Cunjin Xue (Ocean Science, 2026)
Satellite-derived oceanic data are frequently affected by cloud cover, resulting in spatiotemporal gaps. The Multi-DINEOF method is widely used to reconstruct multiple oceanic variables. However, Multi-DINEOF essentially remains a matrix-based DINEOF approach and does not fully leverage the correlations among multiple variables. To address this limitation, this study proposes the T-DINEOF model, aiming to improve the accuracy of reconstructing multiple oceanic variables simultaneously. When applied to sea surface temperature (SST), sea surface chlorophyll a (SCHL), and sea surface wind (SSW) collectively, T-DINEOF reduces root mean square error (RMSE) by 12.9 %, mean absolute error (MAE) by 13.8 %, and mean absolute percentage error (MAPE) by 11.9 % compared to Multi-DINEOF. For each individual oceanic variable, T-DINEOF outperforms both Multi-DINEOF and the original DINEOF methods, reducing RMSE by 9.0 % and 14.7 %, MAE by 10.5 % and 14.6 %, and MAPE by 13.7 % and 13.4 % for SST; reducing RMSE by 9.3 % and 11.8 %, MAE by 9.9 % and 13.4 %, and MAPE by 8.3 % and 11.8 % for SCHL; and reducing RMSE by 16.6 % and 3.7 %, MAE by 16.8 % and 3.5 %, and MAPE by 16.4 % and 3.1 % for SSW. Additionally, T-DINEOF proves effective in regions with a high proportion of missing data and in cases of low data correlation.

Toward high-precision, low-consumption bulk analysis: advancements in extraterrestrial sample studies - Ding-Shuai Xue; Shun Guo; Yan-Hong Liu; Dan-Ping Zhang; Yong-Gang Yao; Bo Wan; Xian-Hua Li (Science Bulletin, 2026)

A 44-min periodic radio transient in a supernova remnant - Di Li; Mao Yuan; Lin Wu; Jingye Yan; Xuning Lv; Chaowei Tsai; Pei Wang; Jiaqi Zhao; Weiwei Zhu; Li Deng; Ailan Lan; Renxin Xu; et al. (Science Bulletin, 2026)

Tolypaxillines A–J: indole diterpenoids with neuroprotective activities from a soil-derived fungus Tolypocladium album DWS131 - Yu-Fen Tan; Xing-Yi Chen; Chao Wang; Ai-Lin Liang; Wen-Yu Lu; Le-Meng Feng; Qi Huang; Yue-Ping Jiang; Shao Liu; Xiao-Bo Xia; Jing Li; Wen-Xuan Wang (Phytochemistry, 2026)

Carbohydrate conversion and microbial community restructuring following Saccharomyces cerevisiae inoculation during Pu-erh tea fermentation - Ruoyu Li; Teng Wang; Qiuyue Chen; Yanhui Guan; Nianguo Bo; Qi Wang; Yiqing Guan; Dihan Yang; Ping Liang; Yan Ma; Tiejun Ling; Ming Zhao (International Journal of Food Microbiology, 2026)

NFIL3-dependent regulation of NF-κB pathway mediates alginic oligosaccharide alleviation of nitrite immunotoxicity in Procambarus clarkii - Xue Zhang; Shuang-Gui Dai; Xiang Lu; Bo-Ping Tang; Dan-Dan Bian; Qiu-Ning Liu (Fish & Shellfish Immunology, 2026)

Erratum to “Efficient anaerobic metformin biodegradation driven by a cross-feeding consortium: novel pathways, enzymes, and toxicity dynamics” [Bioresource Technology 450 (2026) 134473] - Xin Wang; Bo-Jun Liang; Dan-Ni Wu; Xue-Ming Zhang; He-Ping Zhao; Chun-Yu Lai (Bioresource Technology, 2026)

Building undergraduate STEM identity, confidence and skills through prosocial research: the community air research experience - Tania M. Schusler; Ping Jing; Dikshya Dahal; Julie Maertens; Ixchel Barraza Zapata; Bo Zhang; Olivia Sablan; Ilana Pollack; Nora Hartnett; Olga Bautista; Emily Fischer (Journal of Environmental Studies and Sciences, 2026)

Magnetically recoverable N-doped graphene/ZnFe-LDO composite for synergistic adsorption-photocatalytic removal of tetracycline in water - Le You; Tianqi Wang; Boya Zeng; Wu Zhang; Yuqing Huang; Zhanli Chen; Ping Zhang; Yujie Li; Bo Zeng (Applied Clay Science, 2026)

Continental Jurassic/Cretaceous transition in Northeast China: Stratigraphic and spatiotemporal constraints from the Hailar Basin and adjacent areas - Chong-Yang Chen; Li-Ping Yao; Pu-Jun Wang; Hai-Bo Wu; Jing-Sheng Li; Yan-Ping Hou; Yun-Fei Xue; Shu-Qin Zhang (Cretaceous Research, 2026)

Molecular characterization of a novel partitivirus isolated from Fusarium solani, the causal agent of tobacco root rot - Xiao Wu; Ying Wang; Rui Guo; Ya Rong Wang; Si Jun Li; Xiang Ping Zhou; Jie Zhong; Yan Song Xiao; Tian Bo Liu (Archives of Virology, 2026)

Nitrogen-Doped Carbon Quantum Dots for FRET-Assisted and Smartphone-Enabled Fluorescent Detection of Melatonin in Biological Samples - Priyanka K. M.; Himanshu Kumar; Hsin-Chieh Kung; Ya-Ping Chung; Anshu Kumar; Vishal Kumar; Bo-Wun Huang; Balasubramanian Sriram; Sea-Fue Wang; Chih-Lung Wang; Yung-Lung Chen; Amanpreet Kaur; et al. (Journal of Fluorescence, 2026)

Precision measurement of the Ds*+-Ds+ meson mass difference - M. Ablikim; M.N. Achasov; P. Adlarson; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; Y. Ban; H.-R. Bao; V. Batozskaya; et al. (Science Bulletin, 2026)

Pesticide toxicity in Procambarus clarkii: Integrating oxidative stress, immune dysfunction, and gut microbiota disruption - Dan-Dan Bian; Zi-Yi Xing; Xiang Lu; Shuang-Gui Dai; Qiu-Ning Liu; Bo-Ping Tang; Zhi-Gang Wang (Pesticide Biochemistry and Physiology, 2026)

Mechanically engineered multi-oxide heterojunctions for bifunctional antibacterial and photocatalytic environmental remediation - Juan Pei; Jialan Mi; Shuhan Yao; Mingxing Guo; Ye Zhang; Xiaoling Wan; Wei Wu; Ying Hong; Pei Hu; Ping Chen; Lin Chen; Haichun Zeng; et al. (Journal of Environmental Chemical Engineering, 2026)

Zircon U-Pb dating and geochemistry of the Paleoproterozoic tuffs from the Nsama formation in northeastern Zambia - Jun-ping Ren; A-lei Gu; Hong-wei Sun; Li-bo Zuo; Jie Wang; Bao-jin Zhao; Evaristo Kasumba; Shi Xing; Zi-jiang Liu; Jin-meng Dong; Jin-rui Zhang; Ji-hai Chen (Journal of African Earth Sciences, 2026)

Cryoprotective effect of natural deep eutectic solvent combined with sous-vide cooking treatment on the pre-maturation and freeze-thaw cycle of Penaeus vannamei - Jing-jing Fu; Jie Deng; Bo-yang Tan; Yi-shu Ni; Xiu-ping Dong; Si-min Zhang; Yue-wen Chen (Food Chemistry, 2026)

Dual valorization of waste silk sericin: pH-controlled synthesis of luminescent carbon dots for tough, adhesive, and photodynamic antibacterial hydrogels - Zhiteng Zhai; Leilei Wu; Yun Yuan; Yanlong Bu; Ying Liu; Bo Xu; Ping Wang (Chemical Engineering Journal, 2026)

Efficient anaerobic metformin biodegradation driven by a Cross-Feeding Consortium: Novel Pathways, Enzymes, and toxicity dynamics - Xin Wang; Bo-Jun Liang; Dan-Ni Wu; Xue-Ming Zhang; He-Ping Zhao; Chun-Yu Lai (Bioresource Technology, 2026)

Genomic characterization of two novel viruses co-infecting the fungus Conidiobolus macrozygosporus isolate RCEF7522 - Ping Wang; Ying Yin; Guogen Yang; Shengli Zhang; Bo Huang (Archives of Virology, 2026)

STIM2 suppressed Anti-tumor immunity in cholangiocarcinoma - Li-Ping Ying; Zong-Yang Wu; Jin-Bo Wang; Ji-Ye Feng; Kai Lu (Advances in Traditional Medicine, 2026)

Rapid evaluation of the comprehensive quality of paeonol/cyclodextrin supramolecular complexes using CASSA based on near-infrared spectroscopy combined with artificial intelligence - Bo-yao Zhang; Xin-li Li; Cheng Qian; Si-min Xue; Zhi-tong Zhang; Si-yi Liu; Guo Zhang; Guo-ping Peng; Ning Ding; Yun-feng Zheng (Molecular Diversity, 2026)

Cuticular evidence and taxonomic reassessment of Miocene Albizia fossils in southwest China: Implications for the biogeography of A. julibrissin - Ping Lu; Jin-Bo Gao; De-Liang Li; Xiao-Qing Liang (Review of Palaeobotany and Palynology, 2026)

Inhibiting Cr(VI)-mediated ARG dissemination in wastewater: Synthetic antioxidant-, extracellular polymeric substance-, and nuclease-producing microbiome targeting ROS, MGEs, and ARG-MRG co-occurrence - Bo Deng; Zi-He Ren; Chong-Yang Ren; He-Ping Zhao (Journal of Hazardous Materials, 2026)

Bioremediation of high concentrations of mercury and nickel in activated sludge by black soldier fly larvae: Accumulation, transformation, and sustainability assessment - Bo Deng; Chong-Yang Ren; Zi-He Ren; Zhi-Jian Zhang; Qiang Li; Qiao-Xia Yuan; He-Ping Zhao (Journal of Hazardous Materials, 2026)

Millimeter-scale zeolite monoliths via one-step hydrothermal synthesis for enhancing dimethyl ether carbonylation - Feng Chen; Pan Deng; Jing-Ping Zhao; Zhi-Yang Ren; Tianlong Liu; Xiao-Bo Feng; Jing-Pei Cao (Fuel, 2026)

Synergistic inhibition of advanced glycation end products and enhancement of flavor by the combination of oligomeric proanthocyanidins and glycated yeast proteins - Jing-jing Fu; Bo-wen Ru; Qi-cheng Zhang; Yu-jun Wu; Hai-yang Feng; Lian-ping Zheng; Yue-wen Chen (Food Research International, 2026)

Enhanced rhamnolipid production in Pseudomonas putida through systematic medium optimization and metabolic engineering - Ai-Ping Pang; Teng Zhang; Kun Yang; Xia Wang; Lianggang Huang; Bo Zhang; Zhi-Qiang Liu; Yu-Guo Zheng (Bioresource Technology, 2026)

Development of a Ternary Heterojunction Photocatalyst for Efficient Antibiotic Degradation - Bo Wang; Yang Sun; Lina Jiang; Peng Zhou; Ping Guo; Xu Wang (Water, Air, & Soil Pollution, 2026)

Isolation of Rhizospheric Fungi from Crocus sativus L. Rhizosphere and their Effects on Host-Growth Promotion - Jing-Chao Xu; Xing-Guang Xie; Xin-Zhu Yu; Zi-hao Zhu; Xue-Wen Bi; Kun-miao Feng; Ying-jie Lu; Khalid Rahman; Bo Zhu; Lu-ping Qin; Zhen-zhen Zhang; Ting Han (Current Microbiology, 2026)

The Potential Drug Target (Glycolysis Pathway) of the Spore Stage of the Pathogen Enterocytozoon hepatopenaei in Shrimp Farming - Bo Zhu; Juan Feng; Dong Qian; Ping Zhuang; Changkao Mu; Jiong Chen; Rongrong Ma (Fishes, 2026)
Enterocytozoon hepatopenaei (EHP) is a specialized parasitic microsporidian that causes significant economic losses to the shrimp farming industry. The glycolysis pathway plays an important role in the survival of EHP spores in vitro. In this study, key enzyme genes involved in the glycolysis pathway of EHP were analyzed, and purified spores were treated with KOH and a low temperature (−20 °C) to promote or inhibit germination. Quantitative analysis and enzyme activity of the initiating key gene hexokinase (HK) and the core link gene glyceraldehyde 3-phosphate dehydrogenase (GAPDH) were conducted to explore the energy response characteristics of germinating spores. The results showed that HK and GAPDH genes had significant differences from the host, based on phylogenetic analysis. The expression of HK gene and enzyme activity increased after promoting germination treatment. The expression of the GAPDH gene was stable, but the activity of the GAPDH enzyme increased significantly after germination promotion. These findings indicate that the inhibition of the HK gene expression level and GAPDH protein level can block spore germination and invasion in vitro, which could be used as potential control targets for EHP.

Synergistic anticoccidial effects of pomegranate peel extract and probiotics against Eimeria tenella via mitigating inflammation and restoring gut microbiota - Weimei Wang; Xiaobin Yi; Yu Han; Ping Feng; Ruonan Bo; Mingjiang Liu; Jingui Li (Veterinary Parasitology, 2026)

Eocene topography differentiation between the western and eastern North China Craton: Insights from multi-method chronometry in the northern Taihangshan Mountains - Li-Xia Feng; Ping-Ping Li; Zeng-Zhen Wang; Rong Ren; Lin Wu; Bo Zheng; Bo Liu; Jian-Qing Ji; Bao-Fu Han (Tectonophysics, 2026)

Chrysovirus BbCV1 confers enhanced sporulation and environmental fitness to Beauveria bassiana - Lili He; Guogen Yang; Ping Wang; Yang Yang; Jiaojiao Qu; Bo Huang (Pesticide Biochemistry and Physiology, 2026)

Distribution, fate, and risk prioritization of antibiotics in wastewater treatment plants in Northwest China: Insights into secondary sedimentation limitations and membrane process advantages - Yixi Zhang; Mengcheng Wu; Yunzhou Tan; Bo Du; Mengjiao Li; Liangliang Liu; Ping Wu; Guodong Kang; Shenghu Zhang; Zhengxiang Shi; Leilei Lu (Journal of Water Process Engineering, 2026)

Comparative effectiveness and mechanisms of different cement types in solidifying/stabilizing copper ions - Chuang Yu; Bing-sheng Huang; Xiaoqing Cai; Ya-bo Wang; Changpeng Ye; Rao-ping Liao (Journal of Environmental Management, 2026)

Latent-driven structural generation and performance-constrained optimization for expansion tube energy absorbers - Bo Wang; Xin Zheng; Jiaxing He; Guangxiang Hao; Ping Xu (Engineering Structures, 2026)

Calcium-mediated modulation of ultra-low-ester pectin-gluten interactions: subunit-level mechanisms revealed using HMW-GS deletion lines and molecular dynamics simulations - Rong-ran Zhang; Ping-ping Zhang; Tian Lv; Bo Wang; Zhe Liu; Yue Zhang; Chuan Zhong; Pei Wang; Qin Zhou; Dong Jiang; Hao Jiang; Tao Yang (Carbohydrate Polymers, 2026)

Histomorphological analysis of the relationship between Helicobacter pylori infection of the gastric mucosa and host immunity strength - Yang-kun Wang; Quan-wei Guo; Hai-ying He; Ying-ying Li; Chao-ya Zhu; Ping Li; Bo Jiang; Su-nan Wang; Si-liang Xu (Journal of Molecular Histology, 2026)

DrPISA: Deep eutectic solvent-assisted reverse proteome-integrated solubility alteration for high-sensitivity drug target identification - Liu Yang; Tian-Bo Ma; Chen-Wan Guo; Run-Bo Yu; Ping Li; Hua Yang; Wen Gao (Analytica Chimica Acta, 2026)

Paleoproterozoic granite chronology, geochemical characterization, and geological significance in the Longdu region of northeastern Zambia - Yu-Xuan Wu; A-Lei Gu; Jun-Ping Ren; Ling-An Bai; Li-Bo Zuo; Hong-Wei Sun; Shi Xing; Zi-Jiang Liu (International Geology Review, 2026)

Dose–dependent effect of Bacillus subtilis on aquaculture pond ecosystems - Weiming Liu; Xiaolong Bo; Yanhao Cao; Jianchun Xiao; Run Zhang; Hongli Liu; Defang Chen; Yi Geng; Ping Ouyang; Xiaoli Huang (World Journal of Microbiology and Biotechnology, 2026)

Raccoon dog parvovirus NS1 protein antagonizes type I interferon signaling by promoting selective autophagic degradation of IRF3 - Wen-yu Cao; Rui-qi Wang; Jin-yang Zheng; Ping Ma; Bo Hu; Cheng-qi Zhang; Ya-jie Sun; Jia-jia Liu; Ding-rui Guo; Zi-han Zhao; Xin Cao; Xue Bai; et al. (Veterinary Microbiology, 2026)

Experimental investigation of hydrogen self-ignition and explosion in confined enclosures: Influence of axial obstruction and ventilation - Ping Li; Yihui Jiang; Di Wu; Jian Guo; Jinwei Xu; Yiwen Xu; Bo Ke; Songlin Zhang; Qiangling Duan (Process Safety and Environmental Protection, 2026)

Isolation and identification of spoilage bacteria from kiwifruit and analysis of the antagonistic activity of three Bacillus strains against these bacteria - Ang Liu; Wen-xin Li; Yi Liu; Xing-lin Ran; Bo-yu Dong; Qiu-ping Yao; De-quan Zhu (Food Control, 2026)

Metagenomics reveals potential antimicrobial peptides in Chinese baijiu fermentation - Rubing Du; Xue Li; Yan Xu; Kexin Jing; Ling Ao; Bo Deng; Qing Xu; Ping Song; Jing Yu (Food Microbiology, 2026)

High-value utilization of hazardous solid waste for efficient electrocatalytic oxygen reduction to produce hydrogen peroxide - Bo Liu; Xiaoshuang Song; Guoxin Mu; Jiayu Feng; Fang Wang; Rui Cao; Zibin Pan; Feixiang Lu; Ping Ning; Shuo Cui; Lijuan Jia (Environmental Research, 2026)

The Classification History of Lamiaceae and a Generic Synopsis in China - Si-Cheng Xu; Su Liu; Ya-Ping Chen; Yue Zhao; Fei Zhao; Chun-Lei Xiang; Bo Li (The Botanical Review, 2026)

Transgenerational Effects of Elevated Temperature on Life History and Lambda-Cyhalothrin Sensitivity in Cydia Pomonella - Kang-Wu Zheng; Zi-Han Wei; Zi-Nan Xia; Bo-Kun Wang; Ping Gao; Yu-Ting Li; Xue-Qing Yang (Neotropical Entomology, 2026)

Breaking the antimicrobial resistance dilemma: marine natural products, a treasure trove for the development of new anti-Staphylococcus aureus drugs - Peng-Jie Li; Liu-Xia Lv; Xi-Zhen Cao; Jian-Yu Liu; Ji-Xiu Gao; Hao-Ran Li; Gulab Said; Dan Chen; Bo Yao; Xin Liu; Mei-Yan Wei; Xiao-Ping Yang; et al. (Marine Life Science & Technology, 2026)
Antimicrobial resistance (AMR) affects multiple fields, including medicine, pharmacy, food safety, and animal husbandry, and poses a major threat to public health and economic development. Staphylococcus aureus has emerged as one of the most critical bacterial pathogens due to its widespread prevalence and significant genetic plasticity. This review outlines currently approved small-molecule drugs for clinical use and their mechanisms in controlling bacterial infections and antimicrobial resistance, highlighting the development of novel agents as an effective strategy to combat AMR. Special emphasis is placed on the antibacterial activity of marine-derived natural products (MNPs) against S. aureus , and a systematic analysis is presented for the first time on the structures, origins, activities, and structure–activity relationships of 1,192 compounds reported in 468 publications from 1977 to 2025. Among these, 36 MNPs exhibited significant activity against both methicillin-sensitive S. aureus and methicillin-resistant S. aureus (MIC ≤ 1 µg/mL). Macrolides and peptides represented the most prevalent structural classes, with compounds displaying potent activity accounting for 24% and 27% of the total active compounds, respectively. Further drug-likeness analysis shows that MNPs have promising therapeutic potential. Among the 160 highly active MNPs, over 80% have suitable lipid-water partition coefficients, and 41% fully meet Lipinski's Rule of Five. Structural analysis reveals tetrahydrofuran, tetrahydropyran, and sugar units as the most common motifs, present in 20, 16, and 14 compounds, respectively. Technologies and strategies to accelerate the development of marine-derived antibacterial drugs are also proposed. This will serve stakeholders across diverse sectors by supporting cross-sectoral coordination to address AMR.

Palynological succession in Gzhelian No. 8 Thick Coal of the Taiyuan Formation, Ordos Basin, North China - Hui Zhang; Yun-He Shi; Peng-Shuai Jiao; Bo Pan; Feng Liu; Ming-Li Wan; Jing-Kun Zhang; Hui-Ping Peng (Palaeoworld, 2026)

Insights into the permeability and anti-pollution mechanism of FeCo/BC@PVDF ultrafiltration membrane in-situ coupled PMS purification fluorine-containing wastewater - Xiaolin Shi; Bo Xing; Guo Yang; Yi Wang; Pan Huang; Fuping Zhang; Qing Yang; Hangdao Qin; Ping Yang; Caiyi Jiang; Xingyong Liu (Journal of Environmental Chemical Engineering, 2026)

Metal and nonmetal active sites induced by dual-ligand engineering in Cu-MOF/GO composites for enhanced electrocatalytic metronidazole degradation - Ya-ping Guo; Yu-bo Li; Zhi Huang; Yan-ying Liu; Qian Zhang (Journal of Environmental Chemical Engineering, 2026)

Molecular insight into the structure and formation mechanism of fluid phase in the classical coking theory - Bo Gong; Jie-Ping Wang; Hao-Dong Liu; Rui Guo; Jin-Xiao Dou; Guang-Yue Li; Ying-Hua Liang (Fuel, 2026)

Mechanically robust, self-healing, and photo-responsive fluorescent smart polyolefins for information storage and encryption - Jin-Kui Liu; Tong Pang; Yanru Feng; Bo Zhang; Chen Zou; Mao-Ping Song; Jun-Fang Gong; Hui Jiang (Chemical Engineering Journal, 2026)

Advances in surfactant-enhanced hydrothermal carbonization of biomass: Theoretical basis, product characteristics, pollutant control, process parameters, and mechanistic insights - Chun-fei Zhou; Chun-huo Zhou; Hai-wei Jiang; Jin-ming Shi; Xin Yin; Xiao-ping Liu; Jiang-bo Xiong; Min Jiang; Hua-jun Huang (Bioresource Technology Reports, 2026)

Construction of a Three-Dimensional Calcific Aortic Valve Disease Model Using Human iPSC-Derived Valvular Interstitial Cells - Ruikang Guo; Zhen Qi; Ping Qiu; Dogukan Mizrak; Bo Yang (Stem Cell Reviews and Reports, 2026)
Calcific aortic valve disease (CAVD) is a progressive and life-threatening condition characterized by fibrocalcific remodeling of the valve leaflets. Valvular interstitial cells (VICs) are central mediators of calcific aortic valve disease (CAVD), as their osteogenic trans-differentiation drives pathological matrix remodeling and calcium deposition within the valve leaflets. Human-induced pluripotent stem cell-derived valvular interstitial cells (hiVICs) represent a promising patient-specific platform for disease modeling. While primary VICs (pVICs) readily undergo mineralization under osteogenic stimulation, hiVICs fail to calcify in conventional two-dimensional (2D) cultures. Our data suggests that the inability of hiVICs to calcify in 2D culture is related to FOXO1 (Forkhead box protein O1) activity, which suppresses the osteogenic transcriptional program by inhibiting RUNX2 (Runt-related transcription factor 2). To address this limitation, we then developed a three-dimensional tissue ring construct using hiVICs. When cultured in osteogenic medium, these constructs exhibited robust calcification, as confirmed by Alizarin Red and Von Kossa staining. FOXO1 was also identified as a mediator of calcification in the tissue ring constructs. Metformin treatment restored FOXO1 expression and inhibited calcification, while AS1842856, a selective FOXO1 inhibitor, exacerbated tissue construct mineralization and led to a near-complete tissue collapse. In summary, we establish a functional 3D hiVIC-based model of CAVD enabling mechanistic investigation and pharmacological screening and identify FOXO1 as a critical regulator of osteogenic transition. Graphical Abstract

Carbon dioxide as the primary greenhouse gas emission in hard clam (Meretrix taiwanica) aquaculture - Yin-Yu Chen; Wei-Sheng Zhang; Chien‑Wei Tu; Bo-Ying Chen; Wen-Ping Cheng; Zhen Hao Liao; Yi-Jung Chen; Meng-Chou Lee; Fan-Hua Nan; Han-Yang Yeh (Aquaculture International, 2026)

Enhancing oil-water separation via droplet coalescence regulated by particle self-rotation in swirling fields - Wei Zhao; Ao-song Wei; Shu Zhu; Tong Zhang; Peng-bo Fu; Jian-ping Li; Xue-jing Yang; Hua-lin Wang (Water Research, 2026)

Insights into pesticides-induced toxicity in the silkworm (Bombyx mori) from physiological responses to molecular mechanisms - Dan-Dan Bian; Shuang-Gui Dai; Bo-Ping Tang; Qiu-Ning Liu (Pesticide Biochemistry and Physiology, 2026)

A novel potential toxic target of PBDEs in cetaceans: Impaired wound healing demonstrated in Indo-Pacific finless porpoise fibroblasts - Yajing Sun; Chengzhang Li; Ying Zeng; Imran Rashid Rajput; Jiashen Tian; Yuqi Wu; Juntao Ye; Ziyan Wang; Qinghong Liao; Jiezhang Mo; Zonghang Zhang; Jianqing Lin; et al. (Journal of Hazardous Materials, 2026)

Energy absorption performance of pomelo-inspired thin-walled tubes for sustainable lightweight design - Xin Zheng; Bo Wang; Ping Xu; Jiaxing He; Shuguang Yao (Journal of Cleaner Production, 2026)

Effects of neutral and alkaline salt stress on seed germination, physiological and biochemical properties of Andrographis paniculata (Burm.f.) Wall. ex Nees - Ming Zhang; Kai-xuan Shi; Jia Jiang; Qiao-chu Ma; Wan-bo Ding; Qing-ni Peng; Ya-ping Shi; Mei-long Liu; Zhi Sun; Ming Li; Sheng Wang (Journal of Applied Research on Medicinal and Aromatic Plants, 2026)

Enrichment and cultivation of thermophilic Bathyarchaeia from oil reservoirs via systematic cultivation profiling - Qing-Ping He; Yi-Fan Liu; Bo-Wen Wang; Lei Zhou; Shi-Zhong Yang; Ji-Dong Gu; Bo-Zhong Mu (International Biodeterioration & Biodegradation, 2026)

Mechanistic insight into curcumin-induced conjugative plasmid transfer acceleration: Role of intracellular arginine uptake - Min-ge Wang; Kai-di Liu; Wen-jie Jin; Run-bo Li; Jun-qi Liu; Liang-xing Fang; Jian Sun; Xiao-ping Liao (Food Microbiology, 2026)

An advanced DEM-PBM coupling with a coarse-grained model for particle coalescence and breakup in wet granulation - Dongling Wu; Bo Liu; Zhuo Chen; Ping Zhou; Liu Liu; Zhenyu Zhu (Chemical Engineering Journal, 2026)

Chemical constituents from Helvella leucopus and their chemotaxonomic significance - Zhao-Zhao Zhang; Yi-Yang Xie; Li-Ping Teng; Zhong-Bo Zhou (Biochemical Systematics and Ecology, 2026)

Breaking the Alzheimer’s Treatment Stalemate: Synergistic Application Strategies of Nanomaterials and Pharmaceutical Agents - Han Gao; Fangyuan Cheng; Zihan Zhang; Bo Yan; Pan Liao; Shishuang Zhang; Dai Li; Fanglian Chen; Ping Lei (Molecular Neurobiology, 2026)

Toxicological Insights Into Multiple Pesticide Exposures in Red Swamp Crayfish ( Procambarus clarkii ): Molecular Mechanisms, Risk Assessments, and Future Perspectives for Aquaculture - Dan‐Dan Bian; Zi‐Yi Xing; Shuang‐Gui Dai; Xiang Lu; Dai‐Zhen Zhang; Bo‐Ping Tang; Bao‐Jian Zhu; Qiu‐Ning Liu (Reviews in Aquaculture, 2026)
The rice–crayfish integrated system (RCIS) is vital to Asian aquaculture, yet its sustainability is threatened by a critical paradox: pesticides used in rice cultivation jeopardize the health of the red swamp crayfish ( Procambarus clarkii ) and the safety of its products. This review systematically synthesizes evidence establishing oxidative stress as the central hub linking pesticide exposure to multilevel toxicity in P. clarkii . We delineate how pesticides dysregulate key pathways (PI3K/AKT/mTOR, MAPK, NF‐κB), triggering apoptosis, metabolic disruption, and immunosuppression. A pivotal mechanism involves pesticide‐induced gut microbiota dysbiosis, which diminishes beneficial short‐chain fatty acids and enriches pathogens, thereby amplifying intestinal barrier damage and host vulnerability. These interconnected processes collectively stunt growth and heighten susceptibility to pathogens like white spot syndrome virus (WSSV). Beyond organismal effects, we evaluate environmental pesticide fate and propose a novel risk assessment framework integrating these sublethal endpoints. Our proposed mitigation strategies include eco‐friendly pesticides, ecological engineering, and microbiome‐directed interventions. We advocate for future research prioritizing multi‐omics and mixture toxicity assessment. By deciphering this toxicity cascade and translating insights into practice, this review aims to protect the productivity, ecological integrity, and food safety of integrated aquaculture systems for long‐term sustainability.

Synthetic peptide vaccines targeting SVA elicit robust protective immune responses in swine - Yamei Li; Nan Cao; Bo Yin; Mingfang Ji; Xiangzu Liu; Shudan Liu; Mingjin Jiao; Xiangmin Li; Ping Qian (Veterinary Microbiology, 2025)

Different detoxification strategies of fruit borers adaptation to quercetin - Bing Bai; Huan-Juan Zhao; Bo-Kun Wang; Yu-Ting Li; Ping Gao; Yun-Tong Lv; Xue-Qing Yang (Pesticide Biochemistry and Physiology, 2025)

Occurrence, partitioning, and fate of per- and polyfluoroalkyl substances (PFAS) in a full-scale AO–MBR–RO municipal WWTP - Aldeno Rachmad Ika; Shu-Fen Lin; Chih-Lung Wang; Guo-Ping Chang-Chien; Bo-Wun Huang (Journal of Water Process Engineering, 2025)

Identifying conservation gaps and proposing climate-smart strategies for amphibians and reptiles on the Qinghai-Tibet Plateau - Lu-Lu Sui; Zhong-Yi Yao; Shun Ma; Sheng-Chao Shi; Xiu-Dong Shi; Li-Wen Liang; Song Tan; Jie Wang; Bo Cai; Feng Xie; Jing-Feng Chen; Bin Wang; et al. (Journal of Environmental Management, 2025)

Valorization of steel slag through CO2 mineralization toward improved reactivity and cementitious performance - Bo Su; Yong Sun; Ping Jiang; Chao Zhang; Kai Cui; Yong Zheng; Jingping Qiu; Yingliang Zhao (Journal of Environmental Chemical Engineering, 2025)

Recovery of V2O5 from spent catalysts for NH3 and humidity sensors - Yan Li; Ping Hu; Miaomiao Liu; Bo Ran; Yuqing Zhu; Junxi Cheng; Jun Sun; Zhaofeng Wu (Journal of Environmental Chemical Engineering, 2025)

Palladium-catalyzed thermo, photo, and electrocatalytic CO₂ conversion to methanol and formaldehyde: A review of mechanistic pathways using synthetic, biogas, and fossil-derived CO2 - Yen-Yi Lee; Masimukku Srinivaas; I.-Cheng Li; Kapa Keharika; Rajender Boddula; Ramyakrishna Pothu; Sanna Gull; Bo-Wun Huang; Jein-Wen Chen; Prashanth W. Menezes; Guo-Ping Chang-Chien (Journal of Environmental Chemical Engineering, 2025)

The variation of the East Asian summer monsoon on multi-centennial scale during 8.3–2.9 ka BP - Chao-Jun Chen; Ya-Xi Dong; Yao Wu; Jian Zhang; Hai-Bo Wang; Yan-Xia Xue; Wen-Jun Sun; Man-Ping Xie; Hai Cheng; Jun-Yun Li; Ming-Qiang Liang; Ting-Yong Li (Global and Planetary Change, 2025)

Design of Ni-MOF@biochar heterostructures via ligand-induced distortion for highly selective N2H4 sensing - Bo Ran; Ping Hu; Jun Sun; Jialu Fang; Yan Li; Qihua Sun; Zhizhong Zhang; Zhaofeng Wu; Haiming Duan (Chemical Engineering Journal, 2025)

Ambient-dried polymer aerogel engineered via interparticle “stringing” towards ultrahigh robustness, flame retardancy and harsh-environment durability - Ting-Ting Li; Ting Wang; Chengxu Xu; Xue Gou; Xi-Ping Huang; Si-Yao Zhong; Zhi-Cheng Fu; Jinni Deng; Wenli An; Hai-Bo Zhao; Ming-Jun Chen (Chemical Engineering Journal, 2025)

Tailoring anchoring functionalities of self-assembled materials for efficient wide-bandgap perovskite solar cells - Zhong-En Shi; Yu-Fan Fu; Bo-Shun Peng; Ting-Chun Hung; Deebakkrishnan Ganesan; Rajendiran Balasaravanan; Shao-Huan Hong; Cheng-Liang Liu; Chun-Jen Su; Ming-Chou Chen; Chih-Ping Chen (Chemical Engineering Journal, 2025)

Advances in kidney biomarker electrochemical biosensors: From recognition chemistries to wearable, portable, and AI-enabled devices - Muthusankar Ganesan; Ramadhass Keerthika Devi; Jin-Shuen Chen; Bo-Wun Huang; Abinesh Sankar Pillai; Guo-Ping Chang-Chien (Chemical Engineering Journal, 2025)

Iron single-atom catalysts drive peroxymonosulfate activation for efficient degradation of extracellular antibiotic resistance genes through singlet oxygen-mediated DNA damage - Yunhong Zhang; Ping Yu; Xujing Guo; Lan Wang; Wenguo Wang; Liangwei Deng; Hongwei Zhang; Ting He; Zhaokun Xiong; Bo Lai (Chemical Engineering Journal, 2025)

Triterpenoid saponins from the seeds of Aralia elata (Miq.) Seem. and their chemotaxonomic significance - Wu-Di Zhai; Wen-Hao Zong; Bo-Yue Xiao; Chen-Yang Liu; Xiao-Ping Zhang; Yan Zhang (Biochemical Systematics and Ecology, 2025)

The cotton gene family encoding translationally controlled tumor proteins and the role of GhTCTP5 in salt tolerance - Bo Pang; Jialin Chen; Ping Luo; Ru Zhang; Jing Li; Weiwei Liang; Wenwei Gao; Shengmei Li (Plant Science, 2025)

Mechanistic insights into arginine-mediated gluten solubility enhancement and aggregation inhibition across specific subunit and molecular scales - Tao Yang; Tian Lv; Bo Wang; Yue Zhang; Pei Wang; Qin Zhou; Dong Jiang; Ping-ping Zhang; Hao Jiang (Food Hydrocolloids, 2025)

From disinfectant to neurodegeneration: Integrating machine learning and mendelian randomization reveals triclosan as a novel environmental risk factor for Alzheimer's disease - Fangyuan Cheng; Han Gao; Bo Yan; Fanglian Chen; Ping Lei (Environmental Pollution, 2025)

Mechanochemical synthesis of ZnO@TiO2 II heterojunction material: Photocatalytic degradation and antibacterial synergistic effect - Juan Pei; Xiaoling Wan; Mingxing Guo; Jialan Mi; Wei Wu; Ying Hong; Pei Hu; Ping Chen; Lin Chen; Siwei Xiang; Qianyu Zhang; Haichun Zeng; et al. (Chemical Engineering Journal, 2025)

Synthesis and antitumor evaluation of oleanolic acid acylhydrazone derivatives - Juan Cai; Bo-Wen Pan; Liang-Liang Zheng; You-Ping Tian; Zhang-Chao Dong; Li-Juan Liu; Ting-Ting Feng; Ying Zhou; Xiong-Wei Liu; Yang Shi (Molecular Diversity, 2025)

Sedimentary Stratigraphic Uncertainty: A Quantitative Analysis Framework Based on Information Theory and Stochastic Processes - Zhicheng Lei; Dezhi Yan; Bo Xu; Ping Lei; Songze Li; Yanli Wang (Mathematical Geosciences, 2025)

The Phylogeography of Selfing Caulokaempferia coenobialis Responded to Pleistocene Karst Development and Transgressions‐Regressions in Southern China - Guo‐Hui Lu; Hui‐Ping He; Yan Zhong; Bo Tan; Guang‐Bing Tan; Ying‐Qiang Wang (Journal of Biogeography, 2025)
Aim Southern China was not directly affected by large continuous ice sheets during the late Pliocene to the Quaternary period, thus playing a central role in shaping the biodiversity distribution patterns of species globally. While numerous phylogeographical studies have focused on three subkingdoms: the Qinghai‐Tibetan Plateau (QTP), the Sino‐Himalayan Forest and the Sino‐Japanese Forest, research on the formation of plant diversity in South China is limited. This study aims to investigate the drivers of plant diversification in southern China by elucidating the evolutionary history of the endemic selfing herb Caulokaempferia coenobialis . Location Southern China. Taxon Caulokaempferia coenobialis (Zingiberaceae). Methods We analysed the evolutionary history of C. coenobialis by sequencing 11 chloroplast regions and three nuclear genes from 145 individuals across 15 populations, as well as assembling 29 plastid genomes. Results C. coenobialis exhibits high genetic diversity at the species and regional levels, with low population genetic diversity and significant inter‐population differentiation. All populations diverged into two major lineages located in Southwest and South China approximately 2.75 Ma, after which the South China lineage diverged into two sublineages in Southern and Northern South China approximately 1.21 Ma. These two divergences coincided with the Karst development between Southwest and South China and the transgressions and regressions in South China during the Pleistocene. Main Conclusions The Pleistocene monsoonal climatic fluctuations, the tectonic activity of the southeastern boundary fault of the QTP, the resulting development of Karst landforms and the transgressions and regressions in South China shaped the phylogeographical pattern of C. coenobialis . The study offers new insights into the effect of Pleistocene climatic fluctuations and neotectonic movement on the genetic isolation and population differentiation of plant species in southern China. It also offers practical implications for achieving the ‘30 × 30’ target of the Kunming‐Montreal Biodiversity Framework.

Corrigendum to ‘Isolation of undescribed cladosporols and spirobisnaphthalenes from a plant pathogen Cladosporium cladosporioides F-10-2-A’ [Phytochemistry. 222 (2024) 114073] - Peng Li; Zi Jin Zhang; Yu Tong Guo; Jing Guan; Lin Bo Wen Xi; Li Ping Lin (Phytochemistry, 2025)

Polycyclic polyprenylated acylphloroglucinols with cytotoxicity against human tongue squamous carcinoma cells in vitro from Hypericum curvisepalum - Min-Min Cao; Xian Wei; Jie Huang; Zhong-Qiu Gan; Li-Ping Teng; Zhong-Bo Zhou (Phytochemistry Letters, 2025)

Super-high bed homogeneous sintering for iron ores with low carbon emissions - Liang-ping Xu; Di Wei; Hui-bo Liu; Guang-hui Li; Tao Jiang (Journal of Cleaner Production, 2025)

Z-scheme Cu2O/g-C3N4/Ag heterostructures: A novel approach for simultaneous water pollutant removal and real-time SERS monitoring - Kaiyue Li; Wenhui Li; Ping Huang; Yuquan Zhuo; Ziwen Yang; Bo Wang; Runru Liu; Bing Liu; Enzhu Hou; Shuo Yang; Donglai Han (Journal of Environmental Chemical Engineering, 2025)

Interfacial engineering of ZnSn(OH)6/SnO2 S-scheme heterojunctions for high-performance solar-light-driven photocatalytic nitric oxide oxidation - Hoang Phuong Nguyen; Shih-Wei Huang; Nguyen Minh Quang Ho; Minh-Thuan Pham; Minh-Ky Nguyen; Bo-Wun Huang; Le Thanh Nguyen Huynh; Sheng-Jie You; Chien-Er Huang; Guo-Ping Chang-Chien (Journal of Environmental Chemical Engineering, 2025)

Room-temperature trimethylamine gas sensor with enhanced performance using biomass-derived carbon quantum dot modified biochar - Mengyuan Liu; Bo Ran; Ping Hu; Jialu Fang; Jun Sun; Yuqing Bai; Qingshan Ma; Xiaoman Ma; Zhaofeng Wu; Haiming Duan (Journal of Environmental Chemical Engineering, 2025)

Exogenous arsenic-reducing bacteria enhanced arsenic phytoextraction via synergistic reprogramming of plant endophytic microbiome and metabolome - Yibo Liu; Baiyu Zhang; Ye Yao; Zhenxue Dai; Jie Liu; Bo Wang; Hongjie Gao; Ping Guo (Journal of Environmental Chemical Engineering, 2025)

Excellent durability and multifunctional textiles with dual-mode evaporative and radiative cooling enabled by in-situ growth of SiO2 and electrostatic network coating - Luxuan Zhang; Bo Xu; Man Zhou; Ying Liu; Ying Zhang; Li Cui; Ping Wang; Qiang Wang; Yuanyuan Yu (Chemical Engineering Journal, 2025)

The dielectric permittivity modulation effect of phase engineering on SiC whiskers modified reduced graphene oxide composites - Yun-Tian Chen; Bo Cai; Chen-Ming Liang; Shu-Hao Yang; Pei-Yan Zhao; Wen-Ping Li; Guang-Sheng Wang (Chemical Engineering Journal, 2025)

Adaptive filtering AHU: A novel approach for balancing the efficient filtering performance and energy conservation - Shibo Wang; Bo Xiang; Chaoyan Sun; Pengfei Si; Lijun Shi; Jikang Jia; Yingjun Guo; Ping Guo (Building and Environment, 2025)

Identification and complete genome sequences of two novel double-stranded RNA viruses infecting the basal fungus Conidiobolus lii - Shaoxiong Zhu; Ping Wang; Ming Yin; Ying Yin; Guogen Yang; Bo Huang (Archives of Virology, 2025)

Effect of primate protection on threatened and endemic vertebrates, plants, ecosystem services, and future climate refugia - Yin Yang; Chen Li; Yi‐Hao Fang; Guo‐Peng Ren; Zhi‐Pang Huang; Yan‐Peng Li; Liang‐Wei Cui; Meng‐Ran Chu‐yuan; Colin A. Chapmman; Cyril C. Grueter; Jian Zhou; Wen‐Bo Yan; et al. (Conservation Biology, 2025)
Primates, 69% of which are threatened with extinction, are the third most specious order of mammals. We used primates as model taxa to examine the umbrella effects of primates on ecosystem services and the protection of other vertebrates and seed plants in Yunnan Province, China. We identified areas of conservation priority for 16 primate species and determined which other threatened and endemic terrestrial vertebrates and seed plants would be protected through a program targeting primate conservation. Areas of high primate species richness were spatially correlated with the distribution of 601 species of threatened and endemic vertebrates and 4010 seed plants. Primate species richness was positively correlated with carbon sequestration and enhanced water and soil conservation and coincided with future areas of climate refugia. If 30% of Yunnan's land area were designated as primate conservation priority areas, then 52.3% of the province's average annual carbon sequestration, 51.7% of its water conservation, 54.1% of its soil retention, and 30‐33% of its climate‐stable areas would be protected. Protecting primates as umbrella taxa uniquely contributes to maintaining biodiversity and ecosystem services that promote ecosystem stability. Although we focused on a single mammalian order in a single region, our approach for umbrella taxa evaluation has broad applicability and can help achieve multiple conservation targets of the Kunming–Montreal Global Biodiversity Framework.

In situ addition of layered double hydroxides promotes sulfate-dependent anaerobic methane oxidation and microbial community shifts in freshwater-influenced mangroves sediments - Jijuan Ding; Fei Liu; Jing Huang; Ping Li; Junmao Zhang; Bo Wu; Longfei Shu; Zhili He; Cheng Wang (Water Research, 2025)

Enzymatic copolymerization opens new horizons for rhizoremediation and humification of estrogenic pollutants in water-soil-crop agroecosystems - Zeyu Shi; Wei Dai; Qian Yin; Youbin Si; Bo-Ping Xiong; Kai Sun (Process Safety and Environmental Protection, 2025)

Multifunctional au-DTNB-ag nanoparticles immunoprobes based on color-Raman properties for lateral flow immunoassay detection of Glycinin - Peng Bo Huang; Jing Long Qu; Shuo Yang; Tian Jiao Shui; Huan Huan Yang; Li Ping Cheng; Yang Qin; Jun Xi (Food Chemistry, 2025)

Opposite long-term trends in precipitation during spring and summer over the Pamir Plateau and influential factors - Ping Chen; Bo Sun; Huijun Wang; Junqiang Yao (Atmospheric Research, 2025)

Quorum-sensing Inhibitory Activity of Xanthones from Hypericum Curvisepalum N. Robson Against Chromobacterium Violaceum - Hong Zeng; Qiu-Ying He; Sheng-Qiang Yang; Xiao-Lian Wei; Jia-Zi Luo; Jing-Kai Zhou; Rong-Bing Fu; Li-Ping Teng; Zhong-Bo Zhou (Current Microbiology, 2025)

Nitrite Toxicity in Shrimp Aquaculture: Mechanisms, Health Impacts, and Sustainable Mitigation Strategies - Dan‐Dan Bian; Yan‐Xia Shi; Xue Zhang; Xin Liu; Jun‐Jie Jiang; Xi‐Rong Zhu; Dai‐Zhen Zhang; Qiu‐Ning Liu; Bao‐Jian Zhu; Bo‐Ping Tang (Reviews in Aquaculture, 2025)
The rapid expansion of intensive aquaculture systems has caused escalating environmental challenges due to excessive nitrogenous waste accumulation, which surpasses the metabolic capacity of aquatic microbiota and elevates nitrite concentrations. As a pervasive environmental toxin, nitrite induces oxidative stress, disrupts metabolic homeostasis, and compromises gut microbiota and immune function in shrimp, leading to mass mortality, economic losses, and ecological disruption. These impacts threaten both aquaculture productivity and ecological sustainability. This review synthesizes three decades of research to elucidate the multifactorial mechanisms of nitrite toxicity, including genotoxicity, apoptosis, growth impairment, and dysregulated cellular signaling pathways. Key findings highlight that nitrite overload impairs mitochondrial function, dysregulates apoptosis pathways, and interferes with growth and reproductive processes, thereby undermining shrimp development and reproduction. To address these challenges, the review evaluates emerging mitigation strategies such as antioxidant‐enriched feeds, probiotic modulation, and biofloc technology, which optimize nitrogen cycling, enhance detoxification capacity, restore microbial equilibrium, and improve survival rates in experimental trials. Unlike prior fragmented studies, this review integrates mechanistic insights into nitrite toxicity with scalable interventions, proposing a novel decision framework for system‐specific nitrite management. This framework offers actionable recommendations for policymakers and industry stakeholders to balance aquaculture productivity with ecological sustainability. By advancing the understanding of nitrite's ecotoxicological impacts, this review charts a path toward resilient and sustainable aquaculture systems, transforming mechanistic insights into preventive protocols and offering a holistic perspective on nitrite pollution control that reconciles economic objectives with ecological sustainability.

Chinese Tuina ameliorates muscle damage by regulating endoplasmic reticulum stress and autophagy in a rat model of skeletal muscle contusion - Hai-chao Liu; Hao-ming Zhu; Ming Li; Bo-rui Chen; Zheng-yu Yang; Yu Wang; Shi-zhong Wang; Shao-qing Chen; Jian-ping Lin (Tissue and Cell, 2025)

Isolation of pentasaccharide resin glycosides from the whole plants of Ipomoea biflora and their cytotoxic activities - Jin-Ping Gu; Tian-Zi Qi; Dong-Rong Zhu; Xu-Jia He; Su-Peng Guo; Xin Lan; Hong Gu; Jia-Lie Luo; Min Yang; Yu-Cheng Gu; Wen-Li Wang; Guang-Tong Chen; et al. (Phytochemistry, 2025)

Multi-target directed ligands design of 1-O-Acetylbritannilactone derivatives: Dual anti-neuroinflammatory and acetylcholinesterase inhibitory activities - Yan-Peng Liang; Qian Gao; Hong Chen; Rui Ma; Xiao-Bo Zhao; Xiao-Jie Jin; Jian Zhang; Yan-Ping Shi; Wei Ha (Phytochemistry Letters, 2025)

Construction of hydrophobic cavity surface of calix[4]arene for efficient extraction of endocrine disrupting chemicals in food - Jing-Yan Kang; Xiao-Bo Zhao; Jia-Qi Huang; Wei Ha; Yan-Ping Shi (Chemical Engineering Journal, 2025)

Evaluating the impact of weather variability on maize yield fluctuation for different sowing dates - Yuan-Chih Su; Ping-Wei Sun; Hung-Yu Dai; Bo-Jein Kuo (Agricultural and Forest Meteorology, 2025)

Deep reinforcement learning algorithm incorporating problem characteristics for dynamic multi-objective permutation flow-shop scheduling problem - Yuan-Yuan Yang; Bin Qian; Rong Hu; Zuocheng Li; Zi-Qi Zhang; Huai-Ping Jin; Jian-Bo Yang (Swarm and Evolutionary Computation, 2025)

In vivo and in vitro degradation and biological toxicity studies of polyesters with varying degradation rates - Ze-Yang Zhang; Wei-Zhen Zheng; Zhi-Chao Zhen; Xiao Li; Ping-Li Wang; Bo Lu; Xiu-bin Yang; Dan Huang; Jun-Hui Ji; Ge-Xia Wang (Journal of Hazardous Materials, 2025)

Avermectin induces photoreceptor functional impairment and color vision deficits in zebrafish (Danio rerio) - Wei-Guo Wang; Ming-Jun Yang; Zhu-Bo Sheng; Li-Ming Tao; Wen-Ping Xu; Yang Zhang (Journal of Hazardous Materials, 2025)

Study on the ground temperature response induced by GSHP system operation under different geological conditions - Shiyu Zhou; Hanbing Jia; Bo Zhou; Jiying Liu; Ping Cui; Mingzhi Yu (Geothermics, 2025)

Optimization of energy-absorbing parameters for train crash energy management using a variable-fidelity neural network surrogate model - Jiaxing He; Ping Xu; Jie Xing; Shuguang Yao; Bo Wang; Xin Zheng (Engineering Structures, 2025)

GWAS and GS analysis revealed the selection and prediction efficiency for yield, plant morphological, and fiber quality in Gossypium barbadense - Tao Yang; Honggang Wang; Jikun Song; Kang Zhao; Bo Pang; Yongpan Wang; Ping Luo; Weiwei Liang; Shunyu Shi; Jie Wang; Yifeng Lin; Jing Li; et al. (Theoretical and Applied Genetics, 2025)

Identification of Key Fatty Acid Metabolism-Related Genes in Alzheimer’s Disease - Bo Yan; Pan Liao; Wei Zhang; Zhaoli Han; Conglin Wang; Fanglian Chen; Ping Lei (Molecular Neurobiology, 2025)

Wildfire smoke and PM2.5 pollution in Chicago: Evidence from 2019 to 2023 - Nora Hartnett; Ping Jing; Bo Zhang; Matthew Stuart; Jun Wang (Urban Climate, 2025)

Great Oxidation Event was caused by Neoarchean global cratonization: opportunity and challenge from rock and sedimentary records in China - Li-Gang Zhou; Jun-Ping Liu; Jing Li; Zai-Bo Sun; Lu Xiang; Yan-Yan Zhou; Hao-Shu Tang; Yan-Bin Zhang; Xi-Yan Zhu; Hai-Long He; Ming-Guo Zhai (Science Bulletin, 2025)

Estimating basin-scale heterogeneous hydraulic diffusivity fields based on signal decomposition and river stage tomography - Bo-Tsen Wang; Yu-Li Wang; Chia-Hao Chang; Chin-Tsai Hsiao; Jordi Mahardika Puntu; Ping-Yu Chang; Jui-Pin Tsai (Journal of Hydrology, 2025)

Performance of ethanol transformable microemulsions and remediation of salinized oil – contaminated soils - Xiaoning Feng; Nan Shi; Shuhai Guo; Bo Wu; Gang Li; Bin Lou; Xiujie Yang; Yifan Wang; Ping Xiang; Xiahong He; Dong Liu (Journal of Hazardous Materials, 2025)

Co-transport of polyethylene microplastics and antibiotic resistance genes in soil: Influencing factors, mechanisms, and control strategies - Xiao-Ming Lu; Li-Bo Lu; Xi-Cheng Huang; Xue-Ping Liu (Journal of Environmental Chemical Engineering, 2025)

Pt driven Z-scheme carrier transfer in SnS2/g-C3N4 composites towards efficient photocatalytic H2O2 evolution - Peihao Song; Xiao Zhang; Bo Wang; Ping Yang (Journal of Environmental Chemical Engineering, 2025)

Selective interfacial polymerization improves reversibility of Si anodes - Wen Yang; Shuwei Li; You Liu; Yanyan Li; Ping Jiang; Xiaobo Hong; Gaofeng Li; Bo Fan; Fang Chen; Liangdong Lin; Zhijun Qiao; Dianbo Ruan (Chemical Engineering Journal, 2025)

Dual-window emissive radiative cooling textiles with a PTFE/SiO2 bilayer coating for enhanced thermal management - Luxuan Zhang; Qinting Zhu; Yuting Zhou; Bo Xu; Man Zhou; Ping Wang; Qiang Wang; Yuanyuan Yu (Chemical Engineering Journal, 2025)

Evolving Therapeutic Landscape of Intracerebral Hemorrhage: Emerging Cutting-Edge Advancements in Surgical Robots, Regenerative Medicine, and Neurorehabilitation Techniques - Danyang Chen; Zhixian Zhao; Shenglun Zhang; Shiling Chen; Xuan Wu; Jian Shi; Na Liu; Chao Pan; Yingxin Tang; Cai Meng; Xingwei Zhao; Bo Tao; et al. (Translational Stroke Research, 2025)
Intracerebral hemorrhage (ICH) is the most serious form of stroke and has limited available therapeutic options. As knowledge on ICH rapidly develops, cutting-edge techniques in the fields of surgical robots, regenerative medicine, and neurorehabilitation may revolutionize ICH treatment. However, these new advances still must be translated into clinical practice. In this review, we examined several emerging therapeutic strategies and their major challenges in managing ICH, with a particular focus on innovative therapies involving robot-assisted minimally invasive surgery, stem cell transplantation, in situ neuronal reprogramming, and brain-computer interfaces. Despite the limited expansion of the drug armamentarium for ICH over the past few decades, the judicious selection of more efficacious therapeutic modalities and the exploration of multimodal combination therapies represent opportunities to improve patient prognoses after ICH.

Inhibition of SIRT1/HSF1 pathway contributes to doxorubicin-induced nephrotoxicity in ovarian tumor-bearing mice - Mo Chen; Ying Zhao; Song Hu; Jun-bo Yuan; Kang-jie Xie; Shu-nv Cai; Xiao-yan Zhu; Jian-kui Du; Ping-bo Xu (Apoptosis, 2025)

Three-Dimensional Shallow P-wave Velocity Distribution in the Source Area of the 2021 MS6.0 Luxian Earthquake from Dense Array Seismic Imaging - Jian-xun Yang; Qi-yan Yang; Da-hu Li; Yong-ming Lu; Ping-ping Wu; Hui-li Guo; Ning-bo Jiang; Mi Gao; Heng Pan (Applied Geophysics, 2025)

Flame retardant contamination and ecological risk analysis in estuarine and marine sediments around an industrial port - Tuan Truong Minh Dang; Li-Man Li; Bo-Wun Huang; Chien-Er Huang; Chien-Hsing Wu; Nicholas Kiprotich Cheruiyot; Guo-Ping Chang-Chien (Marine Pollution Bulletin, 2025)

Mechanochemical treatment boosted microwave-assisted sulfonation of softwood lignin for the fabrication of dye dispersant - Xu Fu; Ling-Ping Xiao; Bo-Wen Meng; Wen-Jie Li; Run-Cang Sun (Chemical Engineering Journal, 2025)

Adventitious shoot regeneration from in vitro leaves of Eupatorium chinense L. - Can Cai; Lu Zhang; Ze-bo Liu; Qing-feng Zhang; Zhong-ping Yin; Ji-guang Chen (Plant Cell, Tissue and Organ Culture (PCTOC), 2025)

A combined retrieval and prediction convolution neural network for oceanic primary production - Bo Ping; Yunshan Meng; Fenzhen Su; Cunjin Xue (International Journal of Remote Sensing, 2025)

Preparation and epitope identification of a novel monoclonal antibody against 3A protein of Senecavirus A - Xiang-hui Ling; Biao Zhang; Hao-jie Ren; Ming-yang Li; Shun-da Liu; Meng-ru Luo; Ke-wei Guo; Shi-chong Han; Wen-rui He; Gai-ping Zhang; Yu-hang Zhang; Bo Wan (Veterinary Microbiology, 2025)

ABA-INSENSITIVE 4 promotes nicotine biosynthesis under high light in Nicotiana attenuata - Bo Lei; Yan Mao; Huina Zhao; Jing Yu; Bing Wang; Ping Li; Xiangyang Hu (Plant Science, 2025)

Restoring turbid eutrophic shallow lakes to a clear-water state by combined biomanipulation and chemical treatment: A 4-hectare in-situ experiment in subtropical China - Bo Li; Deyuan Chen; Jichong Lu; Suxia Liu; Jiale Wu; Lei Gan; Xiaoqin Yang; Xiaolin He; Hu He; Jinlei Yu; Ping Zhong; Yali Tang; et al. (Journal of Environmental Management, 2025)

Developing the sensing mechanism of high-performance N2H4 sensors derived from waste cotton stalk using a one-step process - Ping Hu; Jun Sun; Bo Ran; Jialin Li; Jialu Fang; Qihua Sun; Ning Tian; Zhaofeng Wu; Haiming Duan (Chemical Engineering Journal, 2025)

High-Voltage aqueous supercapacitors based on l-lysine pH Self-Buffering Coating-modified carbon cloth electrode - Ang Xu; Jie Gao; Huan Li; Xiyu Song; Bo Xu; Ying Liu; Yuanyuan Yu; Ping Wang; Qiang Wang; Man Zhou (Chemical Engineering Journal, 2025)

The Role of ICP Monitoring in Minimally Invasive Surgery for the Management of Intracerebral Hemorrhage - Ge Zhang; Yunjie Li; Danyang Chen; Zhuojin Wu; Chao Pan; Ping Zhang; Xingwei Zhao; Bo Tao; Han Ding; Cai Meng; Diansheng Chen; Wenjie Liu; et al. (Translational Stroke Research, 2025)
Intracerebral hemorrhage (ICH) is the second major stroke type, with high incidence, high disability rate, and high mortality. At present, there is no effective and reliable treatment for ICH. As a result, most patients have a poor prognosis. Minimally invasive surgery (MIS) is the fastest treatment method to remove hematoma, which is characterized by less trauma and easy operation. Some studies have confirmed the safety of MIS, but there are still no reports showing that it can significantly improve the functional outcome of ICH patients. Intracranial pressure (ICP) monitoring is considered to be an important part of successful treatment in traumatic brain diseases. By monitoring ICP in real time, keeping stable ICP could help patients with craniocerebral injury get a good prognosis. In the course of MIS treatment of ICH patients, keeping ICP stable may also promote patient recovery. In this review, we will take ICP monitoring as the starting point for an in-depth discussion.

Resveratrol Protects Müller Cells Against Ferroptosis in the Early Stage of Diabetic Retinopathy by Regulating the Nrf2/GPx4/PTGS2 Pathway - Yi Wang; Si-Yuan Song; Yi Song; Yuan Wang; Zheng-Wei Wan; Ping Sun; Xue-Mei Yu; Bo Deng; Kai-Hong Zeng (Molecular Neurobiology, 2025)

Effect of Particle Size, Sphericity, and Distribution on Seepage in Granular Porous Media - Bo-bo Xiong; Rui Kuang; Ping Zhang; Bin Tian; Hong-hu Gao; Qian Zheng; Yu-qin Li (Geotechnical and Geological Engineering, 2025)

Composition of breeding bird communities under different intensities of human activity: A case study in Jiulingshan Nature Reserve in eastern China - Bo Zhou; Gang Yang; Mingxiao Di; Ping Lu; Xiaodong Weng; Jiuheng Xu; Yong Tang; Yong Peng; Xinyu Tao (Acta Oecologica, 2025)

Tropical Niche Conservatism and Dispersal Limitation Jointly Determine Taxonomic and Phylogenetic β‐Diversities of Odonata in Eastern China - Zhenyuan Liu; Bo‐Ping Han; Janne Soininen (Global Ecology and Biogeography, 2025)
Aim Tropical niche conservatism (TNC) and dispersal limitation (DL) are major ecological and evolutionary mechanisms in shaping taxonomic and phylogenetic β‐diversities. While these mechanisms have been studied in plants and vertebrates, their roles in freshwater taxa remain unclear. We leveraged Odonata species distribution and phylogenetic data to map geographical patterns of taxonomic and phylogenetic β‐diversities, and to determine whether Odonata β‐diversity is primarily shaped by TNC or DL and whether temperature seasonality is a key driver determining TNC. Location Eastern China. Time Period Present. Major Taxa Studied Odonata. Methods A moving window containing nine grids of 50 × 50 km was employed to quantify taxonomic and phylogenetic β‐diversities, including their turnover and nestedness components. A null model was utilised to calculate randomly expected phylogenetic β‐diversity based on observed taxonomic β‐diversity and site‐specific regional species pools. The generalised dissimilarity model was used to assess the roles of climatic and geographic distances shaping β‐diversity and to identify the key climatic factors. Results Taxonomic total β‐diversity and its turnover component were generally higher than phylogenetic β‐diversity in most Odonata communities, with phylogenetic β‐diversity being relatively higher mainly in tropical regions. Current climatic factors independently explained slightly more of the variation in total β‐diversity than geographic distance alone, while geographic distance independently explained slightly greater proportions of deviance in turnover components. However, their joint effects accounted for an even larger part of the variation in β‐diversity. The key climatic predictors were temperature seasonality. Main Conclusions Current climatic factors, particularly temperature seasonality, largely shape taxonomic and phylogenetic β‐diversities of Odonata communities. Spatial turnover along the climatic gradient tends to involve phylogenetically related taxa, resulting in overall higher taxonomic than phylogenetic β‐diversity, supporting the TNC. The joint effects of climatic and geographic distances highlight the roles of climate, interacting with topographic complexity, shaping taxonomic and phylogenetic β‐diversities of Odonata in eastern China.

Measurement of the decay Ξ 0 → Λ γ with entangled Ξ 0 Ξ ¯ 0 pairs - M. Ablikim; M.N. Achasov; P. Adlarson; O. Afedulidis; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; I. Balossino; Y. Ban; et al. (Science Bulletin, 2025)

High-precision U-series dating of Panxian Dadong hominin site, Guizhou Province, southwestern China - Xiaochao Che; Fei Han; Xingsheng Zhang; Bo Cao; Ping Xiao; Guanjun Shen; Jianxin Zhao (Quaternary Science Reviews, 2025)

Identification of the Shuanglongtan tectonic mélange (ca. 1.7–1.5 Ga) in the southwestern Yangtze Block and it’s tectonic implications - Jun-Ping Liu; Zai-Bo Sun; Xiao-Hu He; Jiang-Tai Zhao; Shi-Jun He; Ling-Jing Bi; Wei-Ke Li (Precambrian Research, 2025)

2.08 Ga andesitic gneisses in the southwestern Yangtze Block: Unveiling new insights into its geological evolution - Jun-Ping Liu; Zai-Bo Sun; Wei-Ke Li; Hua-Li Luo; Shi-Jun He; Shao-Bin Hu; Jiang-Tai Zhao; Hai-bao Yan; Ming-Guo Zhai; Hai-Long He (Precambrian Research, 2025)

Ag modification and defect engineering optimization on three-dimensional coral-like high-entropy oxides to trigger effective oxygen evolution reaction - Bo Zhang; Mengzhao Liu; Meiqin Cui; Wenxue Lu; Ping Geng; Weiming Yi (Journal of Environmental Chemical Engineering, 2025)

Regulating zeolite acid-base sites for selective hydrogenation of 5-hydroxymethylfurfural - Xiaoqin Si; Meng Wu; Xueyi Qiao; Yu Yue; Feier Chen; Bo Xu; Yifan Niu; Tianliang Lu; Ling-Ping Xiao (Fuel, 2025)

A smartphone-integrated bimetallic ratiometric fluorescent probe for specific visual detection of tetracycline antibiotics in food samples and latent fingerprinting - Yin-Xia Sun; Bo-Tao Ji; Jiang-Hai Chen; Li-Ping Liu; Lu-Lu Gao; Zhe-Peng Deng; Yu Sun; Jian-Jun Wang; Biao Zhao; Jin-Guo Li (Food Chemistry, 2025)

Tauroursodeoxycholic acid targets HSP90 to promote protein homeostasis and extends healthy lifespan - Jia-Yu Liu; Yao Wang; Yue Guo; Run-Qi Zheng; Yun-Ying Wang; Yan-Yan Shen; Yan-Hong Liu; Ai-Ping Cao; Rui-Bo Wang; Bo-Yang Xie; Shuai Jiang; Qiu-Ying Han; et al. (Science China Life Sciences, 2025)

Advances in the study of nebulized tranexamic acid for pulmonary hemorrhage - Ping Zhang; Jiaoni Zheng; Xuefeng Shan; Bo Zhou (European Journal of Clinical Pharmacology, 2025)

Evaluation of PM2.5 bound microplastics and plastic additives in several cities in Taiwan: Spatial distribution and human health risk - Chien-Hsing Wu; Tuan Truong Minh Dang; Justus Kavita Mutuku; Li-Man Lin; Bo-Wun Huang; Guo-Ping Chang-Chien (Science of The Total Environment, 2025)

Functionalization of waste-derived artificial aggregates: A state-of-the-art review - Lan-Ping Qian; Ling-Yu Xu; Bo-Tao Huang; Yi Li; Jirong Lan; Fuyuan Gong; Hong Guan (Resources, Conservation and Recycling, 2025)

Ultrahigh energy storage density and efficiency of antiferroelectric AgNbO3-based MLCCs via reducing the off-center cations displacement - Ting Tang; Dong Liu; Long Wang; Jiaze Li; Zheng Zhang; Lei Zhao; Bo-Ping Zhang; Li-Feng Zhu (Chemical Engineering Journal, 2025)

Investigation on the applicability of lime amendments in the paddy soils polluted by e-waste dismantling for reducing the content of Cd and As in rice grains - Zhi-Bo Zhao; Haozhen Zhang; Tingsheng Jia; Linbin Wang; Yu-Ping Yang; Yufeng Wu (Journal of Soils and Sediments, 2025)

Characterization and complete genome sequence of a novel zetapatitivirus from Penicillium exsudans isolate RCEF7900 - Yanjie Zhao; Ping Wang; Lili He; Guogen Yang; Bo Huang (Archives of Virology, 2025)

Effects of nitrite exposure on the oxidative stress, immune response and intestine microbiota of Procambarus clarkii - Dan-Dan Bian; Yan-Xia Shi; Xi-Rong Zhu; Xiao-Li Sun; Xuan Xu; Lu Ding; Dai-Zhen Zhang; Qiu-Ning Liu; Bo-Ping Tang; Bao-Jian Zhu (Aquaculture, 2024)

Self-doped Na-carbon materials derived from a lyocell fiber for a high-performance trimethylamine gas sensor at room temperature - Bo Ran; Ping Hu; Jun Sun; Jialu Fang; Qihua Sun; Juqi Wang; Yuqing Zhu; Ning Tian; Zhaofeng Wu; Haiming Duan (Journal of Hazardous Materials, 2024)

Metabolic variation and oxidative stress responses of clams (Ruditapes philippinarum) perturbed by ofloxacin exposure - Bo Zhang; Xiaotong Wang; Fanping Meng; Shuhao Du; Haiping Li; Yufan Xia; Yu Yao; Ping Zhang; Jiali Cui; Zhengguo Cui (Journal of Hazardous Materials, 2024)

Advanced ceramic membranes: Novel strategies for sulfamethoxazole removal in wastewater treatment - Yen-Yi Lee; Guo-Ping Chang-Chien; I.-Cheng Li; Bo-Wun Huang; Minh-Ky Nguyen; Minh-Thuan Pham; Chien-Hsing Wu (Journal of Environmental Chemical Engineering, 2024)

Enhanced removal of polystyrene microplastics by three-dimensional flower-like layered double oxide: Behavior and mechanism insight - Ping Zhang; Bo Zeng; Jiale Zhang; Tianqi Wang; Youqin Zou; Bing Xie; Zongqi Song; Yuting Mao (Journal of Environmental Chemical Engineering, 2024)

Capability and mechanism of Cr(VI) removal by phthalic acid modified sulfidated microscale zero valent iron - Haowen Zou; Wenqiang Xu; Shuaixuan Ying; Shichao Cai; Bo Chen; Ping Wang; Zhongkuan Wu; Feng He (Journal of Environmental Chemical Engineering, 2024)

Integration of automatic discontinuity identification and multi-scale hierarchical modeling for stability analysis of highly-jointed rock slopes - Ya-ping Wang; Jia-wen Zhou; Jun-lin Chen; Yu-chuan Yang; Fei Ye; Hai-bo Li (International Journal of Rock Mechanics and Mining Sciences, 2024)

Transport characteristics of aeolian sand near different thresholds - Ting Jin; Ping Wang; Bo Cao (CATENA, 2024)

Grazer‐induced toxin production is energetically costly and significantly reduces growth of cylindrospermopsin‐producing cyanobacteria - Lamei Lei; Wei Liu; Zihan Chen; Liang Peng; Li‐Juan Xiao; Bo‐Ping Han; Brett A. Neilan (Limnology and Oceanography, 2024)
Toxins have been proposed as a defense mechanism for phytoplankton against zooplankton grazing. However, the associated costs are not understood. Here, we aim to reveal the costs in terms of both physiological and molecular responses in the cylindrospermopsin (CYN)‐producing cyanobacterium Raphidiopsis raciborskii . Exposure of R. raciborskii to Daphnia magna resulted in a significant increase in its CYN cell quota which was grazer cell density‐dependent, indicating an inducible effect on CYN production. A negative and significant relationship between cellular growth rate and CYN production suggested a growth‐defense trade‐off, highlighting the costly nature of toxin production. Despite strong transcriptional responses (121 differentially expressed genes) in R. raciborskii under grazing pressure, the CYN gene cluster remained largely unaffected, implying post‐transcriptional regulation of CYN biosynthesis. Significant variation was observed in transcripts for phosphorus metabolism and photosynthesis‐related genes, and evidenced that energy (ATP) metabolic processes were stimulated. This study is the first to demonstrate the high energy requirements for CYN production and provide insight into the molecular basis underlying the costs of toxin production.

Potassium persulfate enhances humification of chicken manure and straw composting: The perspective of rare and abundant microbial community structure and ecological interactions - Xiujun Tu; Bo Yin; Jie Kang; Zhenchao Wu; Yuhao Guo; Guoxu Ao; Yangcun Sun; Jingping Ge; Wenxiang Ping (Science of The Total Environment, 2024)

Regime shifts in the thermal dynamics of offshore China due to accelerated global warming - Yajun Wang; Huayang Cai; Yu Yan; Bozhi Wang; Huimin Pan; Ping Zhang; Bo Li; Tongtiegang Zhao (Science of The Total Environment, 2024)

Catastrophic outburst floods along the middle Yarlung Tsangpo River: Responses to coupled fault and glacial activity on the Southern Tibetan Plateau - Ping Wang; Huiying Wang; Gang Hu; Tao Liu; Jintang Qin; Yizhou Wang; Bo Xu; Jinyu Zhang; Xiaonan Shi; Jinhua Liu (Earth and Planetary Science Letters, 2024)

Direct near-infrared laser ignition of CL-20 by introducing DATNBI as a bi-functional additive: Energetic photosensitizer and self-assembly stimulator - Ping Ye; Heng Ding; Bo Yang; Weimiao Wang; Xiaodong Li; Zhiqiang Qiao; Rui Li; Guangcheng Yang; Guoqing Lv (Chemical Engineering Journal, 2024)

Toxicogenomic assessment of hydroxylated metabolites of PBDEs on cetaceans: An in vitro study - Chengzhang Li; Ziyao Tian; Xinying Li; Yajing Sun; Jiashen Tian; Yuqi Wu; Jingting Cai; Yijie He; Edmond Sanganyado; Ping Li; Bo Liang; Wenhua Liu (Chemosphere, 2024)

Comparative transcriptome analysis reveals the immune defense mechanism of the red swamp crayfish (Procambarus clarkii) in response to Vibrio parahaemolyticus challenge - Xiang Lu; Sheng Tang; Xin Liu; Jun-Jie Jiang; Dan-Dan Bian; Dai-Zhen Zhang; Qiu-Ning Liu; Yong-Xu Cheng; Bo-Ping Tang; Li-Shang Dai (Aquaculture, 2024)

Sustainable recycling of the biodegradable polyester poly(butylene succinate) via selective catalytic hydrolysis and repolymerization - Wei-Zhen Zheng; Xiao Li; Peng-Yuan Xu; Ze-Yang Zhang; Ping-Li Wang; Bo Lu; Dan Huang; Zhi-Chao Zhen; Jun-Hui Ji; Ge-Xia Wang (Resources, Conservation and Recycling, 2024)

Effect of lead exposure on silkworm midgut: Insights into oxidative gene expression, digestive function, and microbial community structure - Yan-Xia Shi; Dan-Dan Bian; Fan-Xing Chen; Ye Jin; Qi Jiang; Qiu-Ning Liu; Bo-Ping Tang; Li-Shang Dai (Process Safety and Environmental Protection, 2024)

CFD simulation and experimental validation of novel cutting device for underwater propeller entanglements - Jixin Liu; Xinxin Wei; Ping Qin; Bo He; C. Guedes Soares (Ocean Engineering, 2024)

Water-soluble biodegradable polyesters with pH and ionic responsivity - Xiao Li; Wei-Zhen Zheng; Peng-Yuan Xu; Ze-Yang Zhang; Ping-Li Wang; Bo Lu; Dan Huang; Zhi-Chao Zhen; Yang Zhao; Jun-Hui Ji; Ge-Xia Wang (Journal of Hazardous Materials, 2024)

Green synthesis of biomass-derived porous carbon for electrochemical detection of heavy metal ions: Methods, properties, and applications - Bo Zhang; Gangxin Ren; Linghao Ran; Mengzhao Liu; Ping Geng; Weiming Yi (Journal of Environmental Chemical Engineering, 2024)

Tailor-made the ultrathin nanosheet and acid site accessibility of mordenite zeolite for carbonylation of dimethyl ether - Feng Chen; Xiao-Bo Feng; Pan Deng; Li-Yun Zhang; Jing-Ping Zhao; Yu-Hui Wang; Bo-Yu Tao; Xiao-Yan Zhao; Jing-Pei Cao; Hong-Cun Bai (Chemical Engineering Journal, 2024)

Efficient and low-cost Ni-NiO/Al2O3 catalysts with dual-active-sites for selective catalytic conversion of phthalic anhydride to phthalide - Liang-Liang Zhang; Xiao-Min Duan; Kai-Xuan Yang; Yu-Bo Xu; Jia-Ping Lu; Wan-Xi Li; Bo-Qiong Li; Cai-Long Xue; Ya-Jie Liu (Chemical Engineering Journal, 2024)

Numerical and Field Investigations of Dynamic Failure Caused by Mining-Induced Tremor Based on Focal Mechanism - Zhi-Long He; Yan-Bo Zhang; Cai-Ping Lu; Qi Wang; Xu-Long Yao; Jie-Fang Song; You-Bang Lai (Rock Mechanics and Rock Engineering, 2024)

RIP3 regulates doxorubicin-induced intestinal mucositis via FUT2-mediated α-1,2-fucosylation - Wei Wen; Xiaomin Hu; Jialin Liu; Fanxin Zeng; Yihua Xu; Ye Yuan; Chunyan Gao; Xueting Sun; Bo Cheng; Jue Wang; Xinli Hu; Rui-Ping Xiao; et al. (Inflammation Research, 2024)

B-nZVI optimization of strength and heavy metal stability of lead-contaminated soil solidified by Portland cement - Chuang Yu; Zhao-kai Yu; Rao-ping Liao; Ya-bo Wang; Xiaoqing Cai; Zhi-lei Zeng (Environmental Geochemistry and Health, 2024)

Discovery and genomic characterization of three double-stranded RNA viruses coinfecting Conidiobolus taihushanensis - Ying Yin; Ping Wang; Lili He; Guogen Yang; Bo Huang (Archives of Virology, 2024)

Deep learning for genomic selection of aquatic animals - Yangfan Wang; Ping Ni; Marc Sturrock; Qifan Zeng; Bo Wang; Zhenmin Bao; Jingjie Hu (Marine Life Science & Technology, 2024)

Spatial pattern and coupling characteristics analysis of maritime traffic and economic development based on shipping big data - Ping Wang; Yubo Wen; Bo Ai; Xue Liu (Frontiers in Marine Science, 2024)
The rapid development of maritime transport and the gradual increase in the number of ports, ships and shipping routes can produce direct economic benefits for regional development, and a profound grasp of the actual situation of maritime transport makes it possible to make practical plans for economic development and thus rationally develop and use marine resources. However, there is a lack of research on maritime transport, so this study is based on the AIS, waterways, routes and ports data in the near-shore sea area of Guangdong Province. Using GIS spatial analysis technology and various mathematical models, we refer to the evaluation method of road traffic dominance. It analyses and proposes the evaluation indexes of maritime traffic advantages, such as the density of maritime traffic network and the proximity of ports. Based on the actual situation of the study regions, the indicators were quantitatively evaluated and analyzed. The economic development level of each region was also quantitatively evaluated using principal component analysis, and the study regions were classified based on the coupling-coordination model. The results show that the coastal area of Guangdong Province is divided into four types of zones according to the coupling-coordination type of zoning criteria. Corresponding development suggestions are put forward for different zones, and the research results provide certain practical guidelines for promoting the benign cycle development of maritime traffic and economy, and have important guiding significance and application value for the organization and safety of maritime traffic.

Label-free and ultrasensitive detection of environmental lead ions based on spatially localized DNA nanomachines driven by hyperbranched hybridization chain reaction - Xiao-Yu Li; Bo-Xi Zhou; Yu-Ling Xiao; Xin Liu; Yong-Qian Wang; Ming-Min Li; Jun-Ping Wang (Journal of Hazardous Materials, 2024)

New insight into process pH regulation on caproate production from waste activated sludge acidogenic fermentation liquid by cathodic electro-fermentation - Ping Wu; Qi-hao Cao; Guo-dong Kang; Dan Qi; Hong-bo Liu; Sheng-hu Zhang; Hou-hu Zhang; He Liu (Journal of Cleaner Production, 2024)

Insights into acrylamide and furanic compounds in coffee with a focus on roasting methods and additives - Hsin-Chieh Kung; Bo-Wun Huang; Nicholas Kiprotich Cheruiyot; Kuan-Lin Lee; Guo-Ping Chang-Chien (Food Research International, 2024)

Research progress of nanoparticles enhanced carbon dioxide foam stability and assisted carbon dioxide storage: A review - Yuanxiu Sun; Zhengyang Jia; Bo Yu; Wei Zhang; Liping Zhang; Ping Chen; Lu Xu (Chemical Engineering Journal, 2024)

Corrigendum to “2′-O-galloylhyperin attenuates LPS-induced acute lung injury via upregulation antioxidation and inhibition of inflammatory responses in vivo” [Chem. Biol. Interact. 304 (1 May 2019) 20–27] - Sun-Dong Zhang; Peng Wang; Jing Zhang; Wei Wang; Li-Ping Yao; Cheng-Bo Gu; Thomas Efferth; Yu-Jie Fu (Chemico-Biological Interactions, 2024)

Electrical structure identification of deep shale gas reservoir in complex structural area using wide field electromagnetic method - Zhi-Wen Gu; Yue-Gang Li; Chang-Heng Yu; Zhong-Ping Zou; Ai-Guo Hu; Xue-Bo Yin; Qinag Wang; Heng Ye; Zhang-Kun Tan (Applied Geophysics, 2024)

Molecular characterization of fad6 gene and its transcriptional changes in response to different initial diets and nutritional status in yellow catfish (Pelteobagrus fulvidraco) - Bo Zhou; Xiu-Ying Wei; Zheng-Yong Wen; Bin Wang; Yu-Ying Zhao; Wan-Hong Zeng; Yu He; Panita Prathomya; Yun-Yun Lv; Yan-Ping Li; Jun Wang; Rui Li; et al. (Frontiers in Marine Science, 2024)
Fatty acid desaturases (FADs) are rate-limiting enzymes for the biosynthesis of highly unsaturated fatty acids (HUFAs). As a new member of the FAD family, Fad6 and its roles remain unclear in various teleost fishes. In this study, we identified a fad6 gene from yellow catfish (yc fad6 ) and determined its spatiotemporal expression patterns and responses to different initial diets and nutritional status in yellow catfish. Our results showed that the open reading frame (ORF) of yc fad6 was 1,080 bp in length, encoding a protein of 359 amino acids. Multiple protein sequences alignment proved that fad6 is highly conserved among diverse vertebrates. Meanwhile, phylogenetic analysis revealed that Southern catfish and yellow catfish were clustered into one branch, supporting evolutionary consistence between the fad6 gene and fish morphology. Moreover, comparisons of genomic synteny and gene structure revealed functional and evolutionary conservation of the fad6 gene in various teleost fishes. Tissue distribution analysis by quantitative RT-PCR demonstrated that the yc fad6 gene was extensively expressed in examined tissues, with higher transcription levels in the heart and liver. Meanwhile, yc fad6 gene was widely expressed in various developmental stages, indicating Fad6 may play important roles in HUFA biosynthesis at early developmental stages in yellow catfish. Functional experiments verified that the transcription of yc fad6 decreased significantly with the extension of feeding time (with egg yolk or Artemia nauplii ) at the early developmental stages, indicating that a diet rich in HUFA can remarkably inhibit the transcription of yc fad6 in yellow catfish. In addition, yc fad6 transcription was significantly reduced after a short-term (24-h) or long-term food deprivation (1-week) and then continued to decrease during refeeding, suggesting that nutritional states can affect the transcription of yc fad6 , which further regulates the metabolism of HUFAs. Anyway, these fundamental findings provide basic references for further investigating evolutionary and physiological functions of the fad6 gene in yellow catfish as well as in other teleost fishes.

New geographical records and molecular investigation of the ciliate Spirostomum - Sheng-Bo Zhou; Zhi-Yu Zhao; Ping Guan; Bo Qu (Protist, 2024)

Evaluation and obstacle analysis of sustainable development in small towns based on multi-source big data: A case study of 782 top small towns in China - Mingman Chen; Chen Chen; Chi Jin; Bo Li; Yingqing Zhang; Ping Zhu (Journal of Environmental Management, 2024)

Molecular insights into the interactions of theaflavin and epicatechin with different lipid bilayer membranes by molecular dynamics simulation - Rong-zu Nie; Huo-min Luo; Jing-yu Chen; Li-heng Sun; Zi-bo Wang; Zhen-ping Zhang; Ya-ru Bao (Chemistry and Physics of Lipids, 2024)

FABP3 Induces Mitochondrial Autophagy to Promote Neuronal Cell Apoptosis in Brain Ischemia-Reperfusion Injury - Fang-Fang Zhong; Bo Wei; Guo-Xiang Bao; Yi-Ping Lou; Ming-Er Wei; Xin-Yue Wang; Xiao Xiao; Jin-Jin Tian (Neurotoxicity Research, 2024)

A novel betapartitivirus isolated from Cordyceps militaris, an edible-medicinal mushroom - Hanwen Lu; Ping Wang; Jing Sun; Ying Yin; Guogen Yang; Bo Huang (Archives of Virology, 2024)

Retrieval of subsurface dissolved oxygen from surface oceanic parameters based on machine learning - Bo Ping; Yunshan Meng; Fenzhen Su; Cunjin Xue; Zhi Li (Marine Environmental Research, 2024)

The fabrication of Mn single atoms/clusters on Al2O3 for enhanced catalytic NO oxidation - Xiao-Ke Hou; Hui-Xin Zhang; Yi-Bo Wang; Jin-Ping Zhang; Xin Gao; Lei Chen; Chao Li; Hong-Mei Jing; Chi He; Qiang Lu; Chun-Ran Chang (Fuel, 2024)

Erratum to: Cholesterol homeostasis regulated by ABCA1 is critical for retinal ganglion cell survival - Jialiang Yang; Yuhong Chen; Tongdan Zou; Bai Xue; Fang Yang; Xiangzhou Wang; Yibo Huo; Boyun Yan; Yuxia Xu; Shiyu He; Yi Yin; Jing Wang; et al. (Science China Life Sciences, 2024)

The identification of toll-like receptor genes in large yellow croaker (Larimichthys crocea): provides insights into its environmental adaptation to biological and abiotic stresses - Ting-Yan Yao; Qing-Tao Miao; Xuan-Yang Sun; Chen Rui; Qing-Ping Xie; Xu-Bo Wang (Frontiers in Marine Science, 2024)
Large yellow croaker ( Larimichthys crocea ), the most developing fish of China, suffering from both biotic and abiotic stressors. A genome-wide study was performed for the first time to investigate the roles of Toll-like receptor genes in large yellow croaker ( LcTLRs ) working in hypoxia response and Aeromonas hydrophila infection. 12 TLR genes were identified and annotated, and phylogenetic tree, analysis of structure and motifs demonstrated that TLRs were highly conserved. To further investigate the LcTLRs under environmental stress, expression pattern analysis of hypoxic response and Aeromonas hydrophila infection revealed that there were nine and six members of LcTLRs showing significant differential expression, indicating that they were concerned in hypoxia stress and disease responses. Meanwhile, their expression levels were validated utilizing qPCR. Taken together, a greater appreciation and understanding of TLRs function in the reaction to biotic and abiotic stress would ultimately lead to more efficiently environmental adaptation in large yellow croaker.

Seasonal characterization of chemical and optical properties of water-soluble organic aerosol in Beijing - Bo You; Zhiqiang Zhang; Aodong Du; Yan Li; Jiaxing Sun; Zhijie Li; Chun Chen; Wei Zhou; Weiqi Xu; Lu Lei; Pingqing Fu; Shengjie Hou; et al. (Science of The Total Environment, 2024)

Isolation of undescribed cladosporols and spirobisnaphthalenes from a plant pathogen Cladosporium cladosporioides F-10-2-A - Peng Li; Zi Jin Zhang; Yu Tong Guo; Jing Guan; Lin Bo Wen Xi; Li-Ping Lin (Phytochemistry, 2024)

Numerical analysis of wet-deck slamming characteristics for trimaran section with different main-hull profiles - Jian-Yu Liu; Wen-Yang Duan; Kang-Ping Liao; Shan Ma; Wen-Bo Shao; Yi-Fan Zhang (Ocean Engineering, 2024)

Carbon and conodont apatite oxygen isotope records from the Alengchu section in western Yunnan and their paleoclimatic and paleogeographic implications - Bo Chen; Mei-Qiong Zhang; Wen-Kun Qie; Kun Liang; Jian-Feng Lu; Michael M. Joachimski; Xue-Ping Ma (Palaeoworld, 2024)

Adsorption behavior of CuO doped GeS monolayer on the thermal runaway gas evolution in lithium battery energy storage systems - Jinjie Wang; Bo Lin; Ping Wang; Lu-Qi Tao; Yuan Zhang; Siquan Li (Journal of Environmental Chemical Engineering, 2024)

MetaIBM: A Python-based library for individual-based modelling of eco-evolutionary dynamics in spatial-explicit metacommunities - Jian-Hao Lin; Yu-Juan Quan; Bo-Ping Han (Ecological Modelling, 2024)

Chemical constituents from Strobilanthes cusia and their chemotaxonomic significance - Si-Qi Huang; Chao-Tian He; Qiu-Ying He; Gui-Shuai Lang; Hong-Jie Chen; Li-Ping Teng; Zhong-Bo Zhou (Biochemical Systematics and Ecology, 2024)

Trace element compositions of pyrite and stibnite: implications for the genesis of antimony mineralization in the Yangla Cu skarn deposit, Northwestern Yunnan, China - Ping Pan; Xinfu Wang; Bo Li; Guo Tang; Zuopeng Xiang (Acta Geochimica, 2024)

Three-dimensional multi-channel structure NiCo alloy used for boosting efficient overall water splitting - Fan Yang; Zelin Li; Fei Zhu; Xiaolong Chen; Songwei Ge; Fei Yin; Fairy Fan Yang; Rui Yang; Yanjing Liu; Lili Gao; Qiang Wang; Rui Feng; et al. (Fuel, 2024)

Overall quality changes and deterioration mechanism of fragrant rapeseed oils during 6-Month storage - Chen Chen; Ping-Ping Ye; Feng-Jie Cui; Ming Tan; Hai-Bo Zhang; Tong-Lin Zhou; Jian-Cheng Shi; Xue-Quan Shu; Zhi-Wei Chen (Food Chemistry, 2024)

Biomimetically ordered ultralong hydroxyapatite nanowires-based hierarchical hydrogel scaffold with osteoimmunomodulatory and osteogenesis abilities for augmenting bone regeneration - Xiangwu Geng; Yifan Tang; Bo Yuan; Yuya Dai; Han-Ping Yu; Zhi-Chao Xiong; Ying-Jie Zhu; Xiongsheng Chen (Chemical Engineering Journal, 2024)

Isolation of Rhizobacteria from Crocus Sativus L. Rhizosphere and Their Effects on Host-Growth Promotion - Jing-Chao Xu; Xing-Guang Xie; Xue-Wen Bi; Jia-Hao Zhang; Zi-Hui Zhao; Khalid Rahman; Bo Zhu; Lu-Ping Qin; Ting Han (Journal of Plant Growth Regulation, 2024)

Interspecific occupancy-abundance relationship of benthic diatoms changes seasonally with attachment mode in a tropical river - Lin Tan; Yuting Liu; Muqi Shen; Guifeng Wei; Linglin Wan; Quehui Tang; Bo-Ping Han (Hydrobiologia, 2024)

Evaluation of tire wear particle concentrations in TSP and PM10 using polymeric and molecular markers - Hsin-Chieh Kung; Tran Phuong Uyen; Bo-Wun Huang; Justus Kavita Mutuku; Guo-Ping Chang-Chien (Process Safety and Environmental Protection, 2024)

Sesquiterpenes from Inula macrophylla and their anti-neuroinflammatory activity - Rui Ma; Bakhrom Komilov; Cheng-Bo Wang; Komila Alibekovna Eshbakova; Jun-Li Yang; Wei Ha; Yan-Ping Shi (Phytochemistry Letters, 2024)

A comprehensive assessment indicator of the water-energy-food nexus system based on the material consumption relationship - Lingang Hao; Jingjie Yu; Ping Wang; Chunhui Han; Boris Gojenko; Bo Qu; Enhui Jiang; Sherzod Muminov (Journal of Hydrology, 2024)

A new perspective on the mechanism of swift corrosion perforation of copper in solutions containing sulfate-reducing bacteria - Huixuan Qian; Bo Zhang; Yanwei Zeng; Honglei Guo; Zhiyuan Feng; Bing Lei; Ping Zhang; Guozhe Meng (Journal of Cleaner Production, 2024)

A human-specific insertion promotes cell proliferation and migration by enhancing TBC1D8B expression - Hui Zhao; Lin-Lin Liu; Jian Sun; Lian Jin; Hai-Bing Xie; Jian-Bo Li; Hui Xu; Dong-Dong Wu; Xiao-Lin Zhuang; Min-Sheng Peng; Ya-Jun Guo; Wei-Zhu Qian; et al. (Science China Life Sciences, 2024)

Cognitive Deficits and Alzheimer’s Disease-Like Pathologies in the Aged Chinese Tree Shrew - Hongli Li; Bo-Lin Xiang; Xiao Li; Cong Li; Yu Li; Ying Miao; Guo-Lan Ma; Yu-Hua Ma; Jia-Qi Chen; Qing-Yu Zhang; Long-Bao Lv; Ping Zheng; et al. (Molecular Neurobiology, 2024)

Growth of Scenedesmus obliquus in anaerobically digested swine wastewater from different cleaning processes for pollutants removal and biomass production - Xiao-Bo Tan; Ze-Yuan Zhao; Hui Gong; Tao Jiang; Xin-Ping Liu; Jian-Yu Liao; Ya-Lei Zhang (Chemosphere, 2024)

Comprehensive evaluation of antibiotics pollution the Yangtze River basin, China: Emission, multimedia fate and risk assessment - Yu-Ru Chen; Yan-Ping Duan; Zhi-Bo Zhang; Yao-Feng Gao; Chao-Meng Dai; Yao-Jen Tu; Jun Gao (Journal of Hazardous Materials, 2024)

Kinetic models applied to quality change and shelf-life prediction of fresh-cut pineapple in food cold chain - Bo-Kai Liao; Ai Ping Goh; Chong In Lio; Hsin-I Hsiao (Food Chemistry, 2024)

Complete genome sequence of a novel gammapartitivirus from Penicillium oxalicum RCEF7482 - Jing Sun; Ping Wang; Hanwen Lu; Guogen Yang; Bo Huang (Archives of Virology, 2024)

Co-infection of Aspergillus ochraceopetaliformis strain RCEF7483 by a novel chrysovirus and a known partitivirus - Ping Wang; Hanwen Lu; Jing Sun; Guogen Yang; Bo Huang (Archives of Microbiology, 2024)

Brittleness ductility transition depth of new fracture in the Baodi Miaozhuang Uplift - He Li; Yi-Bing Dong; Yi-Xi Wang; Wu-Ping Gao; Cheng-Guo Yan; Ling-Ling Cai; Bo-Yang Wu; Peng Zhao (Applied Geophysics, 2024)

Road dust exposure and human corneal damage in a plateau high geological background provincial capital city: Spatial distribution, sources, bioaccessibility, and cytotoxicity of dust heavy metals - Zi-Yue Yang; Hai Liu; Jing-Ya Li; Ya-Bo Bao; Ji Yang; Li Li; Zi-Yu Zhao; Qin-Xiang Zheng; Ping Xiang (Science of The Total Environment, 2024)

Age and sedimentology of a Late Pleistocene dammed paleolake in the middle Yarlung Tsangpo River, southern Tibetan Plateau - Huiying Wang; Ping Wang; Gang Hu; Bo Xu; Renmao Yuan; Lingfan Shi; Ziyue Ding (Quaternary International, 2024)

An AUV collision avoidance algorithm in unknown environment with multiple constraints - Ning Dai; Ping Qin; Xiaoting Xu; Yixiao Zhang; Yue Shen; Bo He (Ocean Engineering, 2024)

Evaluations of extreme wave heights around Hainan Island and their uncertainty induced by decadal variations of input variables - Junmin Li; Shaotian Li; Yineng Li; Wuyang Chen; Bo Li; Junliang Liu; Ping Shi (Ocean Engineering, 2024)

Catalytic reforming of cellulose pyrolysis volatiles over hierarchical HZSM-5: Mechanism of a protective effect of tetrapropylammonium (TPA+) during alkali treatment - Xin-Bo Pang; Jing-Pei Cao; Nai-Yu Yao; Jing-Ping Zhao; Tian-Long Liu; Shi-Jie Cai; Hong-Yan Wang; Yan-Cheng Hu; Xiao-Yan Zhao (Fuel, 2024)

QMMM 2023: A program for combined quantum mechanical and molecular mechanical modeling and simulations - Hai Lin; Yan Zhang; Soroosh Pezeshki; Adam W. Duster; Bo Wang; Xin-Ping Wu; Shi-Wen Zheng; Laura Gagliardi; Donald G. Truhlar (Computer Physics Communications, 2024)

Highly efficient production of rhamnolipid in P. putida using a novel sacB-based system and mixed carbon source - Ai-Ping Pang; Yun Wang; Teng Zhang; Feng Gao; Ji-dong Shen; Lianggang Huang; Junping Zhou; Bo Zhang; Zhi-Qiang Liu; Yu-Guo Zheng (Bioresource Technology, 2024)

A Novel Mixed-Mode Power Exponent Cohesive Zone Model for FDEM and Its Application to Tunnel Excavation in the Layered Rock Mass - Ping Liu; Quansheng Liu; Penghai Deng; Yin Bo; Xianqi Xie (Rock Mechanics and Rock Engineering, 2024)

Effects of dietary betaine supplementation on growth performance, feed intake, intestinal histology, lipid metabolism, and immune response of black tiger shrimp (Penaeus monodon) fed diets containing two levels of raw feed attractants - Gui-Lun He; Meng-Lin Shi; Yu-Cheng Liu; Liu-Tong Chen; Xin Chen; Wen-Bo Zhu; Zheng-Bang Chen; Bei-Ping Tan; Shi-Wei Xie (Aquaculture International, 2024)

Generalist and topologically central avian frugivores promote plant invasion unequally across land‐bridge islands - Chen Zhu; Bo Dalsgaard; Wande Li; Fernando Gonçalves; Maximilian G. R. Vollstädt; Peng Ren; Xue Zhang; Junjie Shao; Ping Ding; Xingfeng Si (Ecology, 2024)
Seed dispersal by frugivorous birds facilitates plant invasions, but it is poorly known how invasive plants integrate into native communities in fragmented landscapes. We surveyed plant–frugivore interactions, including an invasive plant ( Phytolacca americana ), on 22 artificial land‐bridge islands (fragmented forests) in the Thousand Island Lake, China. Focusing on frugivory interactions that may lead to seed dispersal, we built ecological networks of studied islands both at the local island (community) and at landscape (metacommunity) levels. On islands with P. americana , we found that P. americana impacted local avian frugivory networks more on islands with species‐poor plant communities and on isolated islands. Moreover, as P. americana interacted mainly with local core birds (generalists), this indicates reduced seed dispersal of native plants on invaded islands. At the landscape level, P. americana had established strong interactions with generalist birds that largely maintain seed‐dispersal functions across islands, as revealed by their topologically central roles both in the regional plant–bird trophic network and in the spatial metanetwork. This indicates that generalist frugivorous birds may have facilitated the dispersal of P. americana across islands, making P. americana well integrated into the plant–frugivore mutualistic metacommunity. Taken together, our study demonstrates that the impact of plant invasion is context‐dependent and that generalist native frugivores with high dispersal potential may accelerate plant invasion in fragmented landscapes. These findings highlight the importance of taking the functional roles of animal mutualists and habitat fragmentation into account when managing plant invasions and their impact on native communities.

Blue carbon development in China: realistic foundation, internal demands, and the construction of blue carbon market trading mode - Ping Li; Dahai Liu; Chao Liu; Xiaoxuan Li; Zhenhang Liu; Yanjing Zhu; Bo Peng (Frontiers in Marine Science, 2024)
Promoting the inclusion of blue carbon in market trading is crucial for recognizing its value and protecting the marine ecological environment. However, China currently does not have an internationally influential blue carbon market trading platform, which hampers the transmission of supply and demand in the blue carbon market and prevents the realization of blue carbon value. In this study, we analyze the feasibility and necessity of establishing a trading mode for the blue carbon market in China. The introduction of futures trading in the blue carbon market’s trading mode allows for the use of futures pricing methods and multiple financial instruments to address the challenges of income cost mismatch in blue carbon project development. The paper also discusses key strategies for the development of China’s blue carbon market, including the creation of a blue carbon trading methodology, the improvement of preservation and appreciation mechanisms, and the establishment of a unified trading platform. These strategies aim to provide intellectual support and decision-making reference for the construction of the market.

Multiomics analyses of two Leonurus species illuminate leonurine biosynthesis and its evolution - Peng Li; Meng-Xiao Yan; Pan Liu; Dan-Jie Yang; Ze-Kun He; Yun Gao; Yan Jiang; Yu Kong; Xin Zhong; Sheng Wu; Jun Yang; Hong-Xia Wang; et al. (Molecular Plant, 2024)

Insight into the synergistic mechanism of Co and N doped titanium-based adsorbents for liquid lithium extraction - Ping Zhang; Mingcheng Yang; Chuan Xu; Qian Wang; Chuanshu He; Can Liu; Bo Lai (Chemical Engineering Journal, 2024)

Rapid photothermal antibacterial and antifungal textiles through dynamic disulfide bond-assisted in-situ deposition of SeNPs - Leilei Wu; Xueming Bao; Zirong Li; Yuanyuan Yu; Ying Liu; Bo Xu; Man Zhou; Qiang Wang; Ping Wang (Chemical Engineering Journal, 2024)

Achieving ultrahigh energy storage density and efficiency above 90% via reducing defect concentrations for AgNbO3-based multilayer capacitors - Dekai Shi; Dong Liu; Lei Zhao; Qi Wang; Ting Tang; Xinyue Long; Liqin Yan; Bo-Ping Zhang; He Qi; Li-Feng Zhu (Chemical Engineering Journal, 2024)

Effects of land-use patterns on seasonal water quality at multiple spatial scales in the Jialing River, Chongqing, China - Yuan-Bo Wang; Muhammad Junaid; Jiao-Yun Deng; Qi-Ping Tang; Lin Luo; Zhuo-Yuan Xie; De-Sheng Pei (CATENA, 2024)

Soybean WRINKLED1 protein GmWRI1a promotes flowering under long-day conditions via regulating expressions of flowering-related genes - Zhikun Wang; Siqi Xing; Meng Li; Qingyan Zhang; Qiang Yang; Pengfei Xu; Bo Song; Ping Shang; Mingming Yang; Changhuan Du; Jihan Chen; Shanshan Liu; et al. (Plant Science, 2023)

Chemical constituents from the stems of Marsdenia tenacissima - Yin-Bo Pan; Xiu-Qing Song; Ping Sun; Hua Zhang (Phytochemistry Letters, 2023)

An acidic heteropolysaccharide rich in galactose and arabinose derived from ginger: Structure and dynamics - Xiao-tong Lin; Bo-xian Xiao; Jun-ping Liu; Ming-yuan Cao; Zhi-ping Yang; Li-yan Zhao; Gui-tang Chen (Food Bioscience, 2023)

Identifying priority PBT-like compounds from emerging PFAS by nontargeted analysis and machine learning models - Bao-Cang Han; Jin-Song Liu; Aaron Bizimana; Bo-Xuan Zhang; Sukhodolska Kateryna; Zhen Zhao; Li-Ping Yu; Zhong-Zeng Shen; Xiang-Zhou Meng (Environmental Pollution, 2023)

The analyses of the complete mitochondrial genomes of three crabs revealed novel gene rearrangements and phylogenetic relationships of Brachyura - Zhao-Zhe Xin; Sheng Tang; Xiang Lu; Hua-Bin Zhang; Dai-Zhen Zhang; Gang Wang; Bo-Ping Tang; Qiu-Ning Liu (Molecular Biology Reports, 2023)

Improving Yolo5 for Real-Time Detection of Small Targets in Side Scan Sonar Images - Jianjun Wang; Qi Wang; Guocheng Gao; Ping Qin; Bo He (Journal of Ocean University of China, 2023)

SIRT3-dependent mitochondrial redox homeostasis mitigates CHK1 inhibition combined with gemcitabine treatment induced cardiotoxicity in hiPSC-CMs and mice - Jia-Wen Chen; Tian-Kai Shan; Tian-Wen Wei; Qi-Qi Jiang; Chong Du; Ling-Feng Gu; Tong-Tong Yang; Liu-Hua Zhou; Si-Bo Wang; Yu-Lin Bao; Hao Wang; Yong Ji; et al. (Archives of Toxicology, 2023)

Cytotoxic phenyl polyketides from Hypericum curvisepalum N. Robson - Qiu-Ying He; Hong Zeng; Qiu-Lan Zhang; Guan-Fang Qin; He-Bin Wang; Li-Ping Teng; Zhong-Bo Zhou (Natural Product Research, 2023)

All-natural environmentally degradable poly (butylene terephthalate-co-caprolactone): A theoretical and experimental study of its degradation properties and mechanisms - Peng-Yuan Xu; Ping-Li Wang; Tian-Yuan Liu; Zhi-Chao Zhen; Bo Lu; Dan Huang; Ge-Xia Wang; Jun-Hui Ji (Science of The Total Environment, 2023)

Environmental cadmium exposure facilitates mammary tumorigenesis via reprogramming gut microbiota-mediated glutamine metabolism in MMTV-Erbb2 mice - Yang Yue; Huadong Zhang; Ping Deng; Miduo Tan; Chengzhi Chen; Bo Tang; Jingdian Li; Fengqiong Chen; Qi Zhao; Ling Li; Rongrong Hao; Hui Wang; et al. (Science of The Total Environment, 2023)

Contribution of the bacterial community of poorly fermented oat silage to biogas emissions on the Qinghai Tibetan Plateau - Chaosheng Liao; Binbin Na; Xiaolong Tang; Man Zhao; Changbing Zhang; Shiyong Chen; Minghong You; Binqiang Bai; Lizhuang Hao; Dorjeeh Tondrob; Guangpeng Qu; Shuqing Yang; et al. (Science of The Total Environment, 2023)

Lindenane sesquiterpenoid dimers from Chloranthus holostegius with anti-neuroinflammatory activities in BV-2 microglia - Zhao-Chun Zhan; Yi-Ping Xia; Qing Tang; Hui-Hui Zhu; Jing-Yi Du; Jun-Xing Cai; Yan-Jun Chen; Zhong-Nan Wu; Yao-Lan Li; Neng-Hua Chen; Guo-Cai Wang; Yu-Bo Zhang (Phytochemistry, 2023)

Biodegradation of polyvinyl chloride, polystyrene, and polylactic acid microplastics in Tenebrio molitor larvae: Physiological responses - Bo-Yu Peng; Ying Sun; Ping Li; Siran Yu; Yazhou Xu; Jiabin Chen; Xuefei Zhou; Wei-Min Wu; Yalei Zhang (Journal of Environmental Management, 2023)

mitfa deficiency promotes immune vigor and potentiates antitumor effects in zebrafish - Wan-Ping Bian; Shao-Lin Xie; Chao Wang; Grigoriy G. Martinovich; Yan-Bo Ma; Pan-Pan Jia; De-Sheng Pei (Fish & Shellfish Immunology, 2023)

Effect of stirrups on shear performance of geometrically-similar reinforced concrete deep beams: An experimental study - Liu Jin; Jiangxing Zhang; Bo Song; Dong Li; Ping Li; Xiuli Du (Engineering Structures, 2023)

Amino acids as in-situ electron donors drive medium chain fatty acids production from sludge acidogenic fermentation liquid by electro-fermentation enhancement - Ping Wu; Peng Ding; Qi-hao Cao; Chao Zhang; Bo Fu; Hong-bo Liu; Chong-jun Chen; He Liu (Chemical Engineering Journal, 2023)

Soil depths and developmental stages of biological soil crusts are more important than shrub cover in structuring prokaryotic communities - Lin Xu; Yongping Kou; Wenjun Xiong; Chaonan Li; Ping Zou; Bingjie Jiao; Zhenfeng Xu; Bo Tan; Minjie Yao; Bingchang Zhang; Xiangzhen Li (CATENA, 2023)

A novel “Turn-on” fluorometric assays triggered reaction for β-glucosidase activity based on quercetin derived silicon nanoparticles and its potential use for cell imaging - Yves Iradukunda; Jing-Yan Kang; Xiao-bo Zhao; Stanislas Nsanzamahoro; Xiao-Kang Fu; Jia Liu; Yu-Zhu Ding; Wei Ha; Yan-Ping Shi (Analytica Chimica Acta, 2023)

Growth of Scenedesmus obliquus on anaerobic soybean wastewater using different wasted organics for high biomass production and nutrients recycling - Xiao-Bo Tan; Zhuo-Yi Huang; Xi-Ping Wan; Zi-Jie Duan; Ya-Lei Zhang; Jian-Yu Liao (Chemosphere, 2023)

Effects of interspecific interactions on soil carbon emission and efficiency in the semiarid intercropping systems - Wei Wang; Meng-Ying Li; Rui Zhou; Shuang-Guo Zhu; Hong-Yan Tao; Aziz Khan; Aimee Grace Uzamurera; Bao-Zhong Wang; Jun-Ming Jin; Yue Ma; Wen-Bo Li; Xiu-Ping Tao; et al. (Soil and Tillage Research, 2023)

Insight into the plant-associated bacterial interactions: Role for plant arsenic extraction and carbon fixation - Yibo Liu; Baiyu Zhang; Ye Yao; Bo Wang; Yiqi Cao; Yanping Shen; Xiaohui Jia; Fukai Xu; Ziwei Song; Chengpeng Zhao; HongJie Gao; Ping Guo (Science of The Total Environment, 2023)

Application of UPLC-Triple TOF-MS/MS metabolomics strategy to reveal the dynamic changes of triterpenoid saponins during the decocting process of Asian ginseng and American ginseng - Li-Hua Chen; You-Bo Zhang; Xiu-Wei Yang; Jing Xu; Zhao-Jing Wang; Yi-Zheng Sun; Wei Xu; Ying-Ping Wang (Food Chemistry, 2023)

How does land-use change alter soil microbial diversity, composition, and network in subtropical China? - Huacui Xiao; Hao Sheng; Lina Zhang; Liang Zhang; Bo Pan; Ping Zhou (CATENA, 2023)

Trichoscopy for early diagnosis and follow-up of pet-related neonatal tinea capitis - Hui-Lin Zhi; Xiu-Jiao Xia; Hong Shen; Wen-Wen Lv; Yan Zhong; Bo Sang; Qiu-Ping Li; Ze-Hu Liu (Mycopathologia, 2023)

SLC26A11 Inhibition Reduces Oncotic Neuronal Death and Attenuates Stroke Reperfusion Injury - Shunhui Wei; Bo Chen; See Wee Low; Charlene Priscilla Poore; Yahui Gao; Bernd Nilius; Ping Liao (Molecular Neurobiology, 2023)
Neuronal swelling is a pathological feature of stroke which contributes to the formation of cytotoxic edema. Under hypoxic condition, aberrant accumulation of sodium and chloride ions inside neurons increases osmotic pressure, leading to cell volume increase. Sodium entry pathway in neurons has been studied extensively. Here, we determine whether SLC26A11 is the major chloride entry pathway under hypoxia and could be the target for protection against ischemic stroke. In this study, electrophysiological properties of chloride current in primary cultured neurons were characterized using low chloride solution, 4,4′-diisothiocyano-2,2′-stilbenedisulfonic acid, and SLC26A11-specific siRNA under physiological conditions or ATP-depleted conditions. In vivo effect of SLC26A11 was evaluated on a rat stroke reperfusion model. We found that SLC26A11 mRNA in primary cultured neurons was upregulated as early as 6 h after oxygen glucose deprivation, and later, the protein level was elevated accordingly. Blockade of SLC26A11 activity could reduce chloride entry and attenuate hypoxia-induced neuronal swelling. In the animal stroke model, SLC26A11 upregulation was mainly located in surviving neurons close to the infarct core. SLC26A11 inhibition ameliorates infarct formation and improves functional recovery. These findings demonstrate that SLC26A11 is a major pathway for chloride entry in stroke, contributing to neuronal swelling. Inhibition of SLC26A11 could be a novel therapeutic strategy for stroke.

The seasonal patterns of aquatic insect composition and diversity in a disturbed (sub)tropical river revealed by linear and nonlinear approaches with occurrence and abundance data - Lu Wang; Yaokai Li; Jiaxu Li; Lin Tan; Eric Zeus Rizo; Bo-Ping Han (Hydrobiologia, 2023)

A strain of Vibrio alginolyticus isolated from Azumapecten farreri and its pathogenic mechanism using CRISPR-Cas9 technology - Jingxue Ma; Peiyu Zhang; Minggang Zheng; Bo Wang; Ping Gao; Lingyun Qu; Fengrong Zheng (Biotechnology Letters, 2023)

Influence of the oval hole on rock mechanical mechanism under uniaxial and biaxial compression: insights from the combined finite-discrete element method - Ping Liu; Xianqi Xie; Quansheng Liu; Penghai Deng; Xing Huang; Yin Bo (European Journal of Environmental and Civil Engineering, 2023)

Schizophrenia in the genetic era: a review from development history, clinical features and genomic research approaches to insights of susceptibility genes - Ye Lv; Lin Wen; Wen-Juan Hu; Chong Deng; Hui-Wen Ren; Ya-Nan Bao; Bo-Wei Su; Ping Gao; Zi-Yue Man; Yi-Yang Luo; Cheng-Jie Li; Zhi-Xin Xiang; et al. (Metabolic Brain Disease, 2023)

Effects of TCPP and TCEP exposure on human corneal epithelial cells: Oxidative damage, cell cycle arrest, and pyroptosis - Zhen-Ning Zhang; Dan-Lei Yang; Hai Liu; Jue Bi; Ya-Bo Bao; Jiao-Yang Ma; Qin-Xiang Zheng; Dao-Lei Cui; Wei Chen; Ping Xiang (Chemosphere, 2023)

Growth-promoting and low-salt adaptation responses boosted by spermidine in Strombidium parasulcatum, a marine bacteriovorous ciliate potentially applied to live feeds for marine larviculture - Hung-Yun Lin; Bo-Ying Su; Nodali Ndraha; Sheng-Fang Tsai; Kuo-Ping Chiang; Hsin-Yun Liu; Yong-Ting Kang; Wei-Yu Yeh; Che-Chia Tsao; Yi-Min Chen; Hsin-I Hsiao; Han-Jia Lin (Aquaculture, 2023)

Reconstructing post-mid Pleistocene glacial-dammed paleolakes in the Tsangpo Gorge, southeastern Tibetan Plateau - Ping Wang; Huiying Wang; Gang Hu; Yukui Ge; Tao Liu; Bo Xu (Quaternary Science Reviews, 2023)

Metamorphic P–T evolution of the pelitic granulites from the Helanshan in the North China Craton revealed by phase equilibrium modeling and garnet trace elements: Implications for Paleoproterozoic collisional orogenesis - Xiao-Fei Xu; Long-Long Gou; Yun-Peng Dong; Cheng-Li Zhang; Xiao-Ping Long; Yu-Hang Zhao; Feng Zhou; Zhi-Bo Tian (Precambrian Research, 2023)

Numerical investigation on jet penetration capacity of hypervelocity shaped charge in underwater explosion - Liu-Yi Xu; Yu Tian; Xiao-Bo Liu; Shi-Ping Wang (Ocean Engineering, 2023)

Effects of microplastics on the phytoremediation of Cd, Pb, and Zn contaminated soils by Solanum photeinocarpum and Lantana camara - Qiankui Yu; Bo Gao; Ping Wu; Minni Chen; Chuanqian He; Xingfeng Zhang (Environmental Research, 2023)

Recent advances in micro (nano) plastics in the environment: Distribution, health risks, challenges and future prospects - Yan-Bo Ma; Zhuo-Yuan Xie; Naima Hamid; Qi-Ping Tang; Jiao-Yun Deng; Lin Luo; De-Sheng Pei (Aquatic Toxicology, 2023)

AIWW: a new nutrition-screening tool for the oncologic population - Yi-Zhong Ge; Zhen-Ming Fu; Qi Zhang; Meng-Meng Song; Guo-Tian Ruan; Xi Zhang; Xiao-Wei Zhang; Xiang-Rui Li; Kang-Ping Zhang; Meng Tang; Xiao-Yue Liu; Ming Yang; et al. (Science China Life Sciences, 2023)

Constructed a self-powered sensing platform based on nitrogen-doped hollow carbon nanospheres for ultra-sensitive detection and real-time tracking of double markers - Yong-ping Gao; Ke-jing Huang; Bo-ya Wang; Qianyue Xu; Honglei Shuai; Guoqiang Li (Analytica Chimica Acta, 2023)

Fluorescence tracing the degradation process of biodegradable PBAT: Visualization and high sensitivity - Tian-Yuan Liu; Zhi-Chao Zhen; Xiao-Ling Zang; Peng-Yuan Xu; Ge-Xia Wang; Bo Lu; Fei Li; Ping-Li Wang; Dan Huang; Jun-Hui Ji (Journal of Hazardous Materials, 2023)

Heavy metals in fish, rice, and human hair and health risk assessment in Wuhan city, central China - Muhammad Ubaid Ali; Chuan Wang; Yuan Li; Ruolan Li; Shaochen Yang; Li Ding; Lin Feng; Bo Wang; Ping Li; Ming Hung Wong (Environmental Pollution, 2023)

A photothermal cellulose-based material for rapid anti-bacteria and HCHO removal via sequential formation of MnO2 coatings and amine-quinone networks - Xueming Bao; Leilei Wu; Yuanyuan Yu; Bo Xu; Li Cui; Man Zhou; Qiang Wang; Ping Wang (Chemical Engineering Journal, 2023)

Effects of fungal agents and biochar on odor emissions and microbial community dynamics during in-situ treatment of food waste - Shu-Ping Zou; Ru-Sheng Liu; Yu Luo; Chun-Tao Bo; Su-Qin Tang; Ya-Ping Xue; Yu-Guo Zheng (Bioresource Technology, 2023)

Acid-sensing ion channel 1a exacerbates renal ischemia–reperfusion injury through the NF-κB/NLRP3 inflammasome pathway - Yan Yang; Shi Jin; Jian Zhang; Weize Chen; Yufei Lu; Jun Chen; Zhixin Yan; Bo Shen; Yichun Ning; Yiqin Shi; Jing Chen; Jialin Wang; et al. (Journal of Molecular Medicine, 2023)
Ischemia-reperfusion injury (IRI) is the main cause of acute kidney injury (AKI), and there is no effective therapy. Microenvironmental acidification is generally observed in ischemic tissues. Acid-sensing ion channel 1a (ASIC1a) can be activated by a decrease in extracellular pH which mediates neuronal IRI. Our previous study demonstrated that, ASIC1a inhibition alleviates renal IRI. However, the underlying mechanisms have not been fully elucidated. In this study, we determined that renal tubule-specific deletion of ASIC1a in mice (ASIC1a fl/fl /CDH16 cre ) attenuated renal IRI, and reduced the expression of NLRP3, ASC, cleaved-caspase-1, GSDMD-N, and IL-1β. Consistent with these in vivo results, inhibition of ASIC1a by the specific inhibitor PcTx-1 protected HK-2 cells from hypoxia/reoxygenation (H/R) injury, and suppressed H/R-induced NLRP3 inflammasome activation. Mechanistically, the activation of ASIC1a by either IRI or H/R induced the phosphorylation of NF-κB p65, which translocates to the nucleus and promotes the transcription of NLRP3 and pro-IL-1β. Blocking NF-κB by treatment with BAY 11-7082 validated the roles of H/R and acidosis in NLRP3 inflammasome activation. This further confirmed that ASIC1a promotes NLRP3 inflammasome activation, which requires the NF-κB pathway. In conclusion, our study suggests that ASIC1a contributes to renal IRI by affecting the NF-κB/NLRP3 inflammasome pathway. Therefore, ASIC1a may be a potential therapeutic target for AKI. Key messages Knockout of ASIC1a attenuated renal ischemia-reperfusion injury. ASIC1a promoted the NF-κB pathway and NLRP3 inflammasome activation. Inhibition of the NF-κB mitigated the NLRP3 inflammasome activation induced by ASIC1a.

Transcriptomic and physiological analysis of the effect of octanoic acid on Meloidogyne incognita - Jian-Yu Wang; Qiu-Yue Li; Li Ren; Cheng Guo; Jian-Ping Qu; Zheng Gao; Hui-Fang Wang; Qian Zhang; Bo Zhou (Pesticide Biochemistry and Physiology, 2023)

Anti-inflammatory cembrane-based diterpenoids isolated from the octocoral Sinularia querciformis - Te-An Kung; Lo-Yun Chen; Chia-Ying Li; Bo-Rong Peng; Tsong-Long Hwang; Ping-Jyun Sung; Kuei-Hung Lai; Hsu-Ming Chung (Phytochemistry Letters, 2023)

Vancomycin Pretreatment on MPTP-Induced Parkinson’s Disease Mice Exerts Neuroprotection by Suppressing Inflammation Both in Brain and Gut - Chun Cui; Hui Hong; Yun Shi; Yu Zhou; Chen-Meng Qiao; Wei-Jiang Zhao; Li-Ping Zhao; Jian Wu; Wei Quan; Gu-Yu Niu; Yi-Bo Wu; Chao-Sheng Li; et al. (Journal of Neuroimmune Pharmacology, 2023)

The Relationship Between Phytoplankton Diversity and Ecosystem Functioning Changes with Disturbance Regimes in Tropical Reservoirs - Yuping Xu; Lu Wang; Quehui Tang; Luigi Naselli-Flores; Erik Jeppesen; Bo-Ping Han (Ecosystems, 2023)

First report of cowpea mild mottle virus infecting adzuki bean in China - Shuhao Lu; Xulong Wang; Bo Zhao; Jianping Yu; Yongjiang Zhang; Yongqiang Li; Ping Wan (Journal of Plant Pathology, 2023)

Effects of disinfectants, sponge densities, water circulation rates, and vibration frequency on the artificial incubation of redclaw crayfish embryos - Cheng Shun; Jiang Wen-ping; Liu Shi-li; Chi Mei-li; Zheng Jian-bo; Liu Yi-nuo; Hang Xiao-ying; Peng Miao; Li Fei; Wang Dan-li (Aquaculture, 2023)

Metatranscriptomic insights into the microbial electrosynthesis of acetate by Fe2+/Ni2+ addition - Jie Zhang; He Liu; Yan Zhang; Bo Fu; Chao Zhang; Min-Hua Cui; Ping Wu; Zi-Wei Guan (World Journal of Microbiology and Biotechnology, 2023)

Mathematical Model of Two-Phase Spontaneous Imbibition with Dynamic Contact Angle - Lei Zhang; Jingjing Ping; Bo Tang; Lixin Kang; Gloire Imani; Yongfei Yang; Hai Sun; Junjie Zhong; Jun Yao; Dongyan Fan (Transport in Porous Media, 2023)

Synthesis and biological evaluation of esculetin derivatives as potential anti-HBV agents - Zhen Ye; Tong-Shi-Yao Zhao; Shan-Bin Li; Xian-Li Zhou; Qin Luo; Jiang-Ke Qin; Cheng-Qin Liang; Ping Wang; Guang-Bo Ge (Medicinal Chemistry Research, 2023)

Melatonin inhibits senescence-associated melanin pigmentation through the p53-TYR pathway in human primary melanocytes and the skin of C57BL/6 J mice after UVB irradiation - Li-Ping Ma; Meng-Meng Liu; Fang Liu; Bo Sun; Si-Nian Wang; Jie Chen; Hui-Jie Yu; Juan Yan; Mei Tian; Ling Gao; Qing-Jie Liu (Journal of Molecular Medicine, 2023)
UVB exposure accelerates skin aging and pigmentation. Melatonin effectively regulates tyrosinase (TYR) activity and aging. The purpose of this study was to determine the association between premature senescence and pigmentation, and the mechanism of melanin synthesis effected by melatonin. Primary melanocytes were extracted and identified from the male foreskin. To inhibit TYR expression, primary melanocytes were transduced with the lentivirus pLKD-CMV-EGFP-2A-Puro-U6-TYR. The wild-type TYR ( + / + ) and TYR (–/–) or TYR ( + /–) knockout C57BL/6 J mice were used to determine the role of TYR on melanin synthesis in vivo. Results showed that UVB-induced melanin synthesis is dependent on TYR in primary melanocytes and mice. Furthermore, in primary melanocytes pretreated with Nutlin-3 or PFT-α to up or downregulate p53, results showed that premature senescence and melanin synthesis increased in primary melanocytes after UVB irradiation at 80 mJ/cm 2 , and further increased after being treated with Nutlin-3, while significantly decreased with PFT-α. In addition, melatonin inhibited UVB-induced premature senescence associated with inactivation of p53 and phosphorylation of p53 on Ser15 (ser-15), a decrease of melanin synthesis accompanied by reduced TYR expression. Moreover, skin erythema and pigmentation induced by UVB were reduced in the dorsal and ear skin of mice topically pretreated with 2.5% melatonin. These indicate that melatonin inhibits UVB-induced senescence-associated pigmentation via the p53-TYR pathway in primary melanocytes and prevents pigmentation obviously in the dorsal and ear skin of C57BL/6 J mice after UVB irradiation. Key messages P53 links UVB irradiation-induced senescence and senescence-associated pigmentation and regulates TYR in primary melanocytes after UVB irradiation. Melatonin inhibits senescence-associated pigmentation through the p53-TYR pathway in primary melanocytes. Melatonin prevents skin erythema and melanin pigmentation induced by UVB irradiation in the dorsal and ear skin of C57BL/6J mice.

Undescribed phloroglucinol derivatives with antiviral activities from Dryopteris atrata (Wall. Ex Kunze) Ching - Ji-hui Zhang; Jin-lin Chen; Wei-bin Xu; Yi-ping Xia; Hao-yue Zhu; Jing-hao Wang; Yao-lan Li; Guo-cai Wang; Yu-bo Zhang; Neng-hua Chen (Phytochemistry, 2023)

Ag2S nanoparticle promoted charge separation and transfer in g-C3N4 nanosheets for efficient photo and electro chemical performance - Baogang Xu; Bo Wang; Hongyu Zhang; Ping Yang (Journal of Environmental Chemical Engineering, 2023)

Eicosane-based thermo-conductive phase change composite for efficient capture solar energy and using in real-environment as power source - Linhong Li; Maohua Li; Yue Qin; Yapeng Chen; Wen Dai; Zhenbang Zhang; Xiangdong Kong; Ping Gong; Yandong Wang; Rongjie Yang; Bo Wang; Tao Cai; et al. (Chemical Engineering Journal, 2023)

Encapsulating dual-phase WC-W2C nanoparticles into hollow carbon dodecahedrons for all-pH electrocatalytic hydrogen evolution - Shu-Chao Sun; Fei-Xiang Ma; Hao Jiang; Meng-Xin Chen; Ping Xu; Liang Zhen; Bo Song; Cheng-Yan Xu (Chemical Engineering Journal, 2023)

Carbon nanofibers with gas selective layer containing rich and accessible ultramicropores for methane/nitrogen separation - Tian-Yi Li; Yong-Sheng Wang; Meng-Yao Zhang; Bo-Yang Liu; Zhe Zheng; Guang-Ping Hao; An-Hui Lu (Chemical Engineering Journal, 2023)

Dual-pathway optimization on microwave absorption characteristics of core–shell Fe3O4@C microcapsules: Composition regulation on magnetic core and MoS2 nanosheets growth on carbon shell - Yonglei Liu; Chunhua Tian; Fengyuan Wang; Bo Hu; Ping Xu; Xijiang Han; Yunchen Du (Chemical Engineering Journal, 2023)

Antimicrobial Substances and Mechanisms of Lactobacillus rhamnosus against Gardnerella vaginalis - Yu-Ping Huang; Jie-Yan Shi; Si-Chen Luo; Shao-Yan Xu; Jia-Dong Zhang; István Molnár; Qiong-Qiong Yang; Bo-Bo Zhang (Probiotics and Antimicrobial Proteins, 2023)

Effect of CDM3 on co-culture of human-induced pluripotent stem cells with Matrigel-covered polycaprolactone to prepare cardiac patches - Yue Dai; Fan Zhou; Jianwei Zheng; Junsheng Mu; Ping Bo; Bin You (In Vitro Cellular & Developmental Biology - Animal, 2023)

The essentiality of dietary myo-inositol to oriental river prawn (Macrobrachium nipponense): Evidence in growth performance, lipid metabolism and mitochondrial function - Ming-Yang Liu; Miao Sun; Ling Zhang; Ya-Ping Ge; Bo Liu; Xiang-Fei Li (Aquaculture, 2023)

Deciphering the role and mechanism of nano zero-valent iron on medium chain fatty acids production from CO2 via chain elongation in microbial electrosynthesis - Ping Wu; Jie Zhang; Jing Li; Yan Zhang; Bo Fu; Ming-Yi Xu; Yi-Feng Zhang; He Liu (Science of The Total Environment, 2023)

Automatic detection of river capture based on planform pattern and χ-plot of the stream network - Qi-Yuan Ma; An-Bo Li; Ping Wang (Geomorphology, 2023)

Extraction of weak hydrophobic sulforaphane from broccoli by salting-out assisted hydrophobic deep eutectic solvent extraction - Wen-wen Deng; Xue-ping Mei; Zi-jun Cheng; Tian-xiang gan; Xuan Tian; Jiang-nan Hu; Chuan-ru Zang; Bo Sun; Jing Wu; Yin Deng; Reza. A. Ghiladi; George H. Lorimer; et al. (Food Chemistry, 2023)

Mercury migration to surface water from remediated mine waste and impacts of rainfall in a karst area – Evidence from Hg isotopes - Junyao Yan; Ruolan Li; Muhammad Ubaid Ali; Chuan Wang; Bo Wang; Xingang Jin; Mingyu Shao; Ping Li; Leiming Zhang; Xinbin Feng (Water Research, 2023)

Low-intensity pulsed ultrasound promotes proliferation and myelinating genes expression of Schwann cells through NRG1/ErbB signaling pathway - Bo Huang; Yixuan Jiang; Liang Zhang; Bo Yang; Yanjun Guo; Xingmei Yang; Ping Gong (Tissue and Cell, 2023)

Relative stability analysis for robustness design of real-time hybrid simulation - Huimeng Zhou; Xiaoyun Shao; Bo Zhang; Ping Tan; Tao Wang (Soil Dynamics and Earthquake Engineering, 2023)

Combining of C, N and specific Hg stable isotopes to track bioaccumulation of monomethylmercury in coastal and freshwater seafood - Shaochen Yang; Ping Li; Jinling Liu; Muhammad Ubaid Ali; Li Ding; Bo Wang (Food Chemistry, 2023)

Origin of clay in granite intrusive contact zone and its influence on tunnel deformation and instability - Guo-Hua Zhang; Bo-Wen Zhang; Fei Tan; Zhong-Hou Liu; Jun-Peng Zou; Zhong-Zhi Xie; Jin-Quan Wu; Zhi-Ping Lin; Zhan-Rong Zhang (Engineering Geology, 2023)

Efficient fabrication of desert beetle-inspired micro/nano-structures on polypropylene/graphene surface with hybrid wettability, chemical tolerance, and passive anti-icing for quantitative fog harvesting - Wei-long Zhou; Ting Wu; Yu Du; Xiao-hu Zhang; Xin-chang Chen; Jin-bo Li; Heng Xie; Jin-ping Qu (Chemical Engineering Journal, 2023)

Cholesterol homeostasis regulated by ABCA1 is critical for retinal ganglion cell survival - Jialiang Yang; Yuhong Chen; Tongdan Zou; Bai Xue; Fang Yang; Xiangzhou Wang; Yibo Huo; Boyun Yan; Yuxia Xu; Shiyu He; Yi Yin; Jing Wang; et al. (Science China Life Sciences, 2023)

Stabilized effects of L-S cement-mixed batter pile composite foundation for existed warm frozen soil subgrade - Gao-chen Sun; Gang Yao; Jian-ming Zhang; Bo Li; Jun-qi Li; Wei-ping Lian; Yi Wei (Journal of Mountain Science, 2023)

Bacterial communities exhibit apparent phosphate concentration-related patterns of community composition, alpha diversity, and phylogenetic structure in the subtropical Daya Bay - Ye Chen; Guibin Ma; Chuangfeng Wu; Yuyang Peng; Xingyu Song; Qinglong L. Wu; Bo-Ping Han; Lijuan Ren (Frontiers in Marine Science, 2023)
Increasing anthropogenic activities have caused serious environmental problems and undesirable ecological impacts on bay ecosystems. However, much remains to be learned regarding marine bacterial community assembly and its underlying mechanisms under intensive anthropogenic activities in subtropical bays. In this study, we used the community assembly theory to analyze bacterial community distributions in the subtropical Daya Bay, where the habitats are subject to serious thermal discharge and excessive nutrient load. We found the community assembly of bacterial in the Daya Bay was dominantly shaped by environmental factor of seawater phosphate, followed by temperature, and silicate. High phosphate concentration significantly increased the relative abundance of Actinobacteria , Cyanobacteria , Planctomycetes , and Gammaprotecteria , but reduced the relative abundance of Bacteroidetes and Alphaproteobacteria . Moreover, higher phosphate concentration was found significantly and positively correlated with higher bacterial alpha diversity. Compared with stochastic processes, we found higher phosphate concentration imposed stronger deterministic processes (primarily homogeneous selection) in structuring bacterial community assembly in the subtropical Daya bay, and bacterial communities tended to be higher phylogenetically clustered in higher phosphate-concentration habitats. In summary, we proposed that phosphate is a major environmental determinant in the subtropical Daya Bay and influenced the relative importance of deterministic and stochastic processes in bacterial community assembly.

Effects of light color, photoperiod, and growth-related gene interference or overexpression on the survival, growth, or physiological and biochemical indices of red claw crayfish juveniles - Shun Cheng; Jian-bo Zheng; Yong-yi Jia; Mei-li Chi; Wen-ping Jiang; Shi-li Liu; Fei Li; Yi-nuo Liu; Zhi-min Gu; Dan-li Wang (Aquaculture, 2023)

Assessment of contaminants associated with gold-standard ancient DNA protocols - Bo Miao; Yalin Liu; Ruowei Yang; Xiaotian Feng; Feng Liu; Peng Cao; Qingyan Dai; Wanjing Ping; Yichen Liu; Qiaomei Fu (Science Bulletin, 2023)

Corrigendum to “Comparative efficacy of omega-3 polyunsaturated fatty acids on major cardiovascular events: A network meta-analysis of randomized controlled trials” [Progress in Lipid Research. 2022 Oct 28;88:101196. doi: 10.1016/j.plipres.2022.101196] - Bo Yang; Ping-Tao Tseng; Xiang Hu; Bing-Yan Zeng; Jane Pei-Chen Chang; Yang Liu; Wei-Jie Chu; Shuang-Shuang Zhang; Zhi-Liang Zhou; Chih-Sheng Chu; Cheng-Ho Chang; Yu-Kang Tu; et al. (Progress in Lipid Research, 2023)

Response of ecosystem gross primary productivity to drought in northern China based on multi-source remote sensing data - Ting Zhang; Junzhi Zhou; Ping Yu; Jianzhu Li; Yanfu Kang; Bo Zhang (Journal of Hydrology, 2023)

3-MCPD exposure enhances ovarian fibrosis and reduces oocyte quality in mice - Quan-Kuo He; Yan-Ping Li; Zhi-Ran Xu; Wen-Bo Wei; Feng-Xin Qiao; Ming-Xin Sun; Yue-Cen Liu; Yan-Zhu Chen; Hai-Long Wang; Zhong-Quan Qi; Yu Liu (Environmental Pollution, 2023)

Photo-rechargeable all-solid-state lithium − sulfur batteries based on perovskite indoor photovoltaic modules - Tian-Tian Li; Yuan-Bo Yang; Bo-Sheng Zhao; Yue Wu; Xiao-Wen Wu; Peng Chen; Xue-Ping Gao (Chemical Engineering Journal, 2023)

Ethynyl functionalized porphyrin complex as a new cathode for organic alkali metal batteries with excellent cycling stability - Ye Sun; Fangfang He; Xiuhui Huang; Bo Ren; Jinfeng Peng; Di Chen; Xinyue Hu; Xiujuan Sun; Ping Gao (Chemical Engineering Journal, 2023)

Corrigendum to “CD44-targeted hyaluronic acid-curcumin prodrug protects renal tubular epithelial cell survival from oxidative stress damage” [Carbohydrate Polymers 193 (2018) 268–280] - Jing-Bo Hu; Shu-Juan Li; Xu-Qi Kang; Jing Qi; Jia-Hui Wu; Xiao-Juan Wang; Xiao-Ling Xu; Xiao-Ying Ying; Sai-Ping Jiang; Jian You; Yong-Zhong Du (Carbohydrate Polymers, 2023)

The self-powered electrochemical biosensing platform with multi-amplification strategy for ultrasensitive detection of microRNA-155 - Yong-ping Gao; Ke-jing Huang; Fu-ting Wang; Yang-yang Hou; Lu-di Zhao; Bo-ya Wang; Jing Xu; Honglei Shuai; Guoqiang Li (Analytica Chimica Acta, 2023)

Molecular characterization of a novel non-segmented double-stranded RNA mycovirus isolated from Penicillium citrinum strain RCEF7060 - Yipeng Huang; Ping Wang; Hao Wu; Cheng Yang; Bo Huang (Archives of Virology, 2023)

Molecular characterization of two novel totiviruses coinfecting the basal fungus Conidiobolus adiaeretus - Najie Shi; Tian Xie; Guogen Yang; Ping Wang; Bo Huang (Archives of Virology, 2023)

A novel polymycovirus infecting the entomopathogenic fungus Metarhizium brunneum - Lili He; Ping Wang; Guogen Yang; Xiaolin Chen; Bo Huang (Archives of Virology, 2023)

Improving the CFSv2 prediction of the Indian Ocean Dipole based on a physical‐empirical model and a deep‐learning approach - Ping Chen; Bo Sun; Huijun Wang; Lianmei Yang (International Journal of Climatology, 2022)
Despite significant advances in seasonal climate forecasts, the reliability of both dynamical and empirical models for the Indian Ocean Dipole (IOD) prediction is still limited to a lead time of one season or less. In this study, the skill of the NCEP Climate Forecast System version 2 (CFSv2) for the IOD prediction during the period 1982–2014 is evaluated. The results indicate that the model performance for the IOD prediction is the worst in spring among the four seasons, which is manifested in the fact that a skilful prediction of spring IOD event is limited to a lead time of only about 1–2 months. To improve the forecast of spring IOD events, a physical‐empirical (PE) model and a convolutional neural network (CNN) model are established in the present study. The IOD in April–May–June (AMJ) is taken as the predictand, and the CFSv2‐predicted sea surface height (SSH) in AMJ and the observed Laptev sea ice in the preceding December are used as the two predictors. The original CFSv2‐predicted IOD time series has an insignificant correlation with the observed IOD time series with a temporal correlation coefficient (TCC) of 0.03; the PE model (CNN model) can largely improve the IOD prediction with a TCC of 0.74 (0.77) between the PE‐model‐predicted (CNN‐model‐predicted) IOD and the observed IOD during AMJ. Thus, the PE model and the CNN model developed in the present study can be applied to improve the IOD predictions from numerical models in the future.

A new non-invasive tagging method for leopard coral grouper (Plectropomus leopardus) using deep convolutional neural networks with PDE-based image decomposition - Yangfan Wang; Chun Xin; Boyu Zhu; Mengqiu Wang; Tong Wang; Ping Ni; Siqi Song; Mengran Liu; Bo Wang; Zhenmin Bao; Jingjie Hu (Frontiers in Marine Science, 2022)
External tagging methods can aid in the research of leopard coral grouper ( Plectropomus leopardus ) in terms of its spatio-temporal behavior at population and individual scales. However, due to the strong exclusion ability and the damage to the body wall of P. leopardus , the retention rate of traditional invasive tagging methods is low. To develop a non-invasive identification method for P. leopardus , we adopted a multiscale image processing method based on matched filters with Gaussian kernels and partial differential equation (PDE) multiscale hierarchical decomposition with the deep convolutional neural network (CNN) models VGG19 and ResNet50 to extract shape and texture image features of individuals. Then based on image features, we used three classifiers Random forest (RF), support vector machine (SVM), and multilayer perceptron (MLP)) for individual recognition on sequential images of P. leopardus captured for 50 days. The PDE, ResNet50 and MLP combination obtained a maximum accuracy of 0.985 ± 0.045 on the test set. For individual temporal tracking recognition, feature extraction and model training were performed using images taken in 1-20 days. The classifier could achieve an accuracy of 0.960 ± 0.049 on the test set consisting of images collected in the periods of 20-50 days. The results show that CNNs with the PDE decomposition can effectively and accurately identify P. leopardus .

Environmental impact of typical zinc smelting that implements solid waste collaborative utilization in China - Wei-Ning Liu; Yao Shi; Chen-Mu Zhang; Lang-Ming Liu; Hui-Quan Li; Bin Lu; Yuan-Bo Xie; Cai-Bei Zhuang; Tian-You Sun; Wei-Ping Liu; Xue Guan; Ying-Yan Hu (The International Journal of Life Cycle Assessment, 2022)

Direct Tensile Test and FDEM Numerical Study on Anisotropic Tensile Strength of Kangding Slate - Ping Liu; Quansheng Liu; Xing Huang; Mingming Hu; Yin Bo; Dong Yuan; Xianqi Xie (Rock Mechanics and Rock Engineering, 2022)

Characterization of a novel victorivirus from Nigrospora chinensis, a fungus isolated from tobacco - Jie Zhong; Wen Wen Sui; Ping Li; Qian Jun Tang; Tian Bo Liu; Yan Song Xiao (Archives of Virology, 2022)

Proteomic analysis and identification reveal the anti-inflammatory mechanism of clofazimine on lipopolysaccharide-induced acute lung injury in mice - Bo Yang; Zhan Gao; Qi-Shuang Li; Xiang-Ye Zhang; Lan Song; Yi-Ni Wang; Xin-Yue Wang; Lin-Lin Ji; Hong-Liang Xu; Hui Xie; Fu-Kai Feng; Xiao-Ping Li; et al. (Inflammation Research, 2022)

Genetic diversity, lineage divergence, and demography of Diaphanosoma dubium (Crustacea: Cladocera) on Hainan Island, China - Ping Liu; Xiaoli Zhang; Qi Huang; Eric Zeus C. Rizo; Henri J. Dumont; Bo-Ping Han (Hydrobiologia, 2022)

A Variational Bayesian-Based Simultaneous Localization and Mapping Method for Autonomous Underwater Vehicle Navigation - Pengcheng Mu; Xin Zhang; Ping Qin; Bo He (Journal of Marine Science and Engineering, 2022)
Simultaneous Localization and Mapping (SLAM) is a well-known solution for mapping and realizing autonomous navigation of an Autonomous Underwater Vehicle (AUV) in unknown underwater environments. However, the inaccurate time-varying observation noise will cause filtering divergence and reduce the accuracy of localization and feature estimation. In this paper, VB-AUFastSLAM based on the unscented-FastSLAM (UFastSLAM) and the Variational Bayesian (VB) is proposed. The UFastSLAM combines unscented particle filter (UPF) and unscented Kalman filter (UKF) to estimate the AUV poses and features. In addition, to resist the unknown time-varying observation noise, the method of Variational Bayesian learning is introduced into the SLAM framework. Firstly, the VB method is used to estimate the joint posterior probability of the AUV path and observation noise. The Inverse-Gamma distribution is used to model the observation noise and real-time noise parameters estimation is performed to improve the AUV localization accuracy. Secondly, VB is reused to estimate the noise parameters in the feature update stage to enhance the performance of the feature estimation. The proposed algorithms are first validated in an open-source simulation environment. Then, an AUV SLAM system based on the Inertial Navigation System (INS), Doppler Velocity Log (DVL), and single-beam Sonar are also built to verify the effectiveness of the proposed algorithms in the marine environment. The accuracy of the proposed methods can reach 0.742% and 0.776% of the range, respectively, which is much better than 1.825% and 1.397% of the traditional methods.

TGF-β1/Smad3 upregulates UCA1 to promote liver fibrosis through DKK1 and miR18a - Zhangshuo Yang; Hao Zhang; Maohui Yin; Zhixiang Cheng; Ping Jiang; Maohui Feng; Zhisu Liu; Bo Liao (Journal of Molecular Medicine, 2022)

Molecular characterization of a novel double-stranded RNA virus infecting the entomopathogenic fungus Metarhizium brunneum - Ping Wang; Guogen Yang; Najie Shi; Bo Huang (Archives of Microbiology, 2022)

Exploring the R-ISS stage-specific regular networks in the progression of multiple myeloma at single-cell resolution - Ling Zhong; Xiao Yang; Yu Zhou; Jialing Xiao; Huan Li; Jiang Tao; Qian Xi; Chen Chu; Chenglong Li; Xi Yang; Chen Yang; Yi Zhang; et al. (Science China Life Sciences, 2022)

Novel circularRNA circ-0047078 promotes pancreatic ductal adenocarcinoma progression through mircoRNA miR-11181— Chemokine (C-X-C motif) Ligand 12/Melanoma Cell Adhesion Molecule/Regulator of G-protein signaling 16 pathway - Yuzhou Wang; Hangwei Fu; Yan Jiang; Bo Zhou; Ping Chen (Molecular Biology Reports, 2022)

Impacts of Mercury Exposure Levels and Sources on the Demethylation of Methylmercury Through Human Gut Microbiota - Xian-Feng Yang; Shao-Chen Yang; Fu-Li Wen; Lin Feng; Bo Meng; Hai-Yan Hu; Bao-Lin Wang; Jun Li; Alexandre J. Poulain; Ping Li (Bulletin of Environmental Contamination and Toxicology, 2022)

Transport process and mechanism of the Hongshiyan rock avalanche triggered by the 2014 Ludian earthquake, China - Shi-lin Zhang; Yue-ping Yin; Hai-bo Li; Wen-pei Wang; Jia-wen Zhou (Landslides, 2022)

Mapping the spatial distribution of fossil geothermal manifestations and assessment of geothermal potential of the Tangyin rift, Southeast of Taihang Mountain in China - Joshua Mahwa; Da-jiang Li; Jian-hua Ping; Wei Leng; Jia-bo Tang; Dong-yun Shao (Journal of Mountain Science, 2022)
The spatial prediction of geothermal sites along the southeast side of Taihang Mountain in the Tangyin rift is a critical goal in the development of renewable energy resources in cities such as Hebi in Henan province, which has significant potential for geothermal energy production due to the existence of deep faults and Cenozoic volcano. The study aimed to delineate areas with high geothermal manifestations for detailed geothermal exploration and well-test drilling. To define favorable zones for geothermal potentiality, multi-source datasets were chosen to generate evidence thematic layers that demonstrate the distribution of geothermal anomalies such as geologic maps, structural maps, Land Surface Temperature maps (LST), and hydrothermal mineral alterations maps. The remote sensing and Geographical Information System (GIS) approaches were integrated to map fossil geothermal manifestations and appraise the promising geothermal zones from Landsat 8 OLI/TIRS and Advanced Spaceborne Thermal Emission and Reflection Radiometer-Digital Elevation Model (ASTER-DEM) dataset using the Analytic Hierarchy Process (AHP), which is one of the Mult-criteria Decision Making methods. Results show LST values ranging from 22.6°C to 45.4°C, with the highest values found along the faults and volcanic areas. The hydrothermal alteration minerals discriminated from band ratios of 4/2, 6/5, and 6/7 for iron oxide, ferrous minerals, and clays reveal the presence of high amount of montmorillonite and illite minerals along the faults and volcanoes which are related to hot fluid circulation from subsurface. Structural analysis shows that the major structural trend follows the NNE Tangdong and Tangxi faults, with high density on the west side of the Tangxi fault where there is good exposure of outcrop but less fault density on the east side due to sedimentation in a low land which may conceal geological structures. Lastly, all the thematic layers of geothermal factors were reclassified, ranked, and integrated by the weight overlay logic model based on the influence of geothermal suitability to map potential areas for geothermal resources whereby 5 zones were obtained ranging from very poor to very good. The promising potential sites are mostly found along the highly deep structures of the major Tangxi fault crosscutting the permeable lithology of carbonate rocks and around the Hebi volcanoes. The distribution of hot springs and geothermal wells of the Hebi field were correlated and verified against the potential geothermal anomalies map. The overall integrated method proposes an advanced technique for designing the Tangyin rift’s exploration plan and development actions for geothermal resources utilization, which can be used for exploration of any unveiling geothermal potential sites.

Hyperparameter Optimization for the LSTM Method of AUV Model Identification Based on Q-Learning - Dianrui Wang; Junhe Wan; Yue Shen; Ping Qin; Bo He (Journal of Marine Science and Engineering, 2022)
An accurate mathematical model is a basis for controlling and estimating the state of an Autonomous underwater vehicle (AUV) system, so how to improve its accuracy is a fundamental problem in the field of automatic control. However, AUV systems are complex, uncertain, and highly non-linear, and it is not easy to obtain through traditional modeling methods. We fit an accurate dynamic AUV model in this study using the long short-term memory (LSTM) neural network approach. As hyper-parameter values have a significant impact on LSTM performance, it is important to select the optimal combination of hyper-parameters. The present research uses the improved Q-learning reinforcement learning algorithm to achieve this aim by improving its recognition accuracy on the verification dataset. To improve the efficiency of action exploration, we improve the Q-learning algorithm and choose the optimal initial state according to the Q table in each round of learning. It can effectively avoid the ineffective exploration of the reinforcement learning agent between the poor-performing hyperparameter combinations. Finally, the experiments based on simulated or actual trial data demonstrate that the proposed model identification method can effectively predict kinematic motion data, and more importantly, the modified Q-Learning approach can optimize the network hyperparameters in the LSTM.

Chemometric-Guided Exploration of Marine Anti-Neurofibroma Leads - Lo-Yun Chen; Bo-Rong Peng; Guan-Yi Lai; Hao-Jui Weng; Mohamed El-Shazly; Chun-Han Su; Jui-Hsin Su; Ping-Jyun Sung; Chung-Ping Liao; Kuei-Hung Lai (Frontiers in Marine Science, 2022)
In-depth analysis of metabolomics diversity of marine species through advanced mass spectrometric analysis is one of the most promising new tools for the development of marine drugs against mild and life-threatening diseases. Neurofibromas are a common type of tumor in the peripheral nervous system. Currently, there are very limited treatment options for neurofibromas. In our course of exploring potential therapeutic agents for neurofibroma treatment, the multi-informative molecular networking (MIMN) approach was proposed. The MIMNs of the Lendenfeldia sp. sponge extract and sub-fractions were established according to their inhibitory activity against several inflammatory chemokines (CCL3, CCL4, CCL5, CXCL1, CXCL8, and CXCL10) in neurofibroma cell line hTERT-NF1-ipNF95.11b-C (CRL-3390). The visualized MIMN revealed the anti-inflammatory potential of scalarane-enriched fractions, and the follow-up annotation and isolation led to the identification of a scalarane, 24-methyl-12,24,25-trioxoscalar-16-en-22-oic acid (2). Our results revealed that the most abundant scalarane (2) dominated the anti-chemokine effect of Lendenfeldia sp. extract together with other scalaranes, indicating the potential application of sponge-derived scalaranes to be developed as therapeutic agents for neurofibromas.

Cadinane-type sesquiterpenes with potential anti-inflammatory and anti-HIV activities from the stems and leaves of Mappianthus iodoides - Yan-Ping Liu; Xiao-Mei Yu; Ze-Hua Qiao; Bo Jiang; Lan Xie; Hao-Xuan Tang; Xiao Liang; Yan-Hui Fu (Natural Product Research, 2022)

Sandstorms cause shrinkage of Haloxylon ammodendron shrubs and limit their self-renewal - Sheng-bo Shi; Dang-wei Zhou; Fang-lin Wang; Rui Shi; Tao Sun; Tian-cai Li; Jia-lin Ma; Xiang Wan; Jian-ping Ma; Jing-nian Tang (Theoretical and Experimental Plant Physiology, 2022)
Haloxylon ammodendron is an excellent windproof and sand-fixing species whose shrubs are widely cultivated in arid desert areas of northwest China but are now at risk of degradation and shrinkage. Using the chlorophyll fluorescence image analysis technique, the response of photosystem II (PSII) photochemical efficiency and non-photochemical quenching capacity to sediment-carrying wind and sand-free wind (both 12 m s −1 ) lasting for 10, 20, and 40 min were studied with seedlings in a wind tunnel. The results indicated that the sand-free wind had little influence on the maximum quantum efficiency of PSII photochemistry, F v / F m , which was approximately 0.80 on average; however, the F v / F m decreased over exposure time in the sediment-carrying wind group, with values smaller than those in the wind-only group. The non-photochemical quenching was sensitive to wind erosion, and sediment-carrying wind could aggravate the reduction in non-photochemical quenching ( NPQ ). Except for the 10 min duration, the maximum quantum efficiency of PSII photochemistry after dark recovery for 15 min, F v r / F m r , was lower in seedlings exposed to sediment-carrying wind than in those in the wind-only group. Compared to wind-only, wind-blown sand led to a water imbalance and withering in seedlings, causing the concentration of photosynthetic pigments (when based on the fresh mass of green branches) to not decrease. With a longer exposure time to sediment-carrying wind, both the probability and extent of lignified spots occurring increased in green assimilative branches. Our results demonstrated that sediment-carrying wind at 12 m s −1 lasting for 20 min or more could cause irreversible damage to the photosynthetic apparatus of H. ammodendron seedlings. Therefore, frequent and strong sandstorms are the main disturbance factors leading to shrinkage of shrubs and limiting their self-renewal.

miR171 modulates induction of somatic embryogenesis in citrus callus - Qiao-Fang Shi; Jian-Mei Long; Zhao-Ping Yin; Nan Jiang; Meng-Qi Feng; Bo Zheng; Wen-Wu Guo; Xiao-Meng Wu (Plant Cell Reports, 2022)

Bedside Diagnosis for Disseminated Deep Dermatophytosis: a Case Series Study - Xiu-Jiao Xia; Hong Shen; Hui-Lin Zhi; Yan Zhong; Bo Sang; Wen-Wen Lv; Qiu-Ping Li; Ze-Hu Liu (Mycopathologia, 2022)

Astragalus Polysaccharides Reduce High-glucose-induced Rat Aortic Endothelial Cell Senescence and Inflammasome Activation by Modulating the Mitochondrial Na+/Ca2+ Exchanger - Xin-Yu Miao; Xiao-Xiao Zhu; Zhao-Yan Gu; Bo Fu; Shao-Yuan Cui; Yuan Zu; Ling-Jun Rong; Fan Hu; Xiang-Mei Chen; Yan-Ping Gong; Chun-Lin Li (Cell Biochemistry and Biophysics, 2022)

Investigation on long-term progressive deformation of engineering slope based on comprehensive monitoring - Shi-shu Zhang; Song-feng Guo; Sheng-wen Qi; Feng-jiao Tang; Jin-shan Hu; Xiao-ping Zhao; Cong-yan Ran; Xin Wang; Yu Zou; Xiao-lin Huang; Bo-wen Zheng; Ning Liang (Journal of Mountain Science, 2022)

Human motor learning is robust to control-dependent noise - Bo Pang; Leilei Cui; Zhong-Ping Jiang (Biological Cybernetics, 2022)

Molecular characterization of a novel alternavirus infecting the entomopathogenic fungus Cordyceps chanhua - Yuxiang Zhang; Najie Shi; Ping Wang; Qiuyan Zhu; Guogen Yang; Bo Huang (Archives of Virology, 2022)

Episodic Neoproterozoic extension-related magmatism in the Altyn Tagh, NW China: implications for extension and breakup processes of Rodinia supercontinent - Jiang-bo Hao; Chao Wang; Ji-heng Zhang; Liang Liu; Yong-sheng Gai; Hang Li; Zun-pu Yu; Joseph G Meert; Xiao-ping Long; Xiao-kui Sun; Shuai Zhang (International Geology Review, 2022)

Approximate analytical solution for seepage field of drained tunnel in vertically stratified phreatic aquifer - Wei Meng; Chuan He; Fang-yin Wu; Wen-bo Yang; Hao Kou; Zi-han Zhou; De-ping Guo; Hai-long Meng (Journal of Mountain Science, 2022)

Anterior Cingulate Cortex Mediates Hyperalgesia and Anxiety Induced by Chronic Pancreatitis in Rats - Dan Ren; Jia-Ni Li; Xin-Tong Qiu; Fa-Ping Wan; Zhen-Yu Wu; Bo-Yuan Fan; Ming-Ming Zhang; Tao Chen; Hui Li; Yang Bai; Yun-Qing Li (Neuroscience Bulletin, 2022)
Central sensitization is essential in maintaining chronic pain induced by chronic pancreatitis (CP), but cortical modulation of painful CP remains elusive. Here, we examined the role of the anterior cingulate cortex (ACC) in the pathogenesis of abdominal hyperalgesia in a rat model of CP induced by intraductal administration of trinitrobenzene sulfonic acid (TNBS). TNBS treatment resulted in long-term abdominal hyperalgesia and anxiety in rats. Morphological data indicated that painful CP induced a significant increase in FOS-expressing neurons in the nucleus tractus solitarii (NTS) and ACC, and some FOS-expressing neurons in the NTS projected to the ACC. In addition, a larger portion of ascending fibers from the NTS innervated pyramidal neurons, the neural subpopulation primarily expressing FOS under the condition of painful CP, rather than GABAergic neurons within the ACC. CP rats showed increased expression of vesicular glutamate transporter 1, and increased membrane trafficking and phosphorylation of the N -methyl-D-aspartate receptor (NMDAR) subunit NR2B and the α-amino-3-hydroxy-5-methyl-4-isoxazole propionic acid receptor (AMPAR) subunit GluR1 within the ACC. Microinjection of NMDAR and AMPAR antagonists into the ACC to block excitatory synaptic transmission significantly attenuated abdominal hyperalgesia in CP rats, which was similar to the analgesic effect of endomorphins injected into the ACC. Specifically inhibiting the excitability of ACC pyramidal cells via chemogenetics reduced both hyperalgesia and comorbid anxiety, whereas activating these neurons via optogenetics failed to aggravate hyperalgesia and anxiety in CP rats. Taken together, these findings provide neurocircuit, biochemical, and behavioral evidence for involvement of the ACC in hyperalgesia and anxiety in CP rats, as well as novel insights into the cortical modulation of painful CP, and highlights the ACC as a potential target for neuromodulatory interventions in the treatment of painful CP.

Air-Sea Latent Heat Flux Anomalies Induced by Oceanic Submesoscale Processes: An Observational Case Study - Xiangzhou Song; Xuehan Xie; Bo Qiu; Haijin Cao; Shang-Ping Xie; Zhiqiang Chen; Weidong Yu (Frontiers in Marine Science, 2022)
The classical theory predicts that a geostrophically balanced mesoscale eddy can cause a sea surface temperature (SST) anomaly related to Ekman pumping. Previous studies show that an eddy-induced SST anomaly can result in a sea surface latent heat flux (LH) anomaly at a maximum magnitude of ∼ O (10) Wm –2 , decaying radially outward from the center to the margin. In this study, we investigate the LH anomalies associated with submesoscale processes within a cyclonic eddy for the first time using recent satellite-ship-coordinated air-sea observations in the South China Sea. Unbalanced submesoscale features can be identified as submesoscale SST fronts. Along the ship track, the SST strikingly decreases by 0.5°C within a horizontal distance of ∼1.5 km and increases quickly by 0.9°C with a spatial interval of ∼3.6 km. The along-track SST is decomposed into three parts: large-scale south-north fronts and anomalies induced by mesoscale and submesoscale motions. Our analysis shows that the amplitude of the LH anomaly induced by the mesoscale SST anomaly is 12.3 Wm –2 , while it is 14.3 Wm –2 by unbalanced submesoscale motions. The mean (maximum) spatial gradient of the submesoscale LH anomalies is 1.7 (75.7) Wm –2 km –1 , which is approximately 1.5 times those (1.2 and 59.9 Wm –2 km –1 ) in association with mesoscale eddies. The spectra of LH and SST anomalies show similar peaks at ∼15 km before sloping down with a power law between k –2 and k –3 , indicating the underlying relationship between the LH variance and submesoscale processes.

Cancer metabolism and tumor microenvironment: fostering each other? - Yiyuan Yuan; Huimin Li; Wang Pu; Leilei Chen; Dong Guo; Hongfei Jiang; Bo He; Siyuan Qin; Kui Wang; Na Li; Jingwei Feng; Jing Wen; et al. (Science China Life Sciences, 2022)

Design and synthesis of caffeic acid derivatives and evaluation of their inhibitory activity against Pseudomonas aeruginosa - Yun-feng Zeng; Ya-lun Su; Wei-liang Liu; Hong-geng Chen; Shao-gao Zeng; Hai-bo Zhou; Wei-min Chen; Jun-xia Zheng; Ping-hua Sun (Medicinal Chemistry Research, 2022)

A community effort to assess and improve computerized interpretation of 12-lead resting electrocardiogram - Zijian Ding; Guijin Wang; Huazhong Yang; Ping Zhang; Dapeng Fu; Zhen Yang; Xinkang Wang; Xia Wang; Zhourui Xia; Chiming Zhang; Wenjie Cai; Binhang Yuan; et al. (Medical & Biological Engineering & Computing, 2022)
Computerized interpretation of electrocardiogram plays an important role in daily cardiovascular healthcare. However, inaccurate interpretations lead to misdiagnoses and delay proper treatments. In this work, we built a high-quality Chinese 12-lead resting electrocardiogram dataset with 15,357 records, and called for a community effort to improve the performances of CIE through the China ECG AI Contest 2019. This dataset covers most types of ECG interpretations, including the normal type, 8 common abnormal types, and the other type which includes both uncommon abnormal and noise signals. Based on the Contest, we systematically assessed and analyzed a set of top-performing methods, most of which are deep neural networks, with both their commonalities and characteristics. This study establishes the benchmarks for computerized interpretation of 12-lead resting electrocardiogram and provides insights for the development of new methods.

Correction to: Toward a phylogeny and biogeography of Diaphanosoma (Crustacea: Cladocera) - Henri J. Dumont; Bo-Ping Han; Fei Fei Guo; Hua Chen; Dan Cheng; Ping Liu; Lei Xu; La-Orsri Sanoamuang; Arnola C. Rietzler; Shaolin Xu; Andy Vierstraete; Manuel Elias-Gutierrez (Aquatic Ecology, 2021)

Toward a phylogeny and biogeography of Diaphanosoma (Crustacea: Cladocera) - Henri J. Dumont; Bo-Ping Han; Fei Fei Guo; Hua Chen; Dan Cheng; Ping Liu; Lei Xu; La-Orsri Sanoamuang; Arnola C. Rietzler; Shaolin Xu; Andy Vierstraete; Manuel Elias-Gutierrez (Aquatic Ecology, 2021)

Development of microsatellite markers for Diaphanosoma dubium (Crustacea, Cladocera) and application to seasonal population dynamics - Ping Liu; Shao-Lin Xu; Jian Liao; Henri J. Dumont; Bo-Ping Han (Aquatic Ecology, 2021)

Stress response mechanisms and description of three novel species Shewanella avicenniae sp. nov., Shewanella sedimentimangrovi sp. nov. and Shewanella yunxiaonensis sp. nov., isolated from mangrove ecosystem - Guo-Hong Liu; Qi Zhang; Manik Prabhu Narsing Rao; Shang Yang; Rong Tang; Huai Shi; Jie-Ping Wang; Guan-Min Huang; Bo Liu; Shun-Gui Zhou; Wen-Jun Li (Antonie van Leeuwenhoek, 2021)

Cytotoxic triterpenoid glycosides from leaves of Cyclocarya paliurus - Hui-Hui Sun; Wen-Yan Lv; Jie Tan; Yu-Cheng Tang; Hui Zhu; Jian-Bo Qu; Jing Li; Jian-Ping Wu; Xi-Wen Chang; Zhi-Chun Yang; Wen-Xuan Wang; Zu-Hui Chen; et al. (Natural Product Research, 2021)

Molecular characterization of two dsRNAs that could correspond to the genome of a new mycovirus that infects the entomopathogenic fungus Beauveria bassiana - Najie Shi; Fei Hu; Ping Wang; Yuxiang Zhang; Qiuyan Zhu; Guogen Yang; Bo Huang (Archives of Virology, 2021)

Problem-solving deficits in methcathinone use disorder - Hang-Bin Zhang; Di Zhao; Yu-Ping Liu; Li-Xun Wang; Bo Yang; Ti-Fei Yuan (Psychopharmacology, 2021)

Biogas Production and Microbial Communities in the Anaerobic Digestion of Sewage Sludge Under Hydrothermal Pretreatment with Air and a Catalyst - Van Toi Pham; Pei-Hsun Wu; Chung-Yu Guan; Chia-Chi Chang; Bo-Liang Liu; Ching-Yuan Chang; Chang-Ping Yu (BioEnergy Research, 2021)

Spatiotemporal characteristics and trend assessment of Ms ≥ 5.6 earthquakes in the Tianshan area of China based on co-occurrence analysis and commensurability - Jia Wan; Jun-Ping Yan; Zi-Qiang Liu; Xiao-Meng Wang; Yu-Feng Zhang; Cheng-Bo Wang (Applied Geophysics, 2021)

Microbial characteristics response to the soil quality of newly created farmland on the Loess Plateau - Chen Xu; Yi-ping Chen; Cui-cui Su; Ji-fu Ma; Jun-hua Wu; Kai-bo Wang; Yi Wang; Yao Jiang (Environmental Science and Pollution Research, 2021)

Correction to: TIP60 recruits SUV39H1 to chromatin to maintain heterochromatin genome stability and resist hydrogen peroxide-induced cytotoxicity - Bo Tu; Yantao Bao; Ming Tang; Qian Zhu; Xiaopeng Lu; Hui Wang; Tianyun Hou; Ying Zhao; Ping Zhang; Wei-Guo Zhu (Genome Instability & Disease, 2021)

Interactive effect of water level and flushing rate on population dynamics of a harmful cyanobacterial species: Raphidiopsis raciborskii - Quehui Tang; Lamei Lei; Li Zhao; Jiguang Gu; Lijuan Xiao; Bo-Ping Han (Ecotoxicology, 2021)

Ziziphus jujuba Mill., a plant used as medicinal food: a review of its phytochemistry, pharmacology, quality control and future research - Shi-Jun Liu; Yan-Ping Lv; Zhi-Shu Tang; Yu Zhang; Hong-Bo Xu; Dong-Bo Zhang; Chun-Li Cui; Hong-Bo Liu; Huan-Huan Sun; Zhong-Xing Song; Si-Min Wei (Phytochemistry Reviews, 2021)

Decreased Plasma Pituitary Adenylate Cyclase Activating Polypeptide (PACAP) Levels are Linked with Disease Severity in Patients with Liver Cirrhosis - Lian-Ying Yang; Ji-Ping Hou; En-Kun Han; Gang Qiao; Li-Bin Liu; Xue-Bo Men (International Journal of Peptide Research and Therapeutics, 2021)

Effect of fermentation bed on bacterial growth in the fermentation mattress material and cecum of ducks - Jian- mei Wang; Xin- meng Gan; Fa-jun Pu; Wan- xia Wang; Min Ma; Ling-li Sun; Ji-wei Hu; Bo Hu; Rong-ping Zhang; Li-li Bai; Liang Li; He-he Liu (Archives of Microbiology, 2021)

Effects of Spray Parameters on the Effective Spray Width of Single-Rotor Drone in Sugarcane Plant Protection - Ping Zhang; Wei Zhang; Hai-Tian Sun; Feng-Guang He; Hai-Ba Fu; Li-Qiang Qi; Li-Juan Yu; Li-Yu Jin; Bo Zhang; Jian-Sheng Liu (Sugar Tech, 2021)

Sea level anomaly intelligent inversion model based on LSTM-RBF network - Hanmin Liu; Bo He; Ping Qin; Xin Zhang; Shuai Guo; Xiaokai Mu (Meteorology and Atmospheric Physics, 2021)

Molecular cloning and functional characterization of the hypoxia-inducible factor-1α in bighead carp (Aristichthys nobilis) - Yan Lin; Ling-Hong Miao; Bo Liu; Bing-Wen Xi; Liang-Kun Pan; Xian-Ping Ge (Fish Physiology and Biochemistry, 2021)

Groundwater sources, flow patterns, and hydrochemistry of the Central Yinchuan Plain, China - Ying Li; Ping Wu; Xiao-Qin Huang; Bo Zhang; Zhao-Xiang Xu; Yang Li; Jie Li; Lu-Chen Wang; Yu-Fang Sun; Xu-Chen Meng; Cheng-Wen Wang; Zi-Zhao Cai (Hydrogeology Journal, 2021)

A novel gammapartitivirus from the entomopathogenic fungus Metarhizium brunneum - Ping Wang; Guogen Yang; Najie Shi; Bo Huang (Archives of Virology, 2021)

Warming Iron-Limited Oceans Enhance Nitrogen Fixation and Drive Biogeographic Specialization of the Globally Important Cyanobacterium Crocosphaera - Nina Yang; Carlin A. Merkel; Yu-An Lin; Naomi M. Levine; Nicholas J. Hawco; Hai-Bo Jiang; Ping-Ping Qu; Michelle A. DeMers; Eric A. Webb; Fei-Xue Fu; David A. Hutchins (Frontiers in Marine Science, 2021)
Primary productivity in the nutrient-poor subtropical ocean gyres depends on new nitrogen inputs from nitrogen fixers that convert inert dinitrogen gas into bioavailable forms. Temperature and iron (Fe) availability constrain marine nitrogen fixation, and both are changing due to anthropogenic ocean warming. We examined the physiological responses of the globally important marine nitrogen fixer, Crocosphaera watsonii across its full thermal range as a function of iron availability. At the lower end of its thermal range, from 22 to 27°C, Crocosphaera growth, nitrogen fixation, and Nitrogen-specific Iron Use Efficiencies (N-IUEs, mol N fixed hour –1 mol Fe –1 ) increased with temperature. At an optimal growth temperature of 27°C, N-IUEs were 66% higher under iron-limited conditions than iron-replete conditions, indicating that low-iron availability increases metabolic efficiency. However, Crocosphaera growth and function decrease from 27 to 32°C, temperatures that are predicted for an increasing fraction of tropical oceans in the future. Altogether, this suggests that Crocosphaera are well adapted to iron-limited, warm waters, within prescribed limits. A model incorporating these results under the IPCC RCP 8.5 warming scenario predicts that Crocosphaera N-IUEs could increase by a net 47% by 2100, particularly in higher-latitude waters. These results contrast with published responses of another dominant nitrogen fixer ( Trichodesmium ), with predicted N-IUEs that increase most in low-latitude, tropical waters. These models project that differing responses of Crocosphaera and Trichodesmium N-IUEs to future warming of iron-limited oceans could enhance their current contributions to global marine nitrogen fixation with rates increasing by ∼91 and ∼22%, respectively, thereby shifting their relative importance to marine new production and also intensifying their regional divergence. Thus, interactive temperature and iron effects may profoundly transform existing paradigms of nitrogen biogeochemistry and primary productivity in open ocean regimes.

An approximate system for evaluating real-time port operations based on remote sensing images - Yajun Ping; Jiashen Zhao; Hongxin Shi; Qiang Zhang; Bo Xiang (International Journal of Remote Sensing, 2021)

The MYB transcription factor Baymax1 plays a critical role in rice male fertility - Xiao-Jiao Xiang; Lian-Ping Sun; Ping Yu; Zheng-Fu Yang; Pei-Pei Zhang; Ying-Xin Zhang; Wei-Xun Wu; Dai-Bo Chen; Xiao-Deng Zhan; Riaz-Muhammad Khan; Adil Abbas; Shi-Hua Cheng; et al. (Theoretical and Applied Genetics, 2021)

Starch bio-template synthesis of W-doped CeO2 catalyst for selective catalytic reduction of NOx with NH3: influence of ignition temperature - Zhi-Bo Xiong; Zhen-Zhuang Li; Yan-Ping Du; Cheng-Xu Li; Wei Lu; Su-Le Tian (Environmental Science and Pollution Research, 2021)

The gut bacterial flora associated with brown planthopper is affected by host rice varieties - Zheng-Liang Wang; Hai-bo Pan; Wei Wu; Mu-Yu Li; Xiao-Ping Yu (Archives of Microbiology, 2021)

Correction to: Non-Invasive Multimodality Imaging Directly Shows TRPM4 Inhibition Ameliorates Stroke Reperfusion Injury - Bo Chen; Gandi Ng; Yahui Gao; See Wee Low; Edwin Sandanaraj; Boominathan Ramasamy; Sakthivel Sekar; Kishore Bhakoo; Tuck Wah Soong; Bernd Nilius; Carol Tang; Edward G. Robins; et al. (Translational Stroke Research, 2020)

Population pharmacokinetics and dose optimization of ceftriaxone for children with community-acquired pneumonia - Muhammad Wasim Khan; Ya-Kun Wang; Yue-E Wu; Bo-Hao Tang; Min Kan; Hai-Yan Shi; Yi Zheng; Bao-Ping Xu; A-Dong Shen; Evelyne Jacqz-Aigrain; Li-Yuan Tian; Wei Zhao (European Journal of Clinical Pharmacology, 2020)

TIP60 recruits SUV39H1 to chromatin to maintain heterochromatin genome stability and resist hydrogen peroxide-induced cytotoxicity - Bo Tu; Yantao Bao; Ming Tang; Qian Zhu; Xiaopeng Lu; Hui Wang; Tianyun Hou; Ying Zhao; Ping Zhang; Wei-Guo Zhu (Genome Instability & Disease, 2020)

Impact of prophylactic/preemptive donor lymphocyte infusion and intensified conditioning for relapsed/refractory leukemia: a real-world study - Yu Wang; Qi-Fa Liu; De-Pei Wu; Jing-Bo Wang; Xi Zhang; Heng-Xiang Wang; Feng Gao; Shun-Qing Wang; Zi-Min Sun; Jian Ouyang; Kai-Lin Xu; Su-Jun Gao; et al. (Science China Life Sciences, 2020)

Zooplankton in a continuous waterscape: environmental and spatial factors shaping spring zooplankton community structure in a large canyon reservoir at the tropic of cancer - Eric Zeus C. Rizo; Ping Liu; Haiyu Niu; Yang Yang; Qiuqi Lin; Rey Donne S. Papa; Henri J. Dumont; Bo-Ping Han (Hydrobiologia, 2020)

Model test of the stability degradation of a prestressed anchored rock slope system in a corrosive environment - Cong Li; Rong-tang Zhang; Jie-bing Zhu; Zhi-jun Liu; Bo Lu; Bin Wang; Yu-zhou Jiang; Jie-sheng Liu; Ping Zeng (Journal of Mountain Science, 2020)

A histone deacetylase, GhHDT4D, is positively involved in cotton response to drought stress - Jing-Bo Zhang; Shao-Ping He; Jing-Wen Luo; Xin-Peng Wang; Deng-Di Li; Xue-Bao Li (Plant Molecular Biology, 2020)

Colletotrichum neorubicola sp. nov., a new leaf anthracnose pathogen of raspberry from northeast China - Li-Ping Liu; Yu Wang; Peng-Lei Qiu; Bo Zhang; Lin Zhang; Na Wang; Yu Li; Jie Gao; Tom Hsiang (Mycological Progress, 2020)

Corticosterone Induced the Increase of proBDNF in Primary Hippocampal Neurons Via Endoplasmic Reticulum Stress - Yu Liu; Guang-Jing Zou; Bo-Xuan Tu; Zhao-Lan Hu; Cong Luo; Yan-Hui Cui; Yang Xu; Fang Li; Ru-Ping Dai; Fang-Fang Bi; Chang-Qi Li (Neurotoxicity Research, 2020)

Life-history responses of Daphnia sinensis simultaneously exposed to Microcystis aeruginosa and Cylindrospermopsis raciborskii - Lamei Lei; Haitang Huang; Liang Peng; Yang Yang; Lijuan Xiao; Bo-Ping Han (Ecotoxicology, 2020)

Species diversity and seasonal dynamics of filamentous cyanobacteria in urban reservoirs for drinking water supply in tropical China - Yang Yang; Xunhao Zheng; Quehui Tang; Jiguang Gu; Lamei Lei; Bo-Ping Han (Ecotoxicology, 2020)

Reclassification of Brevibacterium frigoritolerans DSM 8801T as Bacillus frigoritolerans comb. nov. Based on Genome Analysis - Guo-Hong Liu; Bo Liu; Jie-Ping Wang; Jian-Mei Che; Peng-Fei Li (Current Microbiology, 2020)

A novel non-segmented double-stranded RNA virus isolated from the basal fungus Conidiobolus sp. - Guogen Yang; Fei Hu; Najie Shi; Ping Wang; Bo Huang (Archives of Virology, 2020)

Improving the dynamical seasonal prediction of western Pacific warm pool sea surface temperatures using a physical–empirical model - Ping Chen; Bo Sun (International Journal of Climatology, 2020)
The western Pacific warm pool (WPWP) has a profound impact on the global climate. In this study, the forecast skill of ENSEMBLES model for predicting the WPWP sea surface temperature (SST) for the period 1960–2006 is evaluated, where a WPWP index (WPWPI) is defined to represent the interannual variability of WPWP SST. The result indicates that the ENSEMBLES exhibit a poor skill in predicting the WPWPI during January–April (2‐ to 5‐month forecasts starting on November 1). To improve the ENSEMBLES‐predicted WPWP SSTs during January–April, a physical–empirical (PE) model is developed based on two predictors, using the year‐to‐year increment method and the linear regression method. The two predictors include the ENSEMBLES‐predicted sea level pressure during January and the observed northern tropical Atlantic SSTs during the preceding August. The mechanisms associated with the two predictors are illuminated. The 1‐year‐out cross‐validation and the independent hindcast indicate that this PE model may notably improve the WPWPI prediction of ENSEMBLES, with a correlation coefficient (CC) above 0.6 between the PE‐model‐predicted WPWPI and the observed WPWPI during January–April. The physical mechanisms expounded in this study and the PE model utilized in this study can be considered to improve the prediction of WPWP SST of numerical models in the future.

Arsenic, lead, and cadmium bioaccessibility in contaminated soils: Measurements and validations - Hong-Bo Li; Meng-Ya Li; Di Zhao; Jie Li; Shi-Wei Li; Ping Xiang; Albert L. Juhasz; Lena Q. Ma (Critical Reviews in Environmental Science and Technology, 2020)

Identification and Validation of Reference Genes in the Adzuki Bean (Vigna angularis) Under Iron Deficiency Using Quantitative Real-Time PCR - Junshuai Wang; Kai Yang; Bo Zhao; Yisong Li; Ping Wan (Plant Molecular Biology Reporter, 2020)

Curcumin protects BV2 cells against lipopolysaccharide-induced injury via adjusting the miR-362-3p/TLR4 axis - Ping Xie; Ming Deng; Qinguo Sun; Bo Jiang; Hongjie Xu; Junqi Liu; Yan Zhou; Yonggang Ma; Zhonghui Chen (Molecular Biology Reports, 2020)

Detection of serum IgM and IgG for COVID-19 diagnosis - Ling Zhong; Junlan Chuan; Bo Gong; Ping Shuai; Yu Zhou; Yi Zhang; Zhilin Jiang; Dingding Zhang; Xiaoqi Liu; Shi Ma; Yi Huang; He Lin; et al. (Science China Life Sciences, 2020)

Synthesis and biological effects of naphthalene-chalcone derivatives - Qing-Hao Jin; Hong-Hai Chen; Wen-Bo Chen; Zhi-Yang Fu; Li-Ping Guan; Hai-Ying Jiang (Medicinal Chemistry Research, 2020)

PX Domain-Containing Kinesin KIF16B and Microtubule-Dependent Intracellular Movements - Bo-jie Li; Hao Chen; Su-su Jiang; Chu-yao Wang; Qin-hui Tuo; Shi-yin Long; Cai-ping Zhang; Duan-fang Liao (The Journal of Membrane Biology, 2020)

Haplogroup Structure and Genetic Variation Analyses of 60 Mitochondrial DNA Markers in Southern Shaanxi Han Population - Yuan-Yuan Wei; Zhan-Ping Ren; Xiao-Ye Jin; Wei Cui; Chong Chen; Yu-Xin Guo; Hao-Tian Meng; Bo-Feng Zhu (Biochemical Genetics, 2020)

Enhanced adsorption of hydrophobic organic contaminants by high surface area porous graphene - Lixuan Ma; Kai Li; Chi Wang; Bo Liu; Hongbo Peng; Yi Mei; Ping Ning (Environmental Science and Pollution Research, 2020)

Molecular characterization of a new partitivirus, MbPV1, isolated from the entomopathogenic fungus Metarhizium brunneum in China - Ping Wang; Guogen Yang; Najie Shi; Bo Huang (Archives of Virology, 2020)

Roles of PTBP1 in alternative splicing, glycolysis, and oncogensis - Wei Zhu; Bo-lun Zhou; Li-juan Rong; Li Ye; Hong-juan Xu; Yao Zhou; Xue-jun Yan; Wei-dong Liu; Bin Zhu; Lei Wang; Xing-jun Jiang; Cai-ping Ren (Journal of Zhejiang University-SCIENCE B, 2020)

High expression of keratin 6C is associated with poor prognosis and accelerates cancer proliferation and migration by modulating epithelial–mesenchymal transition in lung adenocarcinoma - Hai-Bo Hu; Xiao-Ping Yang; Pei-Xia Zhou; Xin-Ai Yang; Bin Yin (Genes & Genomics, 2020)

Characterization and genome sequencing of a novel T7-like lytic phage, kpssk3, infecting carbapenem-resistant Klebsiella pneumoniae - Yunlong Shi; Yu Chen; Zichen Yang; Yulong Zhang; Bo You; Xinzhu Liu; Ping Chen; Meixi Liu; Cheng Zhang; Xiaoqiang Luo; Yajie Chen; Zhiqiang Yuan; et al. (Archives of Virology, 2020)

Risk profiling using metabolomic characteristics for susceptible individuals of drug-induced liver injury caused by Polygonum multiflorum - Le Zhang; Ming Niu; Ai-wu Wei; Jin-fa Tang; Can Tu; Zhao-fang Bai; Zheng-sheng Zou; Xiao-he Xiao; You-ping Liu; Jia-bo Wang (Archives of Toxicology, 2020)

Probiotic Clostridium butyricum Improves the Growth Performance, Immune Function, and Gut Microbiota of Weaning Rex Rabbits - Lei Liu; Dong Zeng; Mingyue Yang; Bin Wen; Jing Lai; Yi Zhou; Hao Sun; Lvcheng Xiong; Jie Wang; Yicen Lin; Kangcheng Pan; Bo Jing; et al. (Probiotics and Antimicrobial Proteins, 2019)

TRPM4-specific blocking antibody attenuates reperfusion injury in a rat model of stroke - Bo Chen; Yahui Gao; Shunhui Wei; See Wee Low; Gandi Ng; Dejie Yu; Tian Ming Tu; Tuck Wah Soong; Bernd Nilius; Ping Liao (Pflügers Archiv - European Journal of Physiology, 2019)
Reperfusion therapy is currently the gold standard treatment for acute ischemic stroke. However, reperfusion injuries such as oedema and haemorrhagic transformation largely limit the use of this potent treatment to a narrow time window. Recently, transient receptor potential melastatin 4 (TRPM4) channel has emerged as a potential target for vascular protection in stroke management. Non-specificity and side effects are major concerns for current TRPM4 blockers. The present study was undertaken to develop a novel TRPM4 blocker for stroke management. We report the generation of a TRPM4-specific antibody M4P which binds to a region close to the channel pore. M4P could inhibit TRPM4 current and downregulate TRPM4 surface expression, therefore prevent hypoxia-induced cell swelling. In the rat model of 3-h stroke reperfusion, application of M4P at 2 h after occlusion ameliorated reperfusion injury by improving blood–brain barrier integrity, and enhanced functional recovery. Our results demonstrate that TRPM4 blockade could attenuate reperfusion injury in stroke recanalization. When applied together with reperfusion treatments, TRPM4 blocking antibody has the potential to extend the therapeutic time window for acute ischemic stroke.

Development of real-time PCR for quantification of Cylindrospermopsis raciborskii cells and potential cylindrospermopsin-producing genotypes in subtropicalreservoirs of southern China - Lamei Lei; Minting Lei; Yan Lu; Liang Peng; Bo-Ping Han (Journal of Applied Phycology, 2019)

Inositol as a new enhancer for improving lipid production and accumulation in Schizochytrium sp. SR21 - Zhao-Xin Liu; Shuai You; Bin-Ping Tang; Bo Wang; Sheng Sheng; Fu-An Wu; Jun Wang (Environmental Science and Pollution Research, 2019)

Complete genome sequence of a novel partitivirus from the entomogenous fungus Beauveria bassiana in China - Najie Shi; Guogen Yang; Ping Wang; Yulong Wang; Deshui Yu; Bo Huang (Archives of Virology, 2019)

Genome-based reclassification of Bacillus plakortidis Borchert et al. 2007 and Bacillus lehensis Ghosh et al. 2007 as a later heterotypic synonym of Bacillus oshimensis Yumoto et al. 2005; Bacillus rhizosphaerae Madhaiyan et al. 2011 as a later heterotypic synonym of Bacillus clausii Nielsen et al. 1995 - Guo-Hong Liu; Manik Prabhu Narsing Rao; Zhou-Yan Dong; Jie-Ping Wang; Jian-Mei Che; Qian-Qian Chen; Cetin Sengonca; Bo Liu; Wen-Jun Li (Antonie van Leeuwenhoek, 2019)

An integrative bioinformatics analysis identified miR-375 as a candidate key regulator of malignant breast cancer - Jiaxuan Liu; Ping Wang; Ping Zhang; Xinyu Zhang; Hang Du; Qiang Liu; Bo Huang; Caiyun Qian; Shuhua Zhang; Weifeng Zhu; Xiaohong Yang; Yingqun Xiao; et al. (Journal of Applied Genetics, 2019)

Two novel alkaliphiles, Bacillus alkalisoli sp. nov., and Bacillus solitudinis sp. nov., isolated from saline-alkali soil - Guo-Hong Liu; Manik Prabhu Narsing Rao; Zhou-Yan Dong; Jie-Ping Wang; Zheng Chen; Bo Liu; Wen-Jun Li (Extremophiles, 2019)

N2O production in the organic and mineral horizons of soil had different responses to increasing temperature - Lifei Sun; Changpeng Sang; Chao Wang; Zhenzhen Fan; Bo Peng; Ping Jiang; Zongwei Xia (Journal of Soils and Sediments, 2019)

Complete Genome Sequence of Pseudomonas Parafulva PRS09-11288, a Biocontrol Strain Produces the Antibiotic Phenazine-1-carboxylic Acid - Yu Zhang; Ping Chen; Guoyou Ye; Haiyan Lin; Deyong Ren; Longbiao Guo; Bo Zhu; Zhongwei Wang (Current Microbiology, 2019)

Numerical simulation of ground motion amplification in Modong area, Lushan - Chao Han; Jiashun Yu; Wei-Zu Liu; Jian-Long Yuan; Xiao-Bo Fu; Xiao-Ping Hou (Applied Geophysics, 2019)

Correction to: Elevated expression of CST1 promotes breast cancer progression and predicts a poor prognosis - Da-nian Dai; Yan Li; Bo Chen; Yong Du; Shi-bing Li; Shi-xun Lu; Zhi-ping Zhao; Ai-jun Zhou; Ning Xue; Tian-liang Xia; Mu-sheng Zeng; Qian Zhong; et al. (Journal of Molecular Medicine, 2019)

Lateral Organ Boundaries Domain 19 (LBD19) negative regulate callus formation in Arabidopsis - Siqi Liu; Bo Wang; Xiaojing Li; Jingxian Pan; Xuexue Qian; Yahui Yu; Ping Xu; Jian Zhu; Xiaofeng Xu (Plant Cell, Tissue and Organ Culture (PCTOC), 2019)

Favus of Scrotum Due to Trichophyton rubrum in Immunocompetent Patients: A Clinical, Mycological and Ultrastructural Study - Ze-Hu Liu; Xiu-Jiao Xia; Yong Zhang; Yan Zhong; Bo Sang; Qiu-Ping Li; Mei Wang; Wen-Wen Lv; Hui-Lin Zhi; Xiang-Dong Wang; Cui-Ping Guan; Hong Shen (Mycopathologia, 2019)

Resina draconis inhibits the endoplasmic-reticulum-induced apoptosis of myocardial cells via regulating miR-423-3p/ERK signaling pathway in a tree shrew myocardial ischemia–reperfusion model - Tian-Rui Yang; Tong Zhang; Ning-Hui Mu; Li-Bo Ruan; Jin-Lan Duan; Rong-Ping Zhang; Yun-Bo Miao (Journal of Biosciences, 2019)

Polymorphism analyses of 19 STRs in Labrador Retriever population from China and its heterozygosity comparisons with other retriever breeds - Meng-Lei Wang; Xiao-Ye Jin; Xin Xiong; Jin-Long Yang; Jian-Ping Li; Qi Wang; Bo-Feng Zhu; Ya-Jun Deng (Molecular Biology Reports, 2019)

Toxicological effects benzotriazole to the marine scallop Chlamys nobilis: a 2-month exposure study - Tang-tian He; Tao Zhang; Shi-bo Liu; Jing-chun Shi; Yi-sheng Huang; Huai-ping Zheng; Wen-hua Liu (Environmental Science and Pollution Research, 2019)

The short-term effects of outdoor temperature on blood pressure among children and adolescents: finding from a large sample cross-sectional study in Suzhou, China - Jia Hu; Hui Shen; Chen-gang Teng; Di Han; Guang-ping Chu; Yi-kai Zhou; Qi Wang; Bo Wang; Jing-zhi Wu; Qi Xiao; Fang Liu; Hai-bing Yang (International Journal of Biometeorology, 2019)

Mesenchymal stem cell sheets: a new cell-based strategy for bone repair and regeneration - Meikai Chen; Yifan Xu; Tan Zhang; Yuliang Ma; Junquan Liu; Bo Yuan; Xuerong Chen; Ping Zhou; Xiaofeng Zhao; Fei Pang; Wenqing Liang (Biotechnology Letters, 2019)

Precise discovery of a STAT3 inhibitor from Eupatorium lindleyanum and evaluation of its activity of anti-triple-negative breast cancer - Bo Yang; Jia Wei Shen; Dong Heng Zhou; Ya Ping Zhao; Wei Qian Wang; Ying Zhu; Hua Jun Zhao (Natural Product Research, 2019)

Non-Invasive Multimodality Imaging Directly Shows TRPM4 Inhibition Ameliorates Stroke Reperfusion Injury - Bo Chen; Gandi Ng; Yahui Gao; See Wee Low; Edwin Sandanaraj; Boominathan Ramasamy; Sakthivel Sekar; Kishore Bhakoo; Tuck Wah Soong; Bernd Nilius; Carol Tang; Edward G. Robins; et al. (Translational Stroke Research, 2019)
The transient receptor potential melastatin 4 (TRPM4) channel has been suggested to play a key role in the treatment of ischemic stroke. However, in vivo evaluation of TRPM4 channel, in particular by direct channel suppression, is lacking. In this study, we used multimodal imaging to assess edema formation and quantify the amount of metabolically functional brain salvaged after a rat model of stroke reperfusion. TRPM4 upregulation in endothelium emerges as early as 2 h post-stroke induction. Expression of TRPM4 channel was suppressed directly in vivo by treatment with siRNA; scrambled siRNA was used as a control. T2-weighted MRI suggests that TRPM4 inhibition successfully reduces edema by 30% and concomitantly salvages functionally active brain, measured by 18 F-FDG-PET. These in vivo imaging results correlate well with post-mortem 2,3,5-triphenyltetrazolium chloride (TTC) staining which exhibits a 34.9% reduction in infarct volume after siRNA treatment. Furthermore, in a permanent stroke model, large areas of brain tissue displayed both edema and significant reductions in metabolic activity which was not shown in transient models with or without TRPM4 inhibition, indicating that tissue salvaged by TRPM4 inhibition during stroke reperfusion may survive. Evans Blue extravasation and hemoglobin quantification in the ipsilateral hemisphere were greatly reduced, suggesting that TRPM4 inhibition can improve BBB integrity after ischemic stroke reperfusion. Our results support the use of TRPM4 blocker for early stroke reperfusion.

Luminescence chronology of the Palaeolithic–Neolithic transition in the Yujiagou site at the Nihewan Basin, northern China - Xue Rui; Yu‐Jie Guo; Jia‐Fu Zhang; Yue Hu; Hui‐Jie Mei; You‐Ping Wang; Fei Xie; Bo Li (Journal of Quaternary Science, 2019)
The relationship between the Palaeolithic–Neolithic cultural transition and environmental changes is important for understanding human history. However, the timing and nature of human behaviour at the transition, and their relationship to local environmental conditions, remain poorly understood. The Yujiagou archaeological site in the Nihewan Basin, northern China, provides valuable chronological and archaeological information about cultural changes in northern China due to its continuous archaeological sequence of cultural layers from the Palaeolithic to Neolithic. In this study, we apply post‐infrared infrared stimulated luminescence (pIRIR) dating on individual feldspar grains to date the Yujiagou deposits. We provide a revised chronology for the archaeological sequence at the site. We combine these results with multi‐proxy climatic indicators to gain insights into palaeoenvironmental changes in the region. The results show that the age of the artefact‐bearing deposits ranges from 13.5 to 9.7 ka. Polished stones and pottery begin to occur in the archaeological layer around 13 ka, corresponding to a transitional period when the local climate changed from cold to warm. This site provides evidence for understanding the process that led to the regional transition from hunter‐gathering to farming.

Investigation of the stability of submarine sensitive clay slopes underwave-induced pressure - De-feng Zheng; Ting-kai Nian; Bo Liu; Min Liu; Ping Yin; Yan-dong Huo (Marine Georesources & Geotechnology, 2019)

Contamination characteristics and potential environmental implications of heavy metals in road dusts in typical industrial and agricultural cities, southeastern Hubei Province, Central China - Da-Mao Xu; Jia-Quan Zhang; Bo Yan; Hao Liu; Li-Li Zhang; Chang-Lin Zhan; Li Zhang; Ping Zhong (Environmental Science and Pollution Research, 2018)

A new abietane diterpenoid from the roots of Tripterygium regelii - Zhi-Hua Jiang; Yan-Ping Liu; Miao He; Jin-Hua Zhao; Ting-Ting Wang; Xing-Yang Feng; Hao Yue; Ren-Bo An; Yan-Hui Fu (Natural Product Research, 2018)

A corn straw-based diet increases release of inflammatory cytokines in peripheral blood mononuclear cells of dairy cows - Yan-yi Che; Xiao-jing Xia; Bo-ping He; Yuan-yuan Gao; Wen-bo Ren; Hong-tao Liu; Jian-fang Liu; Ting-hao Huang; Wen-yu Han; Lian-cheng Lei (Journal of Zhejiang University-SCIENCE B, 2018)

Gallaecimonas mangrovi sp. nov., a novel bacterium isolated from mangrove sediment - Wei-Yan Zhang; Ye Yuan; Deng-Quan Su; Xiao-Ping He; Shuai-Bo Han; Slava S. Epstein; Shan He; Min Wu (Antonie van Leeuwenhoek, 2018)

Spatial heterogeneity of spring phytoplankton in a large tropical reservoir: could mass effect homogenize the heterogeneity by species sorting? - Yang Yang; Haiyu Niu; Lijuan Xiao; Qiuqi Lin; Bo-Ping Han; Luigi Naselli-Flores (Hydrobiologia, 2018)

Spatial association between landslides and environmental factors over Guizhou Karst Plateau, China - Xi-liu Yue; Shao-hong Wu; Mei Huang; Jiang-bo Gao; Yun-he Yin; Ai-qing Feng; Xiao-ping Gu (Journal of Mountain Science, 2018)

Effects of biofertilizers and super absorbent polymers on plant growth and soil fertility in the arid mining area of Inner Mongolia, China - Jian-feng Zhang; Ting-ning Zhao; Bao-ping Sun; Shuang-shuang Song; Hu-bo Guo; Hao-jie Shen; Yi Wu (Journal of Mountain Science, 2018)

The complete mitochondrial genome of Pseudocrossocheilus bamaensis (Cypriniformes: Cyprinidae: Labeoninae) - Man Zhang; Bo-wen Liu; Guang-ping Cheng; Li Bian; Qi-jia Zhou; Wei-jie Yan; Wen-hong Li (Conservation Genetics Resources, 2018)

Methyl jasmonate and salicylic acid elicitation increase content and yield of chlorogenic acid and its derivatives in Gardenia jasminoides cell suspension cultures - Ze-Bo Liu; Ji-Guang Chen; Zhong-Ping Yin; Xin-Chen Shangguan; Da-Yong Peng; Tao Lu; Ping Lin (Plant Cell, Tissue and Organ Culture (PCTOC), 2018)

CFTR prevents neuronal apoptosis following cerebral ischemia reperfusion via regulating mitochondrial oxidative stress - Ya-Ping Zhang; Yong Zhang; Zhi-Bin Xiao; Yan-Bo Zhang; Jing Zhang; Zhi-Qiang Li; Yao-Bin Zhu (Journal of Molecular Medicine, 2018)

Late Quaternary tectonic activity and shortening rate of the Beiluntai fault zone in the South Tianshan, Xinjiang, NW China - Yuan Yao; He-Ping Song; Jian-Bo Chen; Shuai Li; Hai-Liang Jia (Arabian Journal of Geosciences, 2018)

42,573 cases of hepatectomy in China: a multicenter retrospective investigation - Binhao Zhang; Bixiang Zhang; Zhiwei Zhang; Zhiyong Huang; Yifa Chen; Minshan Chen; Ping Bie; Baogang Peng; Liqun Wu; Zhiming Wang; Bo Li; Jia Fan; et al. (Science China Life Sciences, 2018)

Transcriptome analysis of wheat seedling and spike tissues in the hybrid Jingmai 8 uncovered genes involved in heterosis - Yong-jie Liu; Shi-qing Gao; Yi-miao Tang; Jie Gong; Xiao Zhang; Yong-bo Wang; Li-ping Zhang; Ren-wei Sun; Quan Zhang; Zhao-bo Chen; Xiang Wang; Cai-juan Guo; et al. (Planta, 2018)

Effect of nitrite exposure on oxygen-carrying capacity and gene expression of NF-κB/HIF-1α pathway in gill of bighead carp (Aristichthys nobilis) - Yan Lin; Ling-Hong Miao; Wu-Xiao Zhang; Wen-Jing Pan; Hua-Liang Liang; Xian-Ping Ge; Yan-Shun Xu; Bo Liu; Ming-Chun Ren; Qun-Lan Zhou; Si-Lei Xia (Aquaculture International, 2018)

Responses of terrestrial nitrogen pools and dynamics to different patterns of freeze‐thaw cycle: A meta‐analysis - Decai Gao; Lei Zhang; Jun Liu; Bo Peng; Zhenzhen Fan; Weiwei Dai; Ping Jiang; Edith Bai (Global Change Biology, 2018)
Altered freeze‐thaw cycle ( FTC ) patterns due to global climate change may affect nitrogen (N) cycling in terrestrial ecosystems. However, the general responses of soil N pools and fluxes to different FTC patterns are still poorly understood. Here, we compiled data of 1519 observations from 63 studies and conducted a meta‐analysis of the responses of 17 variables involved in terrestrial N pools and fluxes to FTC . Results showed that under FTC treatment, soil NH 4 + , NO 3 − , NO 3 − leaching, and N 2 O emission significantly increased by 18.5%, 18.3%, 66.9%, and 144.9%, respectively; and soil total N ( TN ) and microbial biomass N ( MBN ) significantly decreased by 26.2% and 4.7%, respectively; while net N mineralization or nitrification rates did not change. Temperate and cropland ecosystems with relatively high soil nutrient contents were more responsive to FTC than alpine and arctic tundra ecosystems with rapid microbial acclimation. Therefore, altered FTC patterns (such as increased duration of FTC , temperature of freeze, amplitude of freeze, and frequency of FTC ) due to global climate warming would enhance the release of inorganic N and the losses of N via leaching and N 2 O emissions. Results of this meta‐analysis help better understand the responses of N cycling to FTC and the relationships between FTC patterns and N pools and N fluxes.

Thermal reaction norms of a subtropical and a tropical species of Diaphanosoma (cladocera) explain their distribution - Franja Pajk; Jiexiang Zhang; Bo‐Ping Han; Henri J. Dumont (Limnology and Oceanography, 2018)
Species distribution boundaries are often associated with aspects of climate and modified by competitive interactions. In the tropical region, Diaphanosoma is the most diverse genus of Cladocera. Diaphanosoma dubium is widely distributed in China, whereas the tropical Diaphanosoma excisum is restricted to the islands off the south China coast. The mean temperature of the coldest month at the northern limit of its distribution is 15°C. We studied the effect of temperature (10–40°C) on life history traits of clones from 16 populations of D. dubium and D. excisum in life‐table experiments in order to determine if their thermal performance curves (TPCs) explain their distribution and to estimate the extent and mode of genetic variation in their TPCs. Our results show that both species have higher optimum temperatures ( T o ∼ 33°C), critical thermal minimum (CT min = 10–15°C), and maximum (CT max = 39–40°C) than temperate cladocerans. Clones of D. excisum had narrower TPCs and higher T o than D. dubium clones, in accordance with predictions based on changes of temperature distributions with latitude. Significant levels of genetic variation in TPCs were present in both species. D. excisum had higher fitness than D. dubium at all temperatures above 15°C. However, at 15°C and below, D. dubium fitness was higher. Negative r at 15°C and below in combination with competition with the more cold‐adapted D. dubium exclude D. excisum from mainland China. TPCs of interacting species may be the basis of predicting future species distributions as temperature increases change the balance of biotic interactions.

Overexpression of Nogo receptor 3 (NgR3) correlates with poor prognosis and contributes to the migration of epithelial cells of nasopharyngeal carcinoma patients - Jiang-Yi He; Ping Han; Yu Zhang; Yong-Dong Liu; Shi-Jian Song; Guo-Kai Feng; Yu An; Ai-Jun Zhou; Hong-Bo Wang; Li Yuan; Zhi-Rui Lin; Tian-Liang Xia; et al. (Journal of Molecular Medicine, 2018)

Species-based classification reveals spatial processes of phytoplankton meta-communities better than functional group approaches: a case study from three freshwater lake regions in China - Li-Juan Xiao; Yiqiu Zhu; Yang Yang; Qiuqi Lin; Bo-Ping Han; Judit Padisák (Hydrobiologia, 2018)

VPS9 domain‐containing proteins are essential for autophagy and endocytosis in Pyricularia oryzae - Xue‐Ming Zhu; Shuang Liang; Huan‐Bin Shi; Jian‐Ping Lu; Bo Dong; Qian‐Sheng Liao; Fu‐Cheng Lin; Xiao‐Hong Liu (Environmental Microbiology, 2018)
Summary Pyricularia oryzae is the causal pathogen of rice blast disease. Autophagy has been shown to play important roles in P . oryzae development and plant infection. The P. oryzae endosomal system is highly dynamic and has been shown to be associated with conidiogenesis and pathogenicity as well. To date, the crosstalk between autophagy and endocytosis has not been explored in P. oryzae . Here, we identified three P. oryzae VPS9 domain‐containing proteins, PoVps9, PoMuk1 and PoVrl1. We found that PoVps9 and PoMuk1 are localized to vesicles and are each co‐localized with PoVps21, a recognized marker of early endosomes. Deletion of PoVPS9 resulted in severe defects in endocytosis and autophagosome degradation and impaired the localization of PoVps21 to endosomes. Additionally, deletion of the PoMUK1 gene in the Δ Povps9 mutant background exhibited more severe defects in development, autophagy and endocytosis compared with the Δ Povps9 mutant. Pull‐down assay showed that PoVps9 interacts with PoVps21, PoRab11 and PoRab1, which have been verified to participate in endocytosis. Furthermore, yeast two‐hybrid and co‐immunoprecipitation assays confirmed that PoVps9 directly interacts with the GDP form of PoVps21. Thus, PoVps9 is a key protein involved in autophagy and in endocytosis.

Effects of an additive (hydroxyapatite–biochar–zeolite) on the chemical speciation of Cd and As in paddy soils and their accumulation and translocation in rice plants - Jiao-Feng Gu; Hang Zhou; Wen-Tao Yang; Pei-Qin Peng; Ping Zhang; Min Zeng; Bo-Han Liao (Environmental Science and Pollution Research, 2018)

CD137–CD137L interaction modulates neointima formation and the phenotype transformation of vascular smooth muscle cells via NFATc1 signaling - Wei Zhong; Bo Li; Ping Yang; Rui Chen; Cuiping Wang; Zhongqun Wang; Chen Shao; Wei Yuan; Jinchuan Yan (Molecular and Cellular Biochemistry, 2018)

Spatial structure and β-diversity of phytoplankton in Tibetan Plateau lakes: nestedness or replacement? - Yang Yang; Ren Hu; Qiuqi Lin; Juzhi Hou; Yongqin Liu; Bo-Ping Han; Luigi Naselli-Flores (Hydrobiologia, 2018)

Prediction of Large Deformation Behavior in Tunnels Based on AHP–FUZZY Method and Numerical Simulation Method - Jian-bo Xu; Jian-ping Chen; Shuang-lan Wu; Yi-heng Pan; Wei Wang; Qi-qi Luo (Geotechnical and Geological Engineering, 2018)

Persistence of immune responses to vaccine against haemorrhagic fever with renal syndrome in healthy adults aged 16–60 years: results from an open-label2-year follow-up study - Yuan Zheng; Bu-Yu Zhou; Jing Wei; Yi Xu; Jian-Hua Dong; Lu-Yuan Guan; Ping Ma; Peng-Bo Yu; Jing-Jun Wang (Infectious Diseases, 2018)

Impact of urban water system treatment on the surrounding residential land price - Ji-wei Zhu; Bo Chen; Ping Lu; Jian-lin Liu; Gang Tang (Arabian Journal of Geosciences, 2018)

Comorbidity Burden of Dementia: A Hospital-Based Retrospective Study from 2003 to 2012 in Seven Cities in China - Qing-Hua Wang; Xin Wang; Xian-Le Bu; Yan Lian; Yang Xiang; Hong-Bo Luo; Hai-Qiang Zou; Jie Pu; Zhong-He Zhou; Xiao-Ping Cui; Qing-Song Wang; Xiang-Qun Shi; et al. (Neuroscience Bulletin, 2017)

Spatial heterogeneity and long-term dynamics of cladoceran ephippia in a monsoonal reservoir, driven by hydrology and eutrophication - Lei Xu; Shaolin Xu; Xiaoyu Han; Sijia Li; Henri J. Dumont; Bo-Ping Han (Journal of Paleolimnology, 2017)

Bioinformatic prediction and analysis of glucolipid metabolic regulation by miR-34a in Megalobrama amblycephala - Ling-Hong Miao; Wen-Jing Pan; Yan Lin; Xian-Ping Ge; Bo Liu; Ming-Chun Ren; Qun-Lan Zhou (Genes & Genomics, 2017)

Molecular insights into the origin of the brown rust resistance gene Bru1 among Saccharum species - Heng-Bo Wang; Ping-Hua Chen; Yan-Qing Yang; Angelique D’Hont; Yun-Hai Lu (Theoretical and Applied Genetics, 2017)

Ten years of elevated CO2 affects soil greenhouse gas fluxes in an open top chamber experiment - Jianfei Sun; Zongwei Xia; Tongxin He; Weiwei Dai; Bo Peng; Jun Liu; Decai Gao; Ping Jiang; Shijie Han; Edith Bai (Plant and Soil, 2017)

Molecular diversity of phenothiazines: design and synthesis of phenothiazine–dithiocarbamate hybrids as potential cell cycle blockers - Dong-Jun Fu; Ruo-Han Zhao; Jia-Huan Li; Jia-Jia Yang; Ruo-Wang Mao; Bo-Wen Wu; Ping Li; Xiao-Lin Zi; Qing-Qing Zhang; Hui-Jie Cai; Sai-Yang Zhang; Yan-Bing Zhang; et al. (Molecular Diversity, 2017)

Comparison of infrared canopy temperature in a rubber plantation and tropical rain forest - Qing-Hai Song; Yun Deng; Yi -Ping Zhang; Xiao-Bao Deng; You-Xing Lin; Li-Guo Zhou; Xue-Hai Fei; Li-Qing Sha; Yun-Tong Liu; Wen-Jun Zhou; Jin-Bo Gao (International Journal of Biometeorology, 2017)

Fasudil Enhances Therapeutic Efficacy of Neural Stem Cells in the Mouse Model of MPTP-Induced Parkinson’s Disease - Yan-Hua Li; Jing-Wen Yu; Jian-Yin Xi; Wen-Bo Yu; Jian-Chun Liu; Qing Wang; Li-Juan Song; Ling Feng; Ya-Ping Yan; Guang-Xian Zhang; Bao-Guo Xiao; Cun-gen Ma (Molecular Neurobiology, 2017)

Identifying functional groups and ecological roles of tropical and subtropical freshwater Cladocera in Asia - Eric Zeus C. Rizo; Yangliang Gu; Rey Donne S. Papa; Henri J. Dumont; Bo-Ping Han (Hydrobiologia, 2017)

Elevated expression of CST1 promotes breast cancer progression and predicts a poor prognosis - Da-nian Dai; Yan Li; Bo Chen; Yong Du; Shi-bing Li; Shi-xun Lu; Zhi-ping Zhao; Ai-jun Zhou; Ning Xue; Tian-liang Xia; Mu-sheng Zeng; Qian Zhong; et al. (Journal of Molecular Medicine, 2017)
Cystatin SN (CST1) belongs to the type 2 cystatin (CST) superfamily, which restricts the proteolytic activities of cysteine proteases. CST1 has been recently considered to be involved in the development of several human cancers. However, the prognostic significance and function of CST1 in breast cancer remains unknown. In the current study, we found that CST1 was generally upregulated in breast cancer at both mRNA and protein level. Furthermore, overall survival (OS) and disease-free survival (DFS) in the low CST1 expression subgroup were significantly superior to the high CST1 expression subgroup (OS, p < 0.001; DFS, p < 0.001), which indicated that CST1 expression level was closely correlated to the survival risk of these patients. Univariate and multivariate analyses demonstrated that CST1 expression was an independent prognostic factor, the same as ER status and nodal status. Next, CST1 overexpression promoted breast cancer cell proliferation, clonogenicity, migration, and invasion abilities. By contrast, knockdown of CST1 attenuated these malignant characteristics in breast cancer cells. Collectively, our study indicates that CST1 cannot only serve as a significant prognostic indicator but also as a potential therapeutic target for breast cancer. Key messages High CST1 expression is negatively correlated with survival of breast cancer patients. CST1 promotes cell proliferation, clone formation, and metastasis in breast cancer cells. CST1 is a novel potential prognostic biomarker and therapeutic target for breast cancer.

Overexpression of Arabidopsis ICR1 gene affects vegetative growth and anthesis - Da-Hui Li; Man-Li Li; Xiao-Bo Yu; Di Wu; Huan Xi; Yi Lin; Yong-Ping Cai (Biologia, 2017)

Chemical constituents from Swertia mussotii Franch. (Gentianaceae) - Haixia Wang; Xiang Yuan; Huiming Huang; Bo Zhang; Changnian Cao; Hong-Ping Zhao (Natural Product Research, 2017)

Two ultraviolet radiation datasets that cover China - Hui Liu; Bo Hu; Yuesi Wang; Guangren Liu; Liqin Tang; Dongsheng Ji; Yongfei Bai; Weikai Bao; Xin Chen; Yunming Chen; Weixin Ding; Xiaozeng Han; et al. (Advances in Atmospheric Sciences, 2017)

Different fates of deposited and in a temperate forest in northeast China: a 15 N tracer study - Jun Liu; Bo Peng; Zongwei Xia; Jianfei Sun; Decai Gao; Weiwei Dai; Ping Jiang; Edith Bai (Global Change Biology, 2017)
Increasing atmospheric reactive nitrogen (N) deposition due to human activities could change N cycling in terrestrial ecosystems. However, the differences between the fates of deposited and are still not fully understood. Here, we investigated the fates of deposited and , respectively, via the application of 15 NH 4 NO 3 and NH 4 15 NO 3 in a temperate forest ecosystem. Results showed that at 410 days after tracer application, most was immobilized in litter layer (50 ± 2%), while a considerable amount of penetrated into 0–5 cm mineral soil (42 ± 2%), indicating that litter layer and 0–5 cm mineral soil were the major N sinks of and , respectively. Broad‐leaved trees assimilated more 15 N under NH 4 15 NO 3 treatment compared to under 15 NH 4 NO 3 treatment, indicating their preference for –N. At 410 days after tracer application, 16 ± 4% added 15 N was found in aboveground biomass under treatment, which was twice more than that under treatment (6 ± 1%). At the same time, approximately 80% added 15 N was recovered in soil and plants under both treatments, which suggested that this forest had high potential for retention of deposited N. These results provided evidence that there were great differences between the fates of deposited and , which could help us better understand the mechanisms and capability of forest ecosystems as a sink of reactive nitrogen.

Analysis of Dynamic Fracture Compliance Based on Poroelastic Theory. Part I: Model Formulation and Analytical Expressions - Ding Wang; Shou-Li Qu; Ping-Bo Ding; Qun Zhao (Pure and Applied Geophysics, 2017)

Genetic characterization of H9N2 avian influenza virus in plateau pikas in the Qinghai Lake region of China - Yan Yan; Jin-Yan Gu; Zhuang-Chuan Yuan; Xin-Yu Chen; Zeng-Kui Li; Jing Lei; Bo-li Hu; Li-Ping Yan; Gang Xing; Min Liao; Ji-Yong Zhou (Archives of Virology, 2017)

Effect of nitrogen addition on the variations in the natural abundance of nitrogen isotopes of plant and soil components - Jun Liu; Chao Wang; Bo Peng; Zongwei Xia; Ping Jiang; Edith Bai (Plant and Soil, 2017)

Mice lacking myotubularin-related protein 14 show accelerated high-fat diet-induced lipid accumulation and inflammation - Lv Yin; Peng Yong-bo; Yu Meng-Fei; Chen Weiwei; Zhao Ping; Xue Lu; Ma Li-Qun; Cai Congli; Liu Qing-hua; Shen Jinhua (Journal of Physiology and Biochemistry, 2017)

Age-dependent impact of inferior alveolar nerve transection on mandibular bone metabolism and the underlying mechanisms - Qingqing Wu; Bo Yang; Cong Cao; Mengkai Guang; Ping Gong (Journal of Molecular Histology, 2016)

Investigating the Effect of Tissue Size on Mycelial Growth of Seven Mushroom Species by Using a Novel Device for Precise Tissue Isolation - Sheng-Rong Liu; Wei-Rui Zhang; Ai-Ping Chen; Yun-Bo Kuang (Indian Journal of Microbiology, 2016)

RhoB/ROCK mediates oxygen–glucose deprivation-stimulated syncytiotrophoblast microparticle shedding in preeclampsia - Jian Han; Bo-ping Yang; Yi-lin Li; Hong-mei Li; Xiu-hui Zheng; Li-li Yu; Qiong Zhang; Ying-ru Zheng; Ping Yi; Li Li; Jian-xin Guo; Yuan-guo Zhou (Cell and Tissue Research, 2016)

MoRad6‐mediated ubiquitination pathways are essential for development and pathogenicity in Magnaporthe oryzae - Huan‐Bin Shi; Guo‐Qing Chen; Ya‐Ping Chen; Bo Dong; Jian‐Ping Lu; Xiao‐Hong Liu; Fu‐Cheng Lin (Environmental Microbiology, 2016)
Summary The ubiquitin system modulates protein functions through targeting substrates for ubiquitination. Here, E2 conjugating enzyme MoRad6‐related ubiquitination pathways are identified and analyzed in Magnaporthe oryzae , the causal agent of rice blast disease. Disruption of MoRad6 leads to severe defects in growth, sporulation, conidial germination, appressorium formation, and plant infection. To depict the functions of MoRad6, three putative ubiquitin ligases, MoRad18, MoBre1 and MoUbr1, are also characterized. Deletion of MoRad18 causes minor phenotypic changes, while MoBre1 is required for growth, conidiation and pathogenicity in M. oryzae . Defects in ΔMobre1 likely resulted from the reduction in di‐ and tri‐methylation level of Histone 3 lysine 4 (H3K4). Notably, MoUbr1 is crucial for conidial adhesion and germination, possibly by degrading components of cAMP/PKA and mitogen‐activated protein kinase (MAPK) Pmk1 signaling pathways via the N‐end rule pathway. Germination failure of ΔMoubr1 conidia could be rescued by elevation of cAMP level or enhanced Pmk1 phosphorylation resulting from further deletion of MoIra1, the M. oryzae homolog of yeast Ira1/2. These reveal vital effects of cAMP/PKA and MAPK Pmk1 signaling on conidial germination in M. oryzae . Altogether, our results suggest that MoRad6‐mediated ubiquitination pathways are essential for the infection‐related development and pathogenicity of M. oryzae .

Netrin-1 Contributes to Myelinated Afferent Fiber Sprouting and Neuropathic Pain - Cai-Hua Wu; Xiao-Cui Yuan; Fang Gao; Hong-Ping Li; Jie Cao; Yan-Shen Liu; Wei Yu; Bo Tian; Xian-Fang Meng; Jing Shi; Hui-Lin Pan; Man Li (Molecular Neurobiology, 2016)

Site amplification effects as an explanation for the intensity anomaly in the Hanyuan Town during the Wenchuan M w 7.9 earthquake - Hongshuai Liu; Jingshan Bo; Ping Li; Wenhao Qi; Yudong Zhang (Earthquake Engineering and Engineering Vibration, 2016)

ASL16 gene, a member of AS2/LOB family, is essential for lateral root formation in Arabidopsis - Lai-Sheng Meng; He Bizhu; Xiao-Ying Cao; Xu-Qin Yang; Jiang-Ping Song; Yi-Bo Wang; Ji-Hong Jiang (Biologia, 2016)

Simulation of Water Quality under Different Reservoir Regulation Scenarios in the Tidal River - Tao Jiang; Ming Zhong; Ying-jie Cao; Long-jian Zou; Bo Lin; Ai-ping Zhu (Water Resources Management, 2016)

Effect of Tai Chi exercise on blood lipid profiles: a meta-analysis of randomized controlled trials - Xiao-hong Pan; Amina Mahemuti; Xue-hua Zhang; Ya-ping Wang; Po Hu; Ju-bo Jiang; Mei-xiang Xiang; Gang Liu; Jian-an Wang (Journal of Zhejiang University-SCIENCE B, 2016)

Highly selective and efficient biotransformation of linarin to produce tilianin by naringinase - Pan Cui; Tong-Yi Dou; Shi-Yang Li; Jun-Xia Lu; Li-Wei Zou; Ping Wang; Yan-Ping Sun; Da-Cheng Hao; Guang-Bo Ge (Biotechnology Letters, 2016)

Effects of fish meal replacement by soybean peptide on growth performance, digestive enzyme activities, and immune responses of yellow catfish Pelteobagrus fulvidraco - Zhen-xin Zhao; Chang-you Song; Jun Xie; Xian-ping Ge; Bo Liu; Si-lei Xia; Shun Yang; Qing Wang; Sai-hua Zhu (Fisheries Science, 2016)

USPIO assisting degradation of MXC by host/guest-type immobilized laccase in AOT reverse micelle system - Yu-Xiang Yang; Na Pi; Jian-Bo Zhang; Yan Huang; Ping-Ping Yao; Yan-Jie Xi; Hong-Ming Yuan (Environmental Science and Pollution Research, 2016)

Comparative proteomic analysis of Phalaenopsis leaves in the vegetative and flowering phase - Xiu-Yun Yuan; Shen-Ping Xu; Fang Liang; Su-Hua Jiang; Mo-Fei Wang; Jie Ma; Xian-Yun Zhang; Bo Cui (Acta Physiologiae Plantarum, 2016)

Nitrogen addition affects chemical compositions of plant tissues, litter and soil organic matter - Jun Liu; Nana Wu; Hui Wang; Jianfei Sun; Bo Peng; Ping Jiang; Edith Bai (Ecology, 2016)
Increasing nitrogen (N) deposition or fertilization has been found to significantly affect carbon (C) cycling. However, a comprehensive understanding of how different C chemical components of plant, litter, and soil would respond to external N addition is still lacking. We compiled data of 1,160 observations from 52 individual studies and conducted a meta‐analysis of N addition effects on 18 variables related to C chemical compositions in terrestrial ecosystems. Results showed that plant lignin (+7.13%), plant protein (+25.94%), and soil lignin (+7.30%) were significantly increased by N addition, and plant hemicellulose (−4.39%) was significantly decreased, whereas plant fiber, plant cellulose, plant non‐structural carbohydrate ( NSC ), litter lignin, and litter cellulose were not significantly changed. The effects of N addition on C chemical composition varied among different ecosystems/plant types and different forms of N addition. Increasing treatment duration did not significantly change the effects of N addition on the chemical composition of plant, litter, and soil C. With increasing N addition rate, the effect of N addition on plant lignin, plant fiber, plant cellulose, and plant protein increased, while the effect of N addition on plant hemicellulose, plant NSC , and litter cellulose became more negative. Our meta‐analysis provided a systematic evaluation of the responses of different C chemical components to N addition in the plant–litter–soil continuum. Results suggest that the change of plant and soil C chemical composition under N addition may be beneficial for ecosystem C sequestration and could affect ecosystem structure and function in the future.

Enhanced short-cut nitrification in an airlift reactor by CaCO3 attachment on biomass under high bicarbonate condition - Mohammad Ali; Li-Yuan Chai; Hai-Ying Wang; Chong-Jian Tang; Xiao-Bo Min; Xu Yan; Cong Peng; Yu-Xia Song; Ping Zheng (Biodegradation, 2016)

Genetic polymorphism analyses of a novel panel of 19 X-STR loci in the Chinese Uygur ethnic minority - Yu-xin Guo; Jian-gang Chen; Yan Wang; Jiang-wei Yan; Jing Chen; Tian-hua Yao; Li-ping Zhang; Guang Yang; Hao-tian Meng; Yu-dang Zhang; Ting Mei; Yao-shun Liu; et al. (Journal of Zhejiang University-SCIENCE B, 2016)

Long-term persistence of anti-hantavirus antibodies in sera of patients undergoing hemorrhagic fever with renal syndrome and subjects vaccinated against the disease - Yuan Zheng; Jing Wei; Bu-Yu Zhou; Yi Xu; Jian-Hua Dong; Lu-Yuan Guan; Ping Ma; Peng-Bo Yu; Jing-Jun Wang (Infectious Diseases, 2016)

Growth performance and immune responses of gibel carp, Carassius auratus gibelio, fed with graded level of rare earth-chitosan chelate - Qun-lan Zhou; Jun Xie; Xian-ping Ge; H. Michael Habte-Tsion; Bo Liu; Mingchun Ren (Aquaculture International, 2016)

Prediction of drug-induced eosinophilia adverse effect by using SVM and naïve Bayesian approaches - Hui Zhang; Peng Yu; Ming-Li Xiang; Xi-Bo Li; Wei-Bao Kong; Jun-Yi Ma; Jun-Long Wang; Jin-Ping Zhang; Ji Zhang (Medical & Biological Engineering & Computing, 2016)

The application study on the multi-scales integrated prediction method to fractured reservoir description - Shuang-Quan Chen; Lian-Bo Zeng; Ping Huang; Shao-Han Sun; Wan-Lu Zhang; Xiang-Yang Li (Applied Geophysics, 2016)

PPM1D exerts its oncogenic properties in human pancreatic cancer through multiple mechanisms - Bo Wu; Bo-Min Guo; Jie Kang; Xian-Zhao Deng; You-Ben Fan; Xiao-Ping Zhang; Kai-Xing Ai (Apoptosis, 2016)

Canonical and non-canonical Wnt signaling control the regeneration of amputated rodent vibrissae follicles - Yan-Ping Yuan; Keng Huang; Yan-Min Xu; Xian-Cai Chen; Hai-Hong Li; Bo-Zhi Cai; Yang Liu; Huan Zhang; Yu Li; Chang-Min Lin (Journal of Molecular Histology, 2016)

Top-down effects of bighead carp (Aristichthys nobilis) and Leptodora richardi (Haplopoda, Leptodoridae) in a subtropical reservoir during the winter–spring transition: a mesocosm experiment - Shuai-Ying Zhao; Yu-Ping Sun; Bo-Ping Han (Hydrobiologia, 2016)

The complete mitochondrial genome of fall armyworm Spodoptera frugiperda (Lepidoptera:Noctuidae) - Qiu-Ning Liu; Xin-Yue Chai; Dan-Dan Bian; Bao-Ming Ge; Chun-Lin Zhou; Bo-Ping Tang (Genes & Genomics, 2016)

Gomisin A is a Novel Isoform-Specific Probe for the Selective Sensing of Human Cytochrome P450 3A4 in Liver Microsomes and Living Cells - Jing-Jing Wu; Guang-Bo Ge; Yu-Qi He; Ping Wang; Zi-Ru Dai; Jing Ning; Liang-Hai Hu; Ling Yang (The AAPS Journal, 2016)

CD147 promotes IKK/IκB/NF-κB pathway to resist TNF-induced apoptosis in rheumatoid arthritis synovial fibroblasts - Yue Zhai; Bo Wu; Jia Li; Xi-ying Yao; Ping Zhu; Zhi-nan Chen (Journal of Molecular Medicine, 2016)

Dissimilarity of phytoplankton assemblages in two connected tropical reservoirs: effects of water transportation and environmental filtering - Li-Juan Xiao; Ren Hu; Liang Peng; La-Mei Lei; Yu Feng; Bo-Ping Han (Hydrobiologia, 2016)

Tracking management-related water quality alterations by phytoplankton assemblages in a tropical reservoir - Ren Hu; Qiuhua Li; Bo-Ping Han; Luigi Naselli-Flores; Judit Padisak; Nico Salmaso (Hydrobiologia, 2016)

Dynamic Transcriptional Regulation of Fis in Salmonella During the Exponential Phase - Hui Wang; Lei Wang; Ping Li; Yilang Hu; Wei Zhang; Bo Tang (Current Microbiology, 2015)

Research on Acute Toxicity and Pharmacodynamics of Jinyulian Oral Solution - Wan-Qing Cheng; Zhen-Jian Zhang; Chuan-Bin Cao; Xiao-Wen Ye; Wang-Ping Pan; Si-Ying Ye; Bo Zhu (Cell Biochemistry and Biophysics, 2015)
A research on Jinyulian Oral Solution was conducted and the objectives were to discover its possible acute toxicity and antibacterial effects when used in vitro and in vivo. Regarding the acute toxicity test, Kunming mice were fed a maximum amount of the solution as their stomachs could hold, i.e., 40 mL kg −1 . To ascertain the minimum inhibitory concentration (MIC) of the solution, two types of germs, i.e., Staphylococcus aureus and Escherichia coli , were selected and tube dilution method was adopted. An antibacterial experimental model relying on animals’ body was developed for the researchers to observe the solution’s antibacterial effects. Test results showed that no abnormalities were discovered within 14 days after the initial date of testing and the mice grew as normal when fed with an amount of the solution 250 times of a normal clinical doze (In this case a man was assumed to weigh 60 kg.) and that the solution demonstrated obvious antibacterial effects on the two types of selected germs. The respective measured MIC 50 and MIC 90 values of the two germs were 3.2, 12.8, 6.4, and 25.6 mg L −1 . Therefore, it is reasonable to conclude that Jinyulian Oral Solution possesses no acute toxicity but obvious antibacterial effects on the two before-mentioned germs.

Formation of radial symmetric needle-like rosette leaves in Arabidopsis - Jiang-Ping Song; Da-Hui Liu; Yi-Bo Wang; Ya-Na Shi (Biologia, 2015)

Competition between toxic and non-toxic Microcystis aeruginosa and its ecological implication - Lamei Lei; Chunlian Li; Liang Peng; Bo-Ping Han (Ecotoxicology, 2015)

Vortex- and Shaker-Assisted Liquid–Liquid Microextraction (VSA-LLME) Coupled with Gas Chromatography and Mass Spectrometry (GC-MS) for Analysis of 16 Polycyclic Aromatic Hydrocarbons (PAHs) in Offshore Produced Water - Jisi Zheng; Bo Liu; Jing Ping; Bing Chen; Hongjing Wu; Baiyu Zhang (Water, Air, & Soil Pollution, 2015)

Roles of Serine/Threonine Phosphatases in Low-Dose Endothelial Monocyte-Activating Polypeptide-II-Induced Opening of Blood–Tumor Barrier - Zhen Li; Xiao-bai Liu; Yun-hui Liu; Yi-xue Xue; Ping Wang; Li-bo Liu; Jing Liu; Yi-long Yao; Jun Ma (Journal of Molecular Neuroscience, 2015)

Functions for the cAMP/Epac/Rap1 Signaling Pathway in Low-Dose Endothelial Monocyte-Activating Polypeptide-II-Induced Opening of Blood–Tumor Barrier - Zhen Li; Xiao-bai Liu; Yun-hui Liu; Yi-xue Xue; Ping Wang; Li-bo Liu; Yi-long Yao; Jun Ma (Journal of Molecular Neuroscience, 2015)

ASYMMETRIC LEAVES2-LIKE38, one member of AS2/LOB gene family, involves in regulating ab-adaxial patterning in Arabidopsis lateral organs - Yi-Bo Wang; Jiang-Ping Song; Zhi-Bo Wang (Acta Physiologiae Plantarum, 2015)

Effects of delayed motherhood on hippocampal gene expression in offspring rats - Ping Duan; Bo Li; Caifang Li; Xuefei Han; Yan Xu; Ying Xing; Wenhai Yan (Molecular and Cellular Biochemistry, 2015)

Pure total flavonoids from Citrus paradisi Macfadyen act synergistically with arsenic trioxide in inducing apoptosis of Kasumi-1 leukemia cells in vitro - Bo Wang; Sheng-yun Lin; Ying-ying Shen; Li-qiang Wu; Zhen-zhen Chen; Jing Li; Zhi Chen; Wen-bin Qian; Jian-ping Jiang (Journal of Zhejiang University-SCIENCE B, 2015)

Elevated Serum Homocysteine (Hcy) Levels May Contribute to the Pathogenesis of Cerebral Infarction - Hong-Juan Fu; Li-Bo Zhao; Ju-Jun Xue; Zhi-Xuan Wu; Yue-Ping Huang; Wei Liu; Zhan Gao (Journal of Molecular Neuroscience, 2015)

Marker-assisted breeding for transgressive seed protein content in soybean [Glycine max (L.) Merr.] - Ying Hu Zhang; Mei Feng Liu; Jian Bo He; Yu Feng Wang; Guang Nan Xing; Yan Li; Shou Ping Yang; Tuan Jie Zhao; Jun Yi Gai (Theoretical and Applied Genetics, 2015)

Expression of Wnt/β-catenin signaling, stem-cell markers and proliferating cell markers in rat whisker hair follicles - Chang-min Lin; Yan-ping Yuan; Xian-cai Chen; Hai-hong Li; Bo-zhi Cai; Yang Liu; Huan Zhang; Yu Li; Keng Huang (Journal of Molecular Histology, 2015)

Risk factors for the Long-Term Efficacy, Recurrence, and Metastasis in Small Hepatocellular Carcinomas - Ye Chen; She-Gan Gao; Jian-Min Chen; Gong-Ping Wang; Zeng-Fang Wang; Bo Zhou; Can-Hui Jin; Yan-Tong Yang; Xiao-Shan Feng (Cell Biochemistry and Biophysics, 2015)

The effect of Bt-transgene introgression on plant growth and reproduction in wild Brassica juncea - Yong-Bo Liu; Henry Darmency; C. Neal Stewart; Wei Wei; Zhi-Xi Tang; Ke-Ping Ma (Transgenic Research, 2015)

Chitooligosaccharides Attenuate Cu2+-Induced Cellular Oxidative Damage and Cell Apoptosis Involving Nrf2 Activation - Han-Chang Huang; Liang Hong; Ping Chang; Jiao Zhang; Shu-Yan Lu; Bo-Wen Zheng; Zhao-Feng Jiang (Neurotoxicity Research, 2015)

Role of cAMP-Dependent Protein Kinase A Activity in Low-Dose Endothelial Monocyte-Activating Polypeptide-II-Induced Opening of Blood–Tumor Barrier - Zhen Li; Xiao-bai Liu; Yun-hui Liu; Yi-xue Xue; Ping Wang; Li-bo Liu (Journal of Molecular Neuroscience, 2015)

Blood–brain barrier permeability change and regulation mechanism after subarachnoid hemorrhage - Zhiqing Li; Guobiao Liang; Teng Ma; Jingchen Li; Ping Wang; Libo Liu; Bo Yu; Yunhui Liu; Yixue Xue (Metabolic Brain Disease, 2015)

Serum CA242, CA199, CA125, CEA, and TSGF are Biomarkers for the Efficacy and Prognosis of Cryoablation in Pancreatic Cancer Patients - Ye Chen; She-Gan Gao; Jian-Min Chen; Gong-Ping Wang; Zeng-Fang Wang; Bo Zhou; Can-Hui Jin; Yan-Tong Yang; Xiao-Shan Feng (Cell Biochemistry and Biophysics, 2015)

Correlation of an interleukin-4 gene polymorphism with susceptibility to severe enterovirus 71 infection in Chinese children - Fei Li; Xiang-ping Liu; Ji-an Li; Zhen-liang Han; Pei-pei Liu; Yuan-yuan Wang; Long Song; Zong-bo Chen (Archives of Virology, 2015)

Shear Strength of an Accumulation Soil from Direct Shear Test - Jun-Jie Wang; Hui-Ping Zhang; Hui-Bo Wen; Yue Liang (Marine Georesources & Geotechnology, 2015)

Analysis on Response of a Single Pile Subjected to Tension Load Using a Softening Model and a Hyperbolic Model - Qian-Qing Zhang; Shu-Cai Li; Qian Zhang; Li-Ping Li; Bo Zhang (Marine Georesources & Geotechnology, 2015)

Host-Choice Behavior of Diaphorina citri Kuwayama (Hemiptera: Psyllidae) Under Laboratory Conditions - Chuan-Qing Ruan; David G. Hall; Bo Liu; Yong-Ping Duan; Tao Li; Han-Qing Hu; Guo-Cheng Fan (Journal of Insect Behavior, 2015)

Natural variation in paternal behavior is associated with central estrogen receptor alpha and oxytocin levels - Yani Li; Zhenmin Lian; Bo Wang; Fadao Tai; Ruiyong Wu; Ping Hao; Xufeng Qiao (Journal of Comparative Physiology A, 2015)

Effect of dexamethasone on the incidence of post-dural puncture headache after spinal anesthesia: a randomized, double-blind, placebo-controlled trial and a meta-analysis - Bo Yang; Dong-Liang Li; Ping Dong; Xi-Yan Zhang; Li Zhang; Jin-Gui Yu (Acta Neurologica Belgica, 2015)

Microneedle-Mediated Delivery of Copper Peptide Through Skin - Hairui Li; Yong Sheng Jason Low; Hui Ping Chong; Melvin T. Zin; Chi-Ying Lee; Bo Li; Melvina Leolukman; Lifeng Kang (Pharmaceutical Research, 2015)

Lead accumulation and tolerance of Moso bamboo (Phyllostachys pubescens) seedlings: applications of phytoremediation - Dan Liu; Song Li; Ejazul Islam; Jun-ren Chen; Jia-sen Wu; Zheng-qian Ye; Dan-li Peng; Wen-bo Yan; Kou-ping Lu (Journal of Zhejiang University-SCIENCE B, 2015)

Molecular cloning and characterization of two novel DREB genes encoding dehydration-responsive element binding proteins in halophyte Suaeda salsa - Xiao-Bo Sun; Hong-Xiang Ma; Xin-Ping Jia; Yu Chen; Xiao-Qing Ye (Genes & Genomics, 2015)

A novel strategy for rapid quantification of 20( S )-protopanaxatriol and 20( S )-protopanaxadiol saponins in Panax notoginseng P. ginseng and P. quinquefolium - Fa-Xiang Xu; Cen Yuan; Jian-Bo Wan; Ru Yan; Hao Hu; Shao-Ping Li; Qing-Wen Zhang (Natural Product Research, 2015)

Genome-wide discovery of novel and conserved microRNAs in white shrimp (Litopenaeus vannamei) - Qian-Yun Xi; Yuan-Yan Xiong; Yuan-Mei Wang; Xiao Cheng; Qi-En Qi; Gang Shu; Song-Bo Wang; Li-Na Wang; Ping Gao; Xiao-Tong Zhu; Qing-Yan Jiang; Yong-Liang Zhang; et al. (Molecular Biology Reports, 2015)

Trace levels of mitomycin C disrupt genomic integrity and lead to DNA damage response defect in long-term-cultured human embryonic stem cells - Di Zhou; Ge Lin; Si-Cong Zeng; Bo Xiong; Ping-Yuan Xie; De-Hua Cheng; Qing Zheng; Qi Ouyang; Xiao-Ying Zhou; Wei-Ling Tang; Yi Sun; Guang-Ying Lu; et al. (Archives of Toxicology, 2015)

Cloning and respond of a cold shock domain protein (CnCSDP) gene to cold stress in noble scallop Chlamys nobilis (Bivalve: Pectinidae) - Ya-Jun Wang; Huai-Ping Zheng; Bo Zhang; He-Lu Liu; Hua-Juan Deng; Long-Hui Deng (Molecular Biology Reports, 2014)

Fibroblast Growth Factor 4 Is Required but not Sufficient for the Astrocyte Dedifferentiation - Guo-Dong Feng; Bao-Rong He; Fan Lu; Lin-Hong Liu; Lingling Zhang; Bo Chen; Zu-Ping He; Ding-Jun Hao; Hao Yang (Molecular Neurobiology, 2014)

Juvenile silver carp Hypophthalmichthys molitrix swim faster in closed surface flow than open surface flow - Xiaotao Shi; Qiuwen Chen; Defu Liu; Yingping Huang; Ping Zhuang; Bo Lu (Environmental Biology of Fishes, 2014)

Synthesis and cytotoxic activities of novel bergenin derivatives - Na-Na Liu; Fu-Kai Bao; Jing-Bo Chen; Xiang-Hui Zeng; Shui-Jing Chi; Jian-Ping Liu (Medicinal Chemistry Research, 2014)

Simultaneous determination by UPLC-MS/MS of seven bioactive compounds in rat plasma after oral administration of Ginkgo biloba tablets: application to a pharmacokinetic study - Wen-ping Wang; Na Liu; Qian Kang; Pei-pei Du; Yi Lan; Bo-chen Zhao; Yan-yan Chen; Qing Zhang; Hui Li; Ye-wen Zhang; Qing Wu (Journal of Zhejiang University-SCIENCE B, 2014)

Effects of hydraulic retention time and nitrobenzene concentration on the performance of sequential upflow anaerobic filter and air lift reactors in treating nitrobenzene-containing wastewater - Jinhua Wu; Guocai Chen; Jingjing Gu; Weizhao Yin; Mengxiong Lu; Ping Li; Bo Yang (Environmental Science and Pollution Research, 2014)

Analysis of the ground settlement control of a large span metro station in Dalian city using the Centre Drift Method - Xin-Bo Ji; Wen Zhao; Shen-Gang Li; Yong-Wei Zhou; Yong-Ping Guan (European Journal of Environmental and Civil Engineering, 2014)

Isolation and functional characterization of a novel rice constitutive promoter - Juan Li; Rong-Fang Xu; Rui-Ying Qin; Hui Ma; Hao Li; Ying-Ping Zhang; Li Li; Peng-Cheng Wei; Jian-Bo Yang (Plant Cell Reports, 2014)

Needle-free injection of insulin powder: delivery efficiency and skin irritation assessment - Chun-yu Li; Zhe-wei Wang; Can Tu; Jia-bo Wang; Bing-qian Jiang; Qi Li; Ling-na Zeng; Zhi-jie Ma; Ping Zhang; Yan-ling Zhao; Ya-ming Zhang; Dan Yan; et al. (Journal of Zhejiang University-SCIENCE B, 2014)

Species-Specific Bioaccumulation of Halogenated Organic Pollutants and Their Metabolites in Fish Serum from an E-Waste Site, South China - Yan-Hong Zeng; Xiao-Jun Luo; Xiao-Bo Zheng; Bin Tang; Jiang-Ping Wu; Bi-Xian Mai (Archives of Environmental Contamination and Toxicology, 2014)

Variation in β-amylase activity and thermostability in Tibetan annual wild and cultivated barley genotypes - Hai-tao Zhang; Tian-long Chen; Bing-lin Zhang; De-zhi Wu; Ye-chang Huang; Fei-bo Wu; Guo-ping Zhang (Journal of Zhejiang University-SCIENCE B, 2014)

Does stocking of filter-feeding fish for production have a cascading effect on zooplankton and ecological state? A study of fourteen (sub)tropical Chinese reservoirs with contrasting nutrient concentrations - Qiuqi Lin; Xiaojun Jiang; Bo-Ping Han; Erik Jeppesen (Hydrobiologia, 2014)

Knockdown of LYRM1 Rescues Insulin Resistance and Mitochondrial Dysfunction Induced by FCCP in 3T3-L1 Adipocytes - Min Zhang; Zhen-Ying Qin; Yong-mei Dai; Yu-Mei Wang; Guan-zhong Zhu; Ya-Ping Zhao; Chen-Bo Ji; Jin-Gai Zhu; Chun-Mei Shi; Jie Qiu; Xin-Guo Cao; Xi-Rong Guo (Cell Biochemistry and Biophysics, 2014)

Differential role of Rac in the basolateral amygdala and cornu ammonis 1 in the reconsolidation of auditory and contextual Pavlovian fear memory in rats - Ping Wu; Zeng-Bo Ding; Shi-Qiu Meng; Hao-Wei Shen; Shi-Chao Sun; Yi-Xiao Luo; Jian-Feng Liu; Lin Lu; Wei-Li Zhu; Jie Shi (Psychopharmacology, 2014)

Prognostic significance of TBX2 expression in non-small cell lung cancer - Bo Hu; Hai-Ping Mu; Yu-Qing Zhang; Chong-Yi Su; Jian-Tao Song; Chong Meng; Dong-Xing Liu (Journal of Molecular Histology, 2014)

Bioactive Equivalence of Combinatorial Components Identified in Screening of an Herbal Medicine - Peng Liu; Hua Yang; Fang Long; Hai-Ping Hao; Xiaojun Xu; Ying Liu; Xiao-Wei Shi; Dan-Dan Zhang; Hao-Chuan Zheng; Qian-Ying Wen; Wen-Wen Li; Hui Ji; et al. (Pharmaceutical Research, 2014)

Molecular cloning and dimorphic expression of growth hormone (gh) in female and male spotted scat Scatophagus argus - Si-Ping Deng; Bo Wu; Chun-Hua Zhu; Guang-Li Li (Fisheries Science, 2014)

A model of sea surface temperature front detection based on a threshold interval - Bo Ping; Fenzhen Su; Yunshan Meng; Shenghui Fang; Yunyan Du (Acta Oceanologica Sinica, 2014)

Fluid Flow-Induced Calcium Response in Osteoclasts: Signaling Pathways - Ping Li; Chenglin Liu; Man Hu; Mian Long; Ding Zhang; Bo Huo (Annals of Biomedical Engineering, 2014)

Adipose-derived stem cells transfected with pEGFP-OSX enhance bone formation during distraction osteogenesis - Qing-guo Lai; Shao-long Sun; Xiao-hong Zhou; Chen-ping Zhang; Kui-feng Yuan; Zhong-jun Yang; Sheng-lei Luo; Xiao-peng Tang; Jiang-bo Ci (Journal of Zhejiang University-SCIENCE B, 2014)

Occurrence and dominance of Cylindrospermopsis raciborskii and dissolved cylindrospermopsin in urban reservoirs used for drinking water supply, South China - Lamei Lei; Liang Peng; Xianghui Huang; Bo-Ping Han (Environmental Monitoring and Assessment, 2014)

Erratum to: Bacillus bingmayongensis sp. nov., isolated from the pit soil of Emperor Qin’s Terra-cotta warriors in China - Bo Liu; Guo-Hong Liu; Gui-Ping Hu; Cetin Sengonca; Nai-Quan Lin; Jian-Yang Tang; Wei-Qi Tang; Ying-Zhi Lin (Antonie van Leeuwenhoek, 2014)

Low-dose Endothelial Monocyte-activating Polypeptide-II Increases Permeability of Blood–tumor Barrier by Caveolae-mediated Transcellular Pathway - Zhen Li; Yun-hui Liu; Yi-xue Xue; Li-bo Liu; Ping Wang (Journal of Molecular Neuroscience, 2014)

Bacillus bingmayongensis sp. nov., isolated from the pit soil of Emperor Qin’s Terra-cotta warriors in China - Bo Liu; Guo-Hong Liu; Gui-Ping Hu; Sengonca Cetin; Nai-Quan Lin; Jian-Yang Tang; Wei-Qi Tang; Ying-Zhi Lin (Antonie van Leeuwenhoek, 2014)

Influence of deep brain stimulation of the subthalamic nucleus on cognitive function in patients with Parkinson’s disease - Bin Wu; Lu Han; Bo-Min Sun; Xiao-Wu Hu; Xiao-Ping Wang (Neuroscience Bulletin, 2014)

Cytotoxicity and enhancement activity of essential oil from Zanthoxylum bungeanum Maxim. as a natural transdermal penetration enhancer - Yi Lan; Qing Wu; Ying-qiu Mao; Qiong Wang; Jing An; Yan-yan Chen; Wen-ping Wang; Bo-chen Zhao; Na Liu; Ye-wen Zhang (Journal of Zhejiang University-SCIENCE B, 2014)

Assessment of wheat variety stability using SSR markers - Li Xin Wang; Hong Bo Li; Tie Cheng Gu; Li Hua Liu; Bin Shuang Pang; Jun Qiu; Chang Ping Zhao (Euphytica, 2014)

Further studies on Toxascaris leonina (Linstow, 1902) (Ascaridida: Ascarididae) from Felis lynx (Linnaeus) and Panthera leo (Linnaeus) (Carnivora: Felidae) - Li-Mei Xue; Jing-Bo Chai; Yan-Ning Guo; Lu-Ping Zhang; Liang Li (Acta Parasitologica, 2014)
Toxascaris leonina (Linstow, 1902) is a most common intestinal parasite of various animals in Felidae and Canidae. In the present paper, light and scanning electron microscopy (SEM) were used to study the morphological aspects of adult worms of this nematode in detail, based on the material collected from Panthera leo (Linnaeus) and Felis lynx (Linnaeus) (Carnivora: Felidae) in China. The results showed that there were some morphometric differences between the present material and the previous studies, including the body size, the width and length of cervical alae, the number of denticles on each lip and the tail length of the female. Previously unreported morphological features were also revealed. These supplementary morphological and morphometric data contributed to a more accurate identification of this worldwide distributed ascarid nematode.

Activation of BKCa Channels Mediates Hippocampal Neuronal Death After Reoxygenation and Reperfusion - Ming Chen; Hong-Yu Sun; Ping Hu; Chun-Fei Wang; Bo-Xing Li; Shu-Ji Li; Jian-Jun Li; Hui-Ying Tan; Tian-Ming Gao (Molecular Neurobiology, 2013)

Mercury speciation and mobility in mine wastes from mercury mines in China - Ping Li; Xinbin Feng; Guangle Qiu; Junfang Zhang; Bo Meng; Jianxu Wang (Environmental Science and Pollution Research, 2013)

Effects of connectivity, dispersal directionality and functional traits on the metacommunity structure of river benthic diatoms - Jing Liu; Janne Soininen; Bo‐Ping Han; Steven A. J. Declerck (Journal of Biogeography, 2013)
Aim Dendritic ecological networks ( DEN s), such as river systems, combine features that challenge the traditional conceptual views and empirical approaches applied to metacommunities. As a result of their dendritic branching geometry and stream flow directionality, they are strongly hierarchical and asymmetrical. We analysed the metacommunity structure of benthic diatoms in a large‐scale river system with the aim of evaluating the importance of potential causal influences. Furthermore, we hypothesized that metacommunities of diatoms that are strongly attached to their substrata show a different spatial structure than metacommunities of other, more weakly attached diatoms. Location The study was carried out in the Dong River, a 32,275 km 2 subtropical river network located in southern China. Methods We surveyed benthic diatom communities during three seasons (dry, intermediate and wet). Using partial redundancy analysis, we partitioned community variation among environmental models and different spatial eigenfunction models to evaluate the influence of alternative dispersal pathways (overland versus water course dispersal), stream directionality, man‐made dams and diatom functional traits on diatom metacommunity structure. Results Models based on hydrological connections and water directionality represent spatial patterns better than overland distances, suggesting that the dynamics of benthic diatom metacommunities are mainly confined to the river network and influenced by the prevailing water flow. We found significant effects of man‐made dams on the spatial structure of important limnological variables and diatom metacommunity structure. The metacommunity of strongly attached diatoms also showed a weaker signature of flow directionality than that of other growth forms, especially in seasons with high water levels. Main conclusions We conclude that the consideration of among‐site connectivity, flow directionality and species traits is key to a better understanding of the spatial ecology of passively dispersing microbial organisms in river systems.

Investigation of individual heterozygosity correlated to growth traits in Tongshan Black-boned goat - Yan Guo Han; Gui Qiong Liu; Xun Ping Jiang; Guo Ming Liang; Chun Bo He; Dang Wei Wang; Yan Wu; Xing Long Xiang; Jie Hu; Yu Qin Peng (Molecular Biology Reports, 2013)

Histone deacetylases inhibitor trichostatin A increases the expression of Dleu2/miR-15a/16-1 via HDAC3 in non-small cell lung cancer - Chi-qi Chen; Cheng-shui Chen; Jun-jie Chen; Lian-ping Zhou; Hong-lei Xu; Wei-wei Jin; Jian-bo Wu; Shen-meng Gao (Molecular and Cellular Biochemistry, 2013)

Global and MGMT promoter hypomethylation independently associated with genomic instability of lymphocytes in subjects exposed to high-dose polycyclic aromatic hydrocarbon - Huawei Duan; Zhini He; Junxiang Ma; Bo Zhang; Zhiguo Sheng; Ping Bin; Juan Cheng; Yong Niu; Haiyan Dong; Han Lin; Yufei Dai; Benzhan Zhu; et al. (Archives of Toxicology, 2013)

Rapid quantitative analysis of diosgenin in the tubers of Dioscorea zingiberensis C.H. Wright by coupling cellulose enzymolysis and two-phase acid hydrolysis in tandem with HPLC-UV - Huan Yang; Bin Chen; Xu-bo Wang; Phen-wei Chue; Yu-ping Shen; Guo-hua Xia; Xiao-bin Jia (Natural Product Research, 2013)

Molecular characteristics and evolutionary analysis of field Marek’s disease virus prevalent in vaccinated chicken flocks in recent years in China - Zu-Hua Yu; Man Teng; Jun Luo; Xin-Wei Wang; Ke Ding; Le-Le Yu; Jing-Wei Su; Jia-Qi Chi; Pu Zhao; Bo Hu; Gai-Ping Zhang; Ju-Xiong Liu (Virus Genes, 2013)

The first complete genomic characterization of an Amur virus isolate from China - Yu Zhang; Bo-Hua Liu; Fang Lin; Yong-Guo Zhang; Bing-Yin Si; Xiao-Ping Kang; Yi Hu; Jing Li; Xiao-Yan Wu; Yu-Chang Li; Qing-Yu Zhu; Yin-Hui Yang (Archives of Virology, 2013)

Separation method for multi-source blended seismic data - Han-Chuang Wang; Sheng-Chang Chen; Bo Zhang; De-Ping She (Applied Geophysics, 2013)

Region-specific role of Rac in nucleus accumbens core and basolateral amygdala in consolidation and reconsolidation of cocaine-associated cue memory in rats - Zeng-Bo Ding; Ping Wu; Yi-Xiao Luo; Hai-Shui Shi; Hao-Wei Shen; Shen-Jun Wang; Lin Lu (Psychopharmacology, 2013)

Up-regulation of Slc39A2(Zip2) mRNA in peripheral blood mononuclear cells from patients with pulmonary tuberculosis - Yan-ting Tao; Qing Huang; Ya-li Jiang; Xiao-lei Wang; Ping Sun; Yuanyuan Tian; Hai-liang Wu; Min Zhang; Si-bo Meng; Yu-shu Wang; Qing Sun; Lian-ying Zhang (Molecular Biology Reports, 2013)

Factors underlying the association of body mass index with serum ALT in Chinese hypertensive adults without known hepatic diseases - Yan Zhang; Xian-hui Qin; Jian-ping Li; Yi-min Cui; Ze-yuan Liu; Zhi-gang Zhao; Jun-bo Ge; De-ming Guan; Jian Hu; Yan-ni Wang; Fu-min Zhang; Xin Xu; et al. (Journal of Zhejiang University-SCIENCE B, 2013)

Inhibitory effect of curcumin analogs on tissue factor procoagulant activity and their preliminary structure–activity relationships - Hai-Xia Ge; Ling Chen; Jian Zhang; Jun-Ping Kou; Bo-Yang Yu (Medicinal Chemistry Research, 2013)

Adsorption of methylene blue onto activated carbon produced from tea (Camellia sinensis L.) seed shells: kinetics, equilibrium, and thermodynamics studies - Jun-jie Gao; Ye-bo Qin; Tao Zhou; Dong-dong Cao; Ping Xu; Danielle Hochstetter; Yue-fei Wang (Journal of Zhejiang University-SCIENCE B, 2013)

Reducing the oxidative stress mediates the cardioprotection of bicyclol against ischemia-reperfusion injury in rats - Jie Cui; Zhi Li; Ling-bo Qian; Qin Gao; Jue Wang; Meng Xue; Xiao-e Lou; Iain C. Bruce; Qiang Xia; Hui-ping Wang (Journal of Zhejiang University-SCIENCE B, 2013)

Preface: Conservation, management, and restoration of shallow lake ecosystems facing multiple stressors - Zhengwen Liu; Bo-Ping Han; Ramesh D. Gulati (Hydrobiologia, 2013)

Predation pressure induced by seasonal fishing moratorium changes the dynamics of subtropical Cladocera populations - Qiuqi Lin; Pingping Zhao; Qiuting Wu; Zhihong Wei; Huiming Li; Bo-Ping Han (Hydrobiologia, 2013)

Erratum to: Synergistic effect and mechanism of vitamin A and vitamin D on inducing apoptosis of prostate cancer cells - Jianjun Sha; Jiahua Pan; Ping Ping; Hanqing Xuan; Dong Li; Juanjie Bo; Dongming Liu; Yiran Huang (Molecular Biology Reports, 2013)

Expression of the MSI-99m Gene in Transgenic Potato Plants Confers Resistance to Phytophthora infestans and Ralstonia solanacearum - Yong-bo Hong; Shui-ping Liu; Yan-ping Zhu; Chao Xie; Deng-wei Jue; Min Chen; Hubdar Ali Kaleri; Qing Yang (Plant Molecular Biology Reporter, 2013)

Synergistic effect and mechanism of vitamin A and vitamin D on inducing apoptosis of prostate cancer cells - Jianjun Sha; Jiahua Pan; Ping Ping; Hanqing Xuan; Dong Li; Juanjie Bo; Dongming Liu; Yiran Huang (Molecular Biology Reports, 2013)

Statin use and risk of bladder cancer: a meta-analysis - Xiao-long Zhang; Jiang Geng; Xiao-peng Zhang; Bo Peng; Jian-ping Che; Yang Yan; Guang-chun Wang; Sheng-qiang Xia; Yan Wu; Jun-hua Zheng (Cancer Causes & Control, 2013)

Analysis of selected singleton transposable elements (SSTEs) and their application for the development of land PATE markers in Magnaporthe oryzae - Hong-yan Zhang; Dong-yang He; Teerapong Kasetsomboon; Heng Zhou; Ping Li; Xiang-long Li; Chatchawan Jantasuriyarat; Bo Zhou (Journal of General Plant Pathology, 2013)

Wnt/β-catenin signaling induces the aging of mesenchymal stem cells through promoting the ROS production - Da-yong Zhang; Yu Pan; Chong Zhang; Bing-xi Yan; Shan-shan Yu; Dong-ling Wu; Meng-meng Shi; Kai Shi; Xin-xiao Cai; Shuang-shuang Zhou; Jun-bo Wang; Jian-ping Pan; et al. (Molecular and Cellular Biochemistry, 2013)

Evaluation of landslide risk based on synchronization of nonlinear motions in observed data - Da-Chao Lin; Jing-Luo Cai; Zhang-Lin Guo; Fan-Lei Zeng; Feng-Ping An; Hai-Bo Liu (Natural Hazards, 2013)

The relationship between carbon and nitrogen stable isotopes of zooplankton and select environmental variables in low-latitude reservoirs - Wei Hou; Binhe Gu; Huajun Zhang; Jiguang Gu; Bo-Ping Han (Limnology, 2013)

Analysis of genetic diversity in the tuber mustard (Brassica juncea var. tumida Tsen et Lee) in the Yangtze river basin of China - Ping Fang; Fa-Bo Chen; Qi-Lun Yao; Ke-Cheng Yang; Guang-Fan Zhou; Yong-Hong Fan; Zhao-Rong Zhang; Jin-Juan Shen; Hong Zhang (Genetic Resources and Crop Evolution, 2013)

Roles of α-linolenic acid on IGF-I secretion and GH/IGF system gene expression in porcine primary hepatocytes - Xin-Ling Fang; Gang Shu; Zhi-Qi Zhang; Song-Bo Wang; Xiao-Tong Zhu; Ping Gao; Qian-Yun Xi; Yong-Liang Zhang; Qing-Yan Jiang (Molecular Biology Reports, 2012)

Identification and characterization of a gene encoding a putative lysophosphatidyl acyltransferase from Arachis hypogaea - Si-Long Chen; Jia-Quan Huang; Yong Lei; Yue-Ting Zhang; Xiao-Ping Ren; Yu-Ning Chen; Hui-Fang Jiang; Li-Ying Yan; Yu-Rong Li; Bo-Shou Liao (Journal of Biosciences, 2012)

Enhanced overall resistance to Fusarium seedling blight and Fusarium head blight in transgenic wheat by co-expression of anti-fungal peptides - Zheng-Wei Liu; He-Ping Li; Wei Cheng; Peng Yang; Jing-Bo Zhang; An-Dong Gong; Yan-Ni Feng; W. G. Dilantha Fernando; Yu-Cai Liao (European Journal of Plant Pathology, 2012)

Numerical modeling of PP- and PS-wave azimuthal anisotropy in HTI media - Zhong-Ping Qian; Shao-Hua Zhang; Bo Zhao; Na Lei; Xiang-Yang Li (Applied Geophysics, 2012)

Integrated Analysis on Gravity and Magnetic Fields of the Hailar Basin, NE China: Implications for Basement Structure and Deep Tectonics - Bin Sun; Liangshu Wang; Ping Dong; YongJing Wu; Changbo Li; Bo Hu; Chong Wang (Pure and Applied Geophysics, 2012)

Effects of drought stress on phosphorus and potassium uptake dynamics in summer maize (Zea mays) throughout the growth cycle - Ti-Da Ge; Ning-Bo Sun; Li-Ping Bai; Chen-Li Tong; Fang-Gong Sui (Acta Physiologiae Plantarum, 2012)

Participation of Gab1 and Gab2 in IL-22-mediated keratinocyte proliferation, migration, and differentiation - Xiaofang Zhu; Zhongliang Li; Wenyan Pan; Lu Qin; Guoqiang Zhu; Yuehai Ke; Jie Wu; Ping Bo; Songshu Meng (Molecular and Cellular Biochemistry, 2012)

Sequence and phylogenetic analysis of H7N3 avian influenza viruses isolated from poultry in China in 2011 - Wu Hai-bo; Lu Ru-feng; Wo En-kang; You Jin-biao; Wang Yi-ting; Wang Qiao-gang; Xu Li-hua; Wu Nan-ping; Guo Chao-tan (Archives of Virology, 2012)

Sprout vacuum-infiltration: a simple and efficient agroinoculation method for virus-induced gene silencing in diverse solanaceous species - Hua-xue Yan; Da-qi Fu; Ben-zhong Zhu; Hai-ping Liu; Xiao-ying Shen; Yun-bo Luo (Plant Cell Reports, 2012)

Correlation between serum CA724 and gastric cancer: multiple analyses based on Chinese population - Xin-Zu Chen; Wei-Ke Zhang; Kun Yang; Lan-Lan Wang; Jin Liu; Li Wang; Jian-Kun Hu; Bo Zhang; Zhi-Xin Chen; Jia-Ping Chen; Zong-Guang Zhou; Xian-Ming Mo (Molecular Biology Reports, 2012)

Signal Mechanisms Underlying Low-Dose Endothelial Monocyte-Activating Polypeptide-II-Induced Opening of the Blood–Tumor Barrier - Zhen Li; Yun-hui Liu; Yi-xue Xue; Li-bo Liu; Ping Wang (Journal of Molecular Neuroscience, 2012)

The expression of pentraxin 3 and tumor necrosis factor-alpha is increased in preeclamptic placental tissue and maternal serum - Ping Zhou; Xin Luo; Hong-bo Qi; Wen-jun Zong; Hua Zhang; Dan-dan Liu; Qing-shu Li (Inflammation Research, 2012)

Fluid Flow-Induced Calcium Response in Early or Late Differentiated Osteoclasts - Ping Li; Man Hu; Shujin Sun; Yan Zhang; Yuxin Gao; Mian Long; Bo Huo; Ding Zhang (Annals of Biomedical Engineering, 2012)

Gossypol‐enhanced P450 gene pool contributes to cotton bollworm tolerance to a pyrethroid insecticide - XIAO‐YUAN TAO; XUE‐YI XUE; YONG‐PING HUANG; XIAO‐YA CHEN; YING‐BO MAO (Molecular Ecology, 2012)
Cotton plants accumulate phytotoxins, including gossypol and related sesquiterpene aldehydes, to resist insect herbivores and pathogens. To counteract these defensive plant secondary metabolites, cotton bollworms ( Helicoverpa armigera ) elevate their production of detoxification enzymes, including cytochrome P450 monooxygenases (P450s). Besides their tolerance to phytotoxin, cotton bollworms have quickly developed resistance to deltamethrin, a widely used pyrethroid insecticide in cotton field. However, the relationship between host plant secondary metabolites and bollworm insecticide resistance is poorly understood. Here, we show that exogenously expressed CYP6AE14, a gossypol‐inducible P450 of cotton bollworm, has epoxidation activity towards aldrin, an organochlorine insecticide, indicating that gossypol‐induced P450s participate in insecticide metabolism. Gossypol‐ingested cotton bollworm larvae showed higher midgut P450 enzyme activities and exhibited enhanced tolerance to deltamethrin. The midgut transcripts of bollworm larvae administrated with different phytochemicals and deltamethrin were then compared by microarray analysis, which showed that gossypol and deltamethrin induced the most similar P450 expression profiles. Gossypol‐induced P450s exhibited high divergence and at least five of them ( CYP321A1 , CYP9A12 , CYP9A14 , CYP6AE11 and CYP6B7 ) contributed to cotton bollworm tolerance to deltamethrin. Knocking down one of them, CYP9A14 , by plant‐mediated RNA interference (RNAi) rendered the larvae more sensitive to the insecticide. These data demonstrate that generalist insects can take advantage of secondary metabolites from their major host plants to elaborate defence systems against other toxic chemicals, and impairing this defence pathway by RNAi holds a potential for reducing the required dosages of agrochemicals in pest control.

Transgenic Potato Plants Expressing StoVe1 Exhibit Enhanced Resistance to Verticillium dahliae - Shui-ping Liu; Yan-ping Zhu; Chao Xie; Deng-wei Jue; Yong-bo Hong; Min Chen; Ali Kaleri Hubdar; Qing Yang (Plant Molecular Biology Reporter, 2012)

Renal insufficiency is an independent predictor of in-hospital mortality for patients with acute myocardial infarction receiving primary percutaneous coronary intervention - Jian-ping Li; Mohetaboer Momin; Yong Huo; Chun-yan Wang; Yan Zhang; Yan-jun Gong; Zhao-ping Liu; Xin-gang Wang; Bo Zheng (Journal of Zhejiang University-SCIENCE B, 2012)

Characterization and virus susceptibility of a skin cell line from red-spotted grouper (Epinephelus akaara) - Xiao-Ying Lei; Zhong-Yuan Chen; Li-Bo He; Chao Pei; Xiu-Ping Yuan; Qi-Ya Zhang (Fish Physiology and Biochemistry, 2012)

Analyses of n-alkanes degrading community dynamics of a high-temperature methanogenic consortium enriched from production water of a petroleum reservoir by a combination of molecular techniques - Lei Zhou; Kai-Ping Li; Serge Maurice Mbadinga; Shi-Zhong Yang; Ji-Dong Gu; Bo-Zhong Mu (Ecotoxicology, 2012)

Survivals of D. galeata in sub-tropical reservoirs: harmful effects of toxic cyanobacteria in food source - Bo-Ping Han; Xian Lin; Lamei Lei; Jiguang Gu (Ecotoxicology, 2012)

Controlling subsidence caused by de-watering in a deep foundation pit - Jianxiu Wang; Bo Feng; Yan Liu; Lingao Wu; Yanfei Zhu; Xingsheng Zhang; Yiqun Tang; Ping Yang (Bulletin of Engineering Geology and the Environment, 2012)

Genomic organization and sequence dynamics of the AvrPiz-t locus in Magnaporthe oryzae - Ping Li; Bin Bai; Hong-yan Zhang; Heng Zhou; Bo Zhou (Journal of Zhejiang University-SCIENCE B, 2012)

Identification of a new Bombyx mori nucleopolyhedrovirus and analysis of its bro gene family - Jing-Bo Zhou; Xing-Qi Li; Wanchai De-Eknamkul; Siripuk Suraporn; Jia-Ping Xu (Virus Genes, 2012)

Genetic characterization of subtype H1 avian influenza viruses isolated from live poultry markets in Zhejiang Province, China, in 2011 - Hai-bo Wu; Chao-tan Guo; Ru-feng Lu; Li-hua Xu; En-kang Wo; Jin-biao You; Yi-ting Wang; Qiao-gang Wang; Nan-ping Wu (Virus Genes, 2012)

Characterization of a highly pathogenic H5N1 avian influenza virus isolated from ducks in Eastern China in 2011 - Wu Hai-bo; Guo Chao-tan; Lu Ru-feng; Xu Li-hua; Wo En-kang; You Jin-biao; Wang Yi-ting; Wang Qiao-gang; Wu Nan-ping (Archives of Virology, 2012)

Spontaneous retroperitoneal hemorrhage after hemodialysis involving anticoagulant agents - Wen-xing Fan; Zheng-xu Deng; Fang Liu; Rong-bo Liu; Ling He; Bogati Amrit; Li Zang; Jing-wen Li; Xian-rong Liu; Song-min Huang; Ping Fu (Journal of Zhejiang University-SCIENCE B, 2012)

Effect of high dietary carbohydrate on growth, serum physiological response, and hepatic heat shock cognate protein 70 expression of the top-mouth culter Erythroculter ilishaeformis Bleeker - Bo Liu; Jun Xie; Xian-ping Ge; Ling-hong Miao; Guangyu Wang (Fisheries Science, 2012)

The interaction of blood proteins with brucine - Hong-Mei Zhang; Zheng-Hao Fei; Bo-Ping Tang; Jian Chen; Wei-Hua Tao; Yan-Qing Wang (Molecular Biology Reports, 2012)

ASYMMETRIC LEAVES2 gene, a member of LOB/AS2 family of Arabidopsis thaliana, causes an abaxializing leaves in transgenic cockscomb - Shao-Bo Sun; Jiang-Ping Song; Lai-Sheng Meng (Molecular Biology Reports, 2012)

H. pylori related proinflammatory cytokines contribute to the induction of miR-146a in human gastric epithelial cells - Na Li; Xiang Xu; Bin Xiao; En-Dong Zhu; Bo-sheng Li; Zhen Liu; Bin Tang; Quan-Ming Zou; Hua-Ping Liang; Xu-Hu Mao (Molecular Biology Reports, 2012)

An Accurate Method of Computing the Gradient of Seismic Wave Reflection Coefficients (SWRCs) for the Inversion of Stratum Parameters - Xiao-Bo Liu; Fu-Ping Liu; Xian-Jun Meng; Jia-Qi Xiao (Surveys in Geophysics, 2012)

Genetic polymorphism analysis of killer cell immunoglobulin-like receptor genes in the Chinese Uygur population - Hong-dan Wang; Bo-feng Zhu; Chun-mei Shen; Guo-lian Yuan; Guang Yang; Juan-ning Guo; Jiang-wei Yan; Hai-xia Qin; Jian-xin Guo; Li-ping Zhang; Xiao-qin Jia; Rudolf Lucas (Molecular Biology Reports, 2012)

Role of RhoA/ROCK Signaling in Endothelial-Monocyte-Activating Polypeptide II Opening of the Blood–Tumor Barrier - Hui Xie; Yi-xue Xue; Li-bo Liu; Yun-hui Liu; Ping Wang (Journal of Molecular Neuroscience, 2012)

Begomovirus–whitefly mutualism is achieved through repression of plant defences by a virus pathogenicity factor - TONG ZHANG; JUN‐BO LUAN; JIN‐FENG QI; CHANG‐JUN HUANG; MENG LI; XUE‐PING ZHOU; SHU‐SHENG LIU (Molecular Ecology, 2012)
Plant‐mediated interactions between herbivorous arthropods and pathogens transmitted by herbivores are important determinants of the population dynamics of both types of organisms in the field. The role of plant defence in mediating these types of tripartite interactions have been recognized but rarely examined especially at the physiological and molecular levels. Our previous work shows that a worldwide invasive whitefly can establish mutualism with the begomovirus Tomato yellow leaf curl China virus (TYLCCNV) via crop plants. Here, we show that TYLCCNV and betasatellite co‐infection suppresses jasmonic acid defences in the plant. Impairing or enhancing defences mediated by jasmonic acid in the plant enhances or depresses the performance of the whitefly. We further demonstrate that the pathogenicity factor βC1 encoded in the betasatellite is responsible for the initiation of suppression on plant defences and contributes to the realization of the virus–vector mutualism. By integrating ecological, mechanistic and molecular approaches, our study reveals a major mechanism of the plant‐mediated mutualism between a virus and its vector. As the test plant is an important economic crop, the results also have substantial implications for developing novel strategies for management of crop viruses and the insect vectors associated with them.

Polymorphisms of XRCC1 and gastric cancer susceptibility: a meta-analysis - Bo Chen; Yong Zhou; Ping Yang; Xiao-Ting Wu (Molecular Biology Reports, 2012)

Integrated expression of the α-amylase, dextranase and glutathione gene in an industrial brewer’s yeast strain - Jin-Jing Wang; Zhao-Yue Wang; Xiu-Ping He; Bo-Run Zhang (World Journal of Microbiology and Biotechnology, 2012)

Xanthoceraside attenuates amyloid β peptide25–35-induced learning and memory impairments in mice - Ping Lu; Takayoshi Mamiya; Lingling Lu; Akihiro Mouri; Takashi Ikejima; Hyoung-Chum Kim; Li-Bo Zou; Toshitaka Nabeshima (Psychopharmacology, 2012)

A meta-analysis of HLA-DR polymorphism and genetic susceptibility to idiopathic dilated cardiomyopathy - Bo Jin; Xin-Ping Luo; Huan-Chun Ni; Wei Shen; Hai-Ming Shi; Yong Li (Molecular Biology Reports, 2012)

Hydrodynamic change recorded by diatoms in sediments of Liuxihe Reservoir, southern China - Jing Liu; Zhangwen Lin; Huajun Zhang; Bo-Ping Han (Journal of Paleolimnology, 2012)

A Promising CdSe@CdS-Quantum Dots-Cysteine for the Determination of Trace IgE by Solid Substrate Room Temperature Phosphorescence Immunoassay - Jia-Ming Liu; Li-ping Lin; Zhen-Bo Liu; Min-Lan Yang; Xin-xing Wang; Li-hong Zhang; Ma-lin Cui; Li Jiao (Journal of Fluorescence, 2012)

Mitochondrial DNA diversity of Glyptothorax zanaensis (Wu et al., 1981) populations in Nu River, China - Xi-Ping Yuan; Yuan-An Wu; Bo Hong; Deng-Qiang Wang; Shao-Ping Liu; Da-Qing Chen (Environmental Biology of Fishes, 2012)

Determination of aflatoxins in edible oil from markets in Hebei Province of China by liquid chromatography–tandem mass spectrometry - Li-xin Yang; Yin-ping Liu; Hong Miao; Bin Dong; Na-jing Yang; Feng-qi Chang; Li-xue Yang; Jing-bo Sun (Food Additives & Contaminants Part B-Surveillance, 2011)

Parallel synthesis of novel antitumor agents: 1,2,3-triazoles bearing biologically active sulfonamide moiety and their 3D-QSAR - Lili Ou; Shuang Han; Wenbo Ding; Ping Jia; Bo Yang; Jose L. Medina-Franco; Marc A. Giulianotti; Jian-Zhong Chen; Yongping Yu (Molecular Diversity, 2011)

New epothilone congeners from Sorangium cellulosum strain So0157-2 - Ji-Dong Wang; Nan Jiang; Hui Zhang; Lin-Ping Ying; Chuan-Xi Wang; Wen-Sheng Xiang; Bo Wu; Hai-Bin Wang; Hua Bai (Natural Product Research, 2011)

Role of death receptor, mitochondrial and endoplasmic reticulum pathways in different stages of degenerative human lumbar disc - Hua Wang; Hui Liu; Zhao-Min Zheng; Kui-Bo Zhang; Tai-Ping Wang; Shilabant-Sen Sribastav; Wen-Sheng Liu; Ting Liu (Apoptosis, 2011)

Overexpressing Arabidopsis KNAT1 gene in Celosia plumosus L. causes modification of plant morphology - Shao-Bo Sun; Jiang-Ping Song; Jing Yang (Acta Physiologiae Plantarum, 2011)

Roles of Bcl-2 family members, PI3K and NF-κB pathways in Escherichia coli-induced apoptosis in human monocytic U937 cells - Jia-He Wang; Bo Yu; Ping He; Xue Bai (World Journal of Microbiology and Biotechnology, 2011)

The effects of simvastatin on angiogenesis: studied by an original model of atherosclerosis and acute myocardial infarction in rabbit - Wei Shen; Hai-Ming Shi; Wei-Hu Fan; Xin-Ping Luo; Bo Jin; Yong Li (Molecular Biology Reports, 2011)

Assessment of spatial distribution of soil loss over the upper basin of Miyun reservoir in China based on RS and GIS techniques - Tao Chen; Rui-qing Niu; Yi Wang; Ping-xiang Li; Liang-pei Zhang; Bo Du (Environmental Monitoring and Assessment, 2011)

Mimecan is involved in aortic hypertrophy induced by sinoaortic denervation in rats - Xiao-Song Gu; Jun-Ping Lei; Jian-Bo Shi; Wen-ling Lian; Xiang Yang; Xing Zheng; Yong-Wen Qin (Molecular and Cellular Biochemistry, 2011)

Isolation and expression analysis of LEA genes in peanut (Arachis hypogaea L.) - Lei Su; Chuan-Zhi Zhao; Yu-Ping Bi; Shu-Bo Wan; Han Xia; Xing-Jun Wang (Journal of Biosciences, 2011)

Why is Diaphanosoma (Crustacea: Ctenopoda) so common in the tropics? Influence of temperature and food on the population parameters of Diaphanosoma dubium, and a hypothesis on the nature of tropical cladocerans - Bo-Ping Han; Juan Yin; Xian Lin; Henri J. Dumont (Hydrobiologia, 2011)

Genotypic differences in callus induction and plant regeneration from mature embryos of barley (Hordeum vulgare L.) - Yong Han; Xiao-li Jin; Fei-bo Wu; Guo-ping Zhang (Journal of Zhejiang University-SCIENCE B, 2011)

Molecular characterisation of cereal cyst nematodes in winter wheat on the Huang-Huai floodplain of China using RFLP and rDNA-ITS sequence analyses - Bo Fu; Hong-xia Yuan; Yu Zhang; Xing-song Hou; Gao-lei Nian; Peng Zhang; Xiao-ping Xing; Bing-jian Sun; Ian T. Riley; Hong-lian Li (Australasian Plant Pathology, 2011)

Why Baltic herring and sprat are weak conduits for astaxanthin from zooplankton to piscivorous fish - Xiang-Ping Nie; Jenny Zie; Norbert Häubner; Bo Tallmark; Pauline Snoeijs (Limnology and Oceanography, 2011)
Atlantic salmon living in the brackish Baltic Sea have lower muscle pigmentation than populations elsewhere. The pigment in question is the antioxidant and vitamin A precursor astaxanthin, which is synthesized by crustaceans from algal carotenoids. Baltic salmon feed nearly exclusively on the clupeids sprat and herring. To evaluate astaxanthin availability to salmon we assessed astaxanthin levels and isomeric composition in their prey fish. We also analyzed astaxanthin dynamics in the dominant piscivorous fish in the Baltic Sea, the Atlantic cod. The geometrical E ‐ ( trans ‐) and Z ‐ ( cis ‐) isomers were distributed selectively in fish tissues, with highest E : Z ratios in salmon gonads (82 : 18) and lowest in herring gonads (24 : 76). Sprat and herring are not ideal prey with respect to their high whole‐body concentrations of Z ‐isomers, which have low bioavailability for salmon and cod. These Z ‐isomers predominantly accumulate in the clupeid gonads. A crucial mechanism for the transport of astaxanthin from clupeids to piscivores is the direct transfer of crustacean astaxanthin (mainly all‐ E ) from the clupeid stomachs. Low stomach astaxanthin content in clupeids decreases total astaxanthin transfer to higher trophic levels. In autumn, herring stomachs (including contents) had 12.5 times lower astaxanthin concentrations than sprat stomachs, and herring had 2.8 times less whole‐body all‐ E ‐astaxanthin (by weight) than sprat. These results confirm recent reports of starvation in the Baltic herring, which may further decrease astaxanthin levels in the Baltic salmon. Cod did not have lower astaxanthin levels than their Atlantic counterpart, which may be attributed to their lower need for astaxanthin and higher food diversity.

Analysis of time-course gene expression profiles of sinusoidal endothelial cells during liver regeneration in rats - Cun-shuan Xu; Xiao-guang Chen; Cui-fang Chang; Gai-ping Wang; Wen-bo Wang; Lian-xing Zhang; Qiu-shi Zhu; Lei Wang (Molecular and Cellular Biochemistry, 2011)

Comparative research of chemical constituents and bioactivities between petroleum ether extracts of the aerial part and the rhizome of Atractylodes macrocephala - Wei Peng; Ting Han; Wen-Bo Xin; Xiao-Gang Zhang; Qiao-Yan Zhang; Min Jia; Lu-Ping Qin (Medicinal Chemistry Research, 2011)

Efficacy and safety of escitalopram versus citalopram in major depressive disorder: a 6-week, multicenter, randomized, double-blind, flexible-dose study - Jian-Jun Ou; Guang-Lei Xun; Ren-Rong Wu; Le-Hua Li; Mao-Sheng Fang; Hong-Geng Zhang; Shi-Ping Xie; Jian-Guo Shi; Bo Du; Xue-Qin Yuan; Jing-Ping Zhao (Psychopharmacology, 2011)

Disturbed tooth germ development in the absence of MINT in the cultured mouse mandibular explants - Ming-Hui Zhu; Wen-Bo Dong; Guang-Ying Dong; Ping Zhang; Yong-Jin Chen; Bu-Ling Wu; Hua Han (Molecular Biology Reports, 2011)

Improvement of acetic acid tolerance and fermentation performance of Saccharomyces cerevisiae by disruption of the FPS1 aquaglyceroporin gene - Jun-Guo Zhang; Xiu-Ying Liu; Xiu-Ping He; Xue-Na Guo; Ying Lu; Bo-run Zhang (Biotechnology Letters, 2011)

Determination of Trace Deoxyribonucleic Acid by Using Fluorescein Isothiocyanate-Phenosafranine as a Double-Luminescent Phosphorescence Probe - Jia-Ming Liu; Xiao-Mei Huang; Zhen-Bo Liu; Fei-Ming Li; Li-Ping Lin; Xin-Xing Wang; Chang-Qing Lin; Ya-Hong Huang; Zhi-Ming Li; Shao-Qin Lin (Journal of Fluorescence, 2011)

Pelagic flatworm predation on daphniids in a subtropical reservoir: different effects on Daphnia galeata and on Ceriodaphnia quadrangula - Tian Wang; Lijuan Xiao; Qiuqi Lin; Bo-Ping Han; Henri J. Dumont (Hydrobiologia, 2011)

Population genetic analysis of 15 autosomal STR loci in the Russian population of northeastern Inner-Mongolia, China - Bo-feng Zhu; Guang Yang; Chun-mei Shen; Hai-xia Qin; Shuan-liang Fan; Li-bin Deng; Feng Chen; Li-ping Chen; Hong-dan Wang; Zhen-yuan Wang; Rudolf Lucas; Zhen-min Lian (Molecular Biology Reports, 2010)

Protein structure alignment based on internal coordinates - Yue-Feng Shen; Bo Li; Zhi-Ping Liu (Interdisciplinary Sciences: Computational Life Sciences, 2010)

Transgenic barley with overexpressed PTrx increases aluminum resistance in roots during germination - Qiao-yun Li; Hong-bin Niu; Jun Yin; Hong-bo Shao; Ji-shan Niu; Jiang-ping Ren; Yong-chun Li; Xiang Wang (Journal of Zhejiang University-SCIENCE B, 2010)

Use of the pyrG gene as a food-grade selection marker in Monascus - Bo-hua Wang; Yang Xu; Yan-ping Li (Biotechnology Letters, 2010)

NYGGF4 homologous gene expression in 3T3-L1 adipocytes: regulation by FFA and adipokines - Ya-ping Zhao; Chun-mei Zhang; Chun Zhu; Xiao-hui Chen; Jia-lin Wang; Chen-bo Ji; Xia Chi; Qin Hong; Yu-zhu Peng; Xi-rong Guo (Molecular Biology Reports, 2010)

The interaction of lysozyme with caffeine, theophylline and theobromine in solution - Hong-Mei Zhang; Bo-Ping Tang; Yan-Qing Wang (Molecular Biology Reports, 2010)

Characterization of Five Putative Acyl Carrier Protein (ACP) Isoforms from Developing Seeds of Arachis hypogaea L. - Meng-Jun Li; Xing-Jun Wang; Lei Su; Yu-Ping Bi; Shu-Bo Wan (Plant Molecular Biology Reporter, 2010)

Cardiac matrix remodeling following intracoronary cell transplantation in dilated cardiomyopathic rabbits - Bo Jin; Xin-Ping Luo; Huan-Chun Ni; Yong Li; Hai-Ming Shi (Molecular Biology Reports, 2010)

A hybrid promoter-containing vector for direct cloning and enhanced expression of PCR-amplified ORFs in mammalian cells - Lei-ming You; Jun Luo; Ai-ping Wang; Gai-ping Zhang; Hai-bo Weng; Ya-nan Guo; Yun-chao Liu; Qiao-mu Li; Man Teng (Molecular Biology Reports, 2010)

Validity and reliability testing of the Chinese (mainland) version of the 39-item Parkinson’s Disease Questionnaire (PDQ-39) - Wei Luo; Xiao-hong Gui; Bo Wang; Wen-ying Zhang; Zhi-yuan Ouyang; Yi Guo; Bao-rong Zhang; Mei-ping Ding (Journal of Zhejiang University-SCIENCE B, 2010)

Decadal variability of the Kuroshio Extension: mesoscale eddies and recirculations - Bunmei Taguchi; Bo Qiu; Masami Nonaka; Hideharu Sasaki; Shang-Ping Xie; Niklas Schneider (Ocean Dynamics, 2010)

Prestack Gaussian beam depth migration under complex surface conditions - Yu-Bo Yue; Zhen-Chun Li; Ping Zhang; Xue-Feng Zhou; Ning Qin (Applied Geophysics, 2010)

Microbial community analysis in crab ponds by denaturing gradient gel electrophoresis - Yan Fen Cheng; Qun Lan Zhou; Jun Xie; Xian Ping Ge; Wei-Yun Zhu; Bo Liu (World Journal of Microbiology and Biotechnology, 2010)

Bacterial melanin interacts with double-stranded DNA with high affinity and may inhibit cell metabolism in vivo - Jing Geng; Peng Yuan; Chun Shao; Sheng-Bing Yu; Bo Zhou; Ping Zhou; Xiang-Dong Chen (Archives of Microbiology, 2010)

Chloroplast transformation of rapeseed (Brassica napus) by particle bombardment of cotyledons - Lin Cheng; He-Ping Li; Bo Qu; Tao Huang; Jin-Xing Tu; Ting-Dong Fu; Yu-Cai Liao (Plant Cell Reports, 2010)

Isolation of high quality RNA and construction of a suppression subtractive hybridization library from ramie (Boehmeria nivea L. Gaud.) - Xu-xia Wang; Bo Wang; Li-jun Liu; Xiao-ping Cui; Jin-yu Yang; Hui Wang; Hui Jiang; Bei-bei Luo; Zhu Long; Wen-xiang Dou; Na Zhang; Ding-xiang Peng (Molecular Biology Reports, 2010)

Identification and characterization of the Enterobacter complex causing mulberry (Morus alba) wilt disease in China - Guo-Fen Wang; Guan-Lin Xie; Bo Zhu; Jun-Sheng Huang; Bo Liu; Praphat Kawicha; Lesley Benyon; Yong-Ping Duan (European Journal of Plant Pathology, 2010)

Fuzzy Approximate Entropy Analysis of Chaotic and Natural Complex Systems: Detecting Muscle Fatigue Using Electromyography Signals - Hong-Bo Xie; Jing-Yi Guo; Yong-Ping Zheng (Annals of Biomedical Engineering, 2010)

Isolation and Characterization of Putative Acetyl-CoA Carboxylases in Arachis hypogaea L. - Meng-Jun Li; Han Xia; Chuan-Zhi Zhao; Ai-Qin Li; Chang-Sheng Li; Yu-Ping Bi; Shu-Bo Wan; Xing-Jun Wang (Plant Molecular Biology Reporter, 2010)

Identification of QTLs for yield and yield components of barley under different growth conditions - Da-wei Xue; Mei-xue Zhou; Xiao-qin Zhang; Song Chen; Kang Wei; Fan-rong Zeng; Ying Mao; Fei-bo Wu; Guo-ping Zhang (Journal of Zhejiang University-SCIENCE B, 2010)

Sanchi ginseng (Panax notoginseng (Burkill) F. H. Chen) in China: distribution, cultivation and variations - Hong Bo Guo; Xiu Ming Cui; Na An; Ge Ping Cai (Genetic Resources and Crop Evolution, 2010)

Expression of the apoptosis-related proteins caspase-3 and NF-κB in the hippocampus of Tg2576 mice - Yan-Li Niu; Wei-Juan Zhang; Ping Wu; Bin Liu; Guo-Tao Sun; Dong-Ming Yu; Jin-Bo Deng (Neuroscience Bulletin, 2010)

Distributions of HLA-A and -B alleles and haplotypes in the Yi ethnic minority of Yunnan, China: relationship to other populations - Bo-feng Zhu; Guang Yang; Chun-mei Shen; Hai-xia Qin; Shun-zhi Liu; Ya-jun Deng; Shuan-liang Fan; Li-bin Deng; Feng Chen; Ping Zhang; Jie Fang; Li-ping Chen; et al. (Journal of Zhejiang University-SCIENCE B, 2010)

A comparative study of pattern synchronization detection between neural signals using different cross-entropy measures - Hong-Bo Xie; Jing-Yi Guo; Yong-Ping Zheng (Biological Cybernetics, 2010)

A new dinorclerone diterpenoid glycoside from Tinospora sinensis - Lang-Ping Dong; Chang-Xiang Chen; Wei Ni; Bai-Bo Xie; Jun-Zhu Li; Hai-Yang Liu (Natural Product Research, 2010)

Pancreatic somatostatinoma with obscure inhibitory syndrome and mixed pathological pattern - Bo Zhang; Qiu-ping Xie; Shun-liang Gao; Yan-biao Fu; Yu-lian Wu (Journal of Zhejiang University-SCIENCE B, 2010)

Correlation Analysis Between Bone Mineral Density and Serum Element Contents of Postmenopausal Women in Xi’an Urban Area - Shun-Zhi Liu; Hong Yan; Peng Xu; Jian-Ping Li; Gui-Hua Zhuang; Bo-Feng Zhu; She-Min Lu (Biological Trace Element Research, 2009)

Enhancing viability of two biocontrol yeasts in liquid formulation by applying sugar protectant combined with antioxidant - Jia Liu; Shi-Ping Tian; Bo-Qiang Li; Guo-Zheng Qin (BioControl, 2009)

Genetic mapping of quantitative trait loci associated with β-amylase and limit dextrinase activities and β-glucan and protein fraction contents in barley - Kang Wei; Da-wei Xue; You-zong Huang; Xiao-li Jin; Fei-bo Wu; Guo-ping Zhang (Journal of Zhejiang University-SCIENCE B, 2009)

The ectopic expression of PttKN1 gene causes pleiotropic alternation of morphology in transgenic carnation (Dianthus caryophyllus L.) - Lai-Sheng Meng; Jiang-Ping Song; Shao-Bo Sun; Chong-Ying Wang (Acta Physiologiae Plantarum, 2009)

Differential expression of N-Myc downstream regulated gene 2 (NDRG2) in the rat testis during postnatal development - Wu-Gang Hou; Yong Zhao; Lan Shen; Jie Zhao; Xue-Wu Liu; Zhen Li; Xin-Ping Liu; Li-Bo Yao; Yuan-Qiang Zhang (Cell and Tissue Research, 2009)

Protective effect of DNA-mediated immunization with liposome-encapsulated GRA4 against infection of Toxoplasma gondii - Rui Chen; Shao-hong Lu; Qun-bo Tong; Di Lou; Dong-yan Shi; Bing-bing Jia; Guo-ping Huang; Jin-fu Wang (Journal of Zhejiang University-SCIENCE B, 2009)

Effect of CO2 enrichment on the glucosinolate contents under different nitrogen levels in bolting stem of Chinese kale (Brassica alboglabra L.) - Gui-xiao La; Ping Fang; Yi-bo Teng; Ya-juan Li; Xian-yong Lin (Journal of Zhejiang University-SCIENCE B, 2009)

Cloning and sequence analysis of putative type II fatty acid synthase genes from Arachis hypogaea L. - Meng-Jun Li; Ai-Qin Li; Han Xia; Chuan-Zhi Zhao; Chang-Sheng Li; Shu-Bo Wan; Yu-Ping Bi; Xing-Jun Wang (Journal of Biosciences, 2009)

A semi-supervised learning based method: Laplacian support vector machine used in diabetes disease diagnosis - Jiang Wu; Yuan-Bo Diao; Meng-Long Li; Ya-Ping Fang; Dai-Chuan Ma (Interdisciplinary Sciences: Computational Life Sciences, 2009)

Singlet oxygen formation and chlorophyll a triplet excited state deactivation in the cytochrome b 6 f complex from Bryopsis corticulans - Fei Ma; Xiao-Bo Chen; Min Sang; Peng Wang; Jian-Ping Zhang; Liang-Bi Li; Ting-Yun Kuang (Photosynthesis Research, 2009)

No spatial memory deficit exists in Kunming mice that recently recovered from motor defects following 3-nitropropionic acid intoxication - Xiao-Min Li; Bing-Gen Zhu; Jian-Bo Ni; Chun-Yan Cao; Jie-Ping Zhang; Xu-Dong Zhao; Rong-Shen Zhu (Neuroscience Bulletin, 2009)

Part V—sorption of pharmaceuticals and personal care products - Bo Pan; Ping Ning; Baoshan Xing (Environmental Science and Pollution Research, 2009)

A shotgun phosphoproteomics analysis of embryos in germinated maize seeds - Tian-Cong Lu; Ling-Bo Meng; Chuan-Ping Yang; Gui-Feng Liu; Guan-Jun Liu; Wei Ma; Bai-Chen Wang (Planta, 2008)

Part IV—sorption of hydrophobic organic contaminants - Bo Pan; Ping Ning; Baoshan Xing (Environmental Science and Pollution Research, 2008)

Molecular actions guiding neural regeneration in planarian - Yan-Fen Zhang; Bo-Ping Ye; Da-Yong Wang (Neuroscience Bulletin, 2008)

Characterization of Citrus tristeza virus strains from southern China based on analysis of restriction patterns and sequences of their coat protein genes - Bo Jiang; Ni Hong; Guo-Ping Wang; John Hu; Jian-Kun Zhang; Cai-Xia Wang; Yong Liu; Xu-Dong Fan (Virus Genes, 2008)

Vesicular stomatitis virus matrix protein gene enhances the antitumor effects of radiation via induction of apoptosis - Xiao-Bo Du; Jin-Yi Lang; Jian-Rong XU; You Lu; Yan-Jun Wen; Ju-Mei Zhao; Peng Diao; Zhi-Ping Yuan; Bin Yao; Ling-Yu Fan; Guo-Qing Wang; Li Liu; et al. (Apoptosis, 2008)

Autophagy is activated and might protect neurons from degeneration after traumatic brain injury - Yan-Bo Zhang; Sheng-Xing Li; Xi-Ping Chen; Li Yang; Yun-Ge Zhang; Ran Liu; Lu-Yang Tao (Neuroscience Bulletin, 2008)

Geographic distribution patterns and status assessment of threatened plants in China - Yin-Bo Zhang; Ke-Ping Ma (Biodiversity and Conservation, 2008)

Characterization of cDNAs associated with lignification and their expression profiles in loquat fruit with different lignin accumulation - Lan Lan Shan; Xian Li; Ping Wang; Chong Cai; Bo Zhang; Chong De Sun; Wang Shu Zhang; Chang Jie Xu; Ian Ferguson; Kun Song Chen (Planta, 2008)

Evaluation of the long-term memory for thermosensation regulated by neuronal calcium sensor-1 in Caenorhabditis elegans - Hua-Yue Ye; Bo-Ping Ye; Da-Yong Wang (Neuroscience Bulletin, 2008)

Molecular control of memory in nematode Caenorhabditis elegans - Hua-Yue Ye; Bo-Ping Ye; Da-Yong Wang (Neuroscience Bulletin, 2008)

Carnivory and active hunting by the planktonic testate amoeba Difflugia tuberspinifera - Bo-Ping Han; Tian Wang; Qiu-Qi Lin; Henri J. Dumont (Hydrobiologia, 2008)

Notch activation promotes cell proliferation and the formation of neural stem cell-like colonies in human glioma cells - Xue-Ping Zhang; Gang Zheng; Lian Zou; Hui-Ling Liu; Li-Hong Hou; Peng Zhou; Dan-Dan Yin; Qi-Jun Zheng; Liang Liang; Su-Zhen Zhang; Lei Feng; Li-Bo Yao; et al. (Molecular and Cellular Biochemistry, 2007)

A new cytotoxic cholesterol sulfate from marine sponge Halichondria rugosa - Hong-Jun Zhang; Jing-Bo Sun; Hou-Wen Lin; Zeng-Lei Wang; Hua Tang; Ping Cheng; Wan-Sheng Chen; Yang-Hua Yi (Natural Product Research, 2007)

Phenotypic plasticity rather than locally adapted ecotypes allows the invasive alligator weed to colonize a wide range of habitats - Yu-Peng Geng; Xiao-Yun Pan; Cheng-Yuan Xu; Wen-Ju Zhang; Bo Li; Jia-Kuan Chen; Bao-Rong Lu; Zhi-Ping Song (Biological Invasions, 2007)

Hydrogen peroxide-induced chlorophyll a bleaching in the cytochrome b 6 f complex: a simple and effective assay for stability of the complex in detergent solutions - Xiao-Bo Chen; Xiao-Hui Zhao; Yi Zhu; Yan-Dao Gong; Liang-Bi Li; Jian-Ping Zhang; Ting-Yun Kuang (Photosynthesis Research, 2007)

Identification of label-retaining cells in nasopharyngeal epithelia and nasopharyngeal carcinoma tissues - Hong-Bo Zhang; Cai-Ping Ren; Xu-Yu Yang; Lei Wang; Hui Li; Ming Zhao; Hong Yang; Kai-Tai Yao (Histochemistry and Cell Biology, 2007)

Computational analysis of genetic loci required for amphid structure and functions and their possibly corresponding microRNAs in C. elegans - Ya-Ou Hu; Yang Sun; Bo-Ping Ye; Da-Yong Wang (Neuroscience Bulletin, 2007)

Carvedilol protected diabetic rat hearts via reducing oxidative stress - He Huang; Jiang Shan; Xiao-hong Pan; Hui-ping Wang; Ling-bo Qian (Journal of Zhejiang University-SCIENCE B, 2006)

Expression analysis of the NDRG2 gene in mouse embryonic and adult tissues - Xiao-Lan Hu; Xin-Ping Liu; Yan-Chun Deng; Shu-Xin Lin; Lin Wu; Jian Zhang; Li-Feng Wang; Xiao-Bin Wang; Xia Li; Lan Shen; Yuan-Qiang Zhang; Li-Bo Yao (Cell and Tissue Research, 2006)

Ciona intestinalis as an emerging model organism: Its regeneration under controlled conditions and methodology for egg dechorionation - Li-ping Liu; Jian-hai Xiang; Bo Dong; Pavanasam Natarajan; Kui-jie Yu; Nan-er Cai (Journal of Zhejiang University-SCIENCE B, 2006)

Study on energy transfer between carotenoid and chlorophyll a in cytochrome b 6 f complex from Bryopsis corticulans - Bin-Xing Li; Ping Zuo; Xiao-Bo Chen; Liang-Bi Li; Jian-Ping Zhang; Jian-Ping Zhang; Ting-Yun Kuang (Photosynthesis Research, 2006)

Protein and hordein fraction content in barley seeds as affected by sowing date and their relations to malting quality - Jun-cong Qi; Jin-xin Chen; Jun-mei Wang; Fei-bo Wu; Lian-pu Cao; Guo-ping Zhang (Journal of Zhejiang University-SCIENCE B, 2005)

Genetic relationships within Brassica rapa as inferred from AFLP fingerprints - Jianjun Zhao; Xiaowu Wang; Bo Deng; Ping Lou; Jian Wu; Rifei Sun; Zeyong Xu; Jaap Vromans; Maarten Koornneef; Guusje Bonnema (Theoretical and Applied Genetics, 2005)

Scattering properties of atmospheric aerosols over Lanzhou City and applications using an integrating nephelometer - Zhang Wu; Hu Bo; Chen Changhe; Du Ping; Zhang Lei; Feng Guanghong (Advances in Atmospheric Sciences, 2004)

Sequences of Transgene Insertion Sites in Transgenic F4 Common Carp - Bo Wu; Yong-Hua Sun; Ya-Ping Wang; Yan-Wu Wang; Zuo-Yan Zhu (Transgenic Research, 2004)

Rhizopus arrhizus – a producer for simultaneous saccharification and fermentation of starch waste materials to l(+)-lactic acid - Bo Jin; Li Ping Huang; Paul Lant (Biotechnology Letters, 2003)

Frame design of remote sensing monitoring for volcanic activities in Changbai mountains - Li-qun Bo; Yun-ping Zhao; Ren-kui Hua (Chinese Geographical Science, 2003)

Prism adaptation with delayed visual error signals in the monkey - Shigeru Kitazawa; Ping-Bo Yin (Experimental Brain Research, 2002)

Genetic Diversity of Chinese Native Pigs Inferred from Protein Electrophoresis - Xiaoqiu Wu; Bo Ding; Ya-Ping Zhang (Biochemical Genetics, 1999)

Abstracts of the 6th FECS Conference 1998 Lectures - F. Sherwood Rowland; Donald R. Blake; B. R. Larsen; Anne Lindskog; Peter J. Peterson; W. Peter Williams; T. J. Wallington; M. J. Pilling; N. Carslaw; D. J. Creasey; D. E. Heard; P. Jacobs; et al. (Environmental Science and Pollution Research, 1998)